GARNET MATERIALS FOR Li SECONDARY BATTERY

Through liquid phase sintering and electric field assisted sintering technology, high-performance lithium-charged garnet films and powders are prepared, solving the compatibility and stability problems of garnet materials in solid-state batteries in the prior art, and achieving improved performance and safety enhancement of solid-state batteries.

JP2025060723AActive Publication Date: 2025-04-10QUANTUMSPACE BATTERY INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024221469
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2014-07-18
Filing Date
2024-12-18
Publication Date
2025-04-10
Estimated Expiration
2034-10-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively manufacture and integrate high-performance garnet materials suitable for solid-state batteries, especially in terms of compatibility and stability with other solid-state battery components.

Method used

Using an innovative process, lithium-charged garnet films and powders with excellent conductivity and mechanical properties are prepared through liquid phase sintering methods and electric field-assisted sintering technology, and applied to electrolytes and cathode materials of solid-state batteries.

Benefits of technology

It realizes efficient preparation and integration of garnet materials, improves the overall performance of solid-state batteries, including conductivity, mechanical strength and electrochemical stability, avoids the growth of metal patterns, and enhances the safety and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060723000001_ABST
    Figure 2025060723000001_ABST
Patent Text Reader

Abstract

To provide a lithium-loaded garnet in a thin film and powder form as catholytes, electrolytes, and anolytes for a solid-state lithium secondary battery.SOLUTION: A bilayer includes a metal foil or metal powder disposed in contact with a lithium-filled garnet thin film which is a thin sintered garnet film having a thickness of less than 50 μm and greater than 10 nm and being bonded to the metal foil or metal powder on at least one side of the film, and is selected from a particular formula.SELECTED DRAWING: Figure 36
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] (CROSS-REFERENCE TO RELATED APPLICATIONS) This application was filed on October 7, 2013, and is related to forming a garnet material using a sintering process. METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH SINTE U.S. Provisional Patent Application No. 61 / 887,451, entitled "RING PROCESS," filed January 13, 2014. , U.S. Provisional Patent Application No. 61 / 9 entitled GARNET THIN FILM ELECTROLYTE No. 26,910, filed June 4, 2014, which discloses a method for forming garnet materials using reaction sintering. METHODS AND SYSTEMS FOR FORMING GARNET MATERIAL WITH REACTIVE No. 62 / 007,417, filed July 18, 2014, entitled "SINTERING" Fine-grained lithium-ion conductive thin film garnet ceramics (FINE GRAINED LITHIUM-IO U.S. Provisional Patent Application No. 62 / 026,271, entitled "CONDUCTING THIN FILM GARNET CERAMICS"; and Garnet Catholyte and Solid-State Electrochemical Devices and Sintering of Components (Garnet Catholyte and Sintering of Solid State Electrochemical Devices) This application claims priority to U.S. Provisional Patent Application No. 62 / 026,440, entitled "A METHOD AND COMPONENTS" Each of these provisional patent applications is incorporated herein by reference in its entirety for all purposes. is incorporated into it. [Background technology]

[0002] BACKGROUND OF THE INVENTION There is a great demand for cleaner forms of stored energy. Clean Energy Storage An example of this is Li + Rechargeable lithium (Li) in which ions move from the negative electrode to the positive electrode ion batteries (i.e., Li-ion secondary batteries). In the case of containers and transport, due to safety and energy density considerations, liquid components (e.g., Uses solid-state Li-ion batteries made from all-solid-state materials, as opposed to batteries containing flammable liquid electrolytes Solid-state Li-ion batteries incorporating Li-metal anodes have significantly lower It is also advantageous to have a small electrode capacity and a correspondingly increased energy density.

[0003] A crucial component of solid-state batteries is the electrolyte, which electrically separates the positive and negative electrodes. In many cases, it is intimately mixed with the positive electrode active material to improve ionic conductivity therein. The third important component in some Li-ion batteries is the anode material. anode material (i.e., anode material; e.g., Li-metal) or in contact with it. However, currently available electrolytes, catholytes, and anolytes Even within the operating voltage range of solid-state batteries, the It is also not stable when in contact with metal fluorides.

[0004] Garnets (e.g., Li-filled garnets) are used as catholytes, electrolytes, and It is a class of oxides that may be suitable for use as anolytes. However, garnet materials still have a suitable morphology (e.g., thin films or nanostructured powders). and to have sufficient conductivity and / or particle connectivity to function well enough. Although certain garnet materials and processing techniques are known (e.g., U.S. Patent Nos. 8,658,317, 8,092,941, and 7,901,658; U.S. Patent Application Publication No. 2013 / 00850 Nos. 55, 2011 / 0281175, 2014 / 0093785, and 2014 / 0170504; and Bonderer "Free-Standing Ultrathin Ceramic Foils," J of the American Ceramic Society, 2010, 93(11):3624 - 3631; and Murugan et al. (See the literature, Angew Chem. Int. Ed. 2007, 46, 7778-7781), these materials and techniques are Such problems include, but are not limited to, insufficient conductivity or processing conditions that are incompatible with certain solid-state battery components. It suffers from various defects.

[0005] Therefore, in particular, garnet films and garnet powders as cathode active materials in all-solid-state batteries With respect to material integration, improved methods for making and processing garnet materials are needed. The following disclosure is based in part on these and related arts to which the present disclosure pertains. It offers many solutions to other problems. Summary of the Invention

[0006] (Summary of the Invention) Disclosed herein are catholytes, electrolytes, and anodic oxides for solid-state lithium secondary batteries. Lithium-stuffed garnet in thin film and powder form as light Also disclosed herein are novel and inventive methods of making and using the novel Garnet catholytes, electrolytes, and anolytes, and novel materials incorporating these materials In contrast to known garnets, the method described herein and materials are uniquely designed for electrochemical devices (e.g., solid-state batteries) and The morphology, conductivity, density, porosity, and surface properties (e.g., roughness) suitable for use in batteries are , flatness, absence of surface cracks and defects), as well as chemical, temperature, and voltage stability It has sexuality. [Brief explanation of the drawings]

[0007] BRIEF DESCRIPTION OF THE DRAWINGS [Figure 1] 1 illustrates an example of liquid phase sintering by the flux sintering method described herein.

[0008] [Figure 2] 1 shows a plot of oxygen partial pressure as a function of calcination temperature for producing certain calcined oxides.

[0009] [Figure 3] A trilayer battery component is shown in which a metal layer (eg, metal powder or metal foil) is disposed between and in contact with two electrolyte (eg, Li-filled garnet) layers.

[0010] [Figure 4]

[0023] A method of calcining or sintering the garnet particles or garnet-metal-garnet triple layers described herein is provided, which includes applying pressure to the layers using a plate (which can be a die plate or a setter plate) during the calcining or sintering step.

[0011] [Figure 5] An example of a method for calcining or sintering a garnet layer (e.g., a garnet bilayer, trilayer, or garnet-active material composite layer) is provided, where the weight of the die (or setter) plate provides the only external pressure applied to the calcined or sintered layer.

[0012] [Figure 6] FIG. 1 shows scanning electron microscopy (SEM) and focused ion beam (FIB) microscopy of thin garnet films made by the reactive sintering method described herein using applied pressure but no additional lithium source powder.

[0013] [Figure 7] Figure 1 shows the x-ray diffraction (XRD) pattern (intensity on the y-axis, 2-θ on the x-axis) of a thin garnet film prepared by reactive sintering without additional lithium source powder at approximately 1150 °C. The labeled peaks [(112), (312), (400), (204), (224)] correspond to the crystalline phase of Li7La3Nb2O13.

[0014] [Figure 8] These images show dense garnet thin films fabricated by reactive sintering using applied pressure. The scale bar in the left image is 10 μm. The scale bar in the right image is 100 μm.

[0015] [Figure 9]Figure 1 shows a conductive phase space map of lithium-lanthanum-zirconia-alumina produced by the methods described herein, showing the total conductivity (20 °C) as a function of Li and Al in LixLa3Zr2O12·yAl2O3 (where x ranges from 5.5 to 9 (the x-axis of the plot is 5.5 to 9.0); and y ranges from 0 to 1 (the y-axis of the plot is 0 to 2)) for several different processing temperature / time combinations. The image on the left is for material processed at 1075 °C; the image in the middle is for material processed at 1150 °C; and the image on the right is for material processed at 1200 °C.

[0016] [Figure 10] The graph shows the grain size (top plot), density (middle plot), and conductivity (bottom plot) as a function of Li content and processing temperature / time for LixLa3Zr2O12·yAl2O3 (where x ranges from 5.5 to 9; and y ranges from 0 to 1). Compositions marked A, B, C, and D were sintered at 1075°C for 6 hours. These compositions possess both small grain size and conductivities >10-4 S / cm. Composition A is characterized by Li6.3La3Zr2O12·0.35Al2O3; composition B is characterized by Li6.3La3Zr2O12·0.67Al2O3; composition C is characterized by Li7La3Zr2O12·0.67Al2O3; and composition D is characterized by Li7La3Zr2O12·Al2O3. The subscripts and molar coefficients in these compositions describe the amount of each of the raw materials used to make these compositions.

[0017] [Figure 11]Comparative lithium-lanthanum-zirconia-alumina compositions are shown in comparison to inventive compositions A, B, C, and D described herein. Composition A is characterized by Li6.3La3Zr2O12·0.35Al2O3; composition B is characterized by Li6.3La3Zr2O12·0.67Al2O3; composition C is characterized by Li7La3Zr2O12·0.67Al2O3; and composition D is characterized by Li7La3Zr2O12·Al2O3. The subscripts and molar coefficients of these compositions describe the amounts of each of the raw materials used to make these compositions.

[0018] [Figure 12] Scanning electron microscope images of lithium-filled garnet films LixLa3Zr2O12·yAl2O3 (where x ranges from 5.5 to 9; and y ranges from 0 to 1) fabricated by thermal sintering at 1075 °C and with varying Li:Al content are shown.

[0019] [Figure 13] 1 shows a plot of conductivity as a function of Li:Al content in lithium-filled garnet films LixLa3Zr2O12·yAl2O3 (where x ranges from 5.5 to 9; and y ranges from 0 to 1) described herein.

[0020] [Figure 14] Figure 1 shows density plots (x-axis ranges from 5.0 to 9.0; y-axis ranges from 0 to 2.0 in each plot) as a function of Li:Al content in lithium-filled garnet films, LixLa3Zr2O12·yAl2O3, described herein (where x ranges from 5.5 to 9; and y ranges from 0 to 1, and the films were thermally sintered at 1075°C for 6 hours (left plot), 1150°C for 6 hours (middle plot), or 1200°C for 15 minutes (right plot).

[0021] [Figure 15] An example of sintering a cylindrical form element material is shown.

[0022] [Figure 16] 1 shows a membrane sintered by a sintering system in which sintered electrodes are in electrical contact with the membrane at two locations on the membrane surface.

[0023] [Figure 17] 1 shows a membrane sintered using a setter plate with individually addressable electrical contact points.

[0024] [Figure 18] An example is shown in which a galvanic calender roller is used to sinter the film.

[0025] [Figure 19] An example is shown in which a film is sintered using calender rollers, one of which has individually addressable electrical contact points and the other roller is a ground electrode.

[0026] [Figure 20] 1 shows a membrane sintered using a sinter plate, where one or more metal foils are inserted between the sinter membrane and the setter plate.

[0027] [Figure 21] 1 shows a membrane sintered using a sinter plate, where one or more metal powders are interposed between the sinter membrane and the setter plate.

[0028] [Figure 22] Shown is a film sintered using calender rollers, where one roller has a movable spiral design, allowing the contact point between the spiral roller and the thin film to be controllably moved during the sintering process.

[0029] [Figure 23] 1 shows examples of films and rectangular feature elements (eg, thin films) that can be sintered according to the methods described herein.

[0030] [Figure 24] 1 shows sintering in which an electric current is passed through the sintered film.

[0031] [Figure 25] 1 illustrates a method of making an embodiment of the invention disclosed herein.

[0032] [Figure 26] 1 shows an example of a composite electrode fabricated according to the methods described herein for a solid-state battery consisting of an active electrode material interspersed with electrolyte particles prior to sintering. This layer may also contain a conductive additive (e.g., carbon) (not shown).

[0033] [Figure 27] 1 shows a schematic diagram of an example of a fully sintered solid composite electrode.

[0034] [Figure 28] The setup for FAST sintering of electrolyte membranes used in Li-ion solid-state batteries is shown.

[0035] [Figure 29] 1 shows the configuration for FAST sintering of an electrolyte-cathode combination that is expected to operate as a solid-state battery.

[0036] [Figure 30] 1 shows a scanning electron microscope (SEM) image of a free-standing membrane fabricated according to the methods described herein. The scale bar is 100 μm. The arrow indicates the termination boundary. The membrane was imaged edge-up.

[0037] [Figure 31]Figure 31 shows an SEM image (left) of a 40 micron thick free-standing (i.e., substrate-free) garnet film fabricated by sintering the green film between supporting setter plates also composed of garnet material, and Figure 31 (right) shows a magnified portion of the image on the left.

[0038] [Figure 32] 1 shows the particle size distribution of the garnet precursor powder before and after milling.

[0039] [Figure 33] 1 shows the particle size distribution of lithium hydroxide and lanthanum oxide powders before milling.

[0040] [Figure 34] 1 shows the particle size distribution of lithium hydroxide and lanthanum oxide after milling.

[0041] [Figure 35] Cross-sectional SEM of a garnet film bilayer formed by sintering garnet powder. The top layer is Ni (nickel) and the bottom layer is lithium-filled garnet. Scale bar is 30 μm.

[0042] [Figure 36] 36 shows the conductance plot of the bilayer of FIG. 35.

[0043] [Figure 37] Figure 1 shows reaction-sintered Li7La3Zr2O12 using a 100% lithium-filled garnet precursor. Scale bar in top left image is 100 μm; scale bar in top right image is 10 μm; scale bar in bottom image is 10 μm. Films were fabricated by doctor blading with a slot gap of 5 mils.

[0044] [Figure 38]This shows reaction-sintered Li7La3Zr2O12 using 75% w / w lithium-filled garnet precursor and 25% w / w lithium-filled garnet powder. The scale bar in the top left image is 100 μm; the scale bar in the top right image is 10 μm; and the scale bar in the bottom image is 5 μm. The film was fabricated by doctor blading with a slot gap of 5 mils.

[0045] [Figure 39] Figure 1 shows reaction-sintered Li7La3Zr2O12 using 50% w / w lithium-filled garnet precursor and 50% w / w lithium-filled garnet powder. Scale bar in top left image is 100 μm; scale bar in top right image is 10 μm; scale bar in bottom image is 10 μm. Films were fabricated by doctor blading with a slot gap of 5 mils.

[0046] [Figure 40] Figure 1 shows reaction-sintered Li7La3Zr2O12 using 25% w / w lithium-filled garnet precursor and 75% w / w lithium-filled garnet powder. Scale bar in top left image is 100 μm; scale bar in top right image is 10 μm; scale bar in bottom image is 5 μm. Films were fabricated by doctor blading with a slot gap of 5 mils.

[0047] [Figure 41] This shows reaction-sintered Li7La3Zr2O12 using 75% w / w lithium-filled garnet precursor and 25% w / w lithium-filled garnet powder. The scale bar in the top left image is 100 μm; the scale bar in the top right image is 10 μm; and the scale bar in the bottom image is 5 μm. The film was fabricated by doctor blading with a slot gap of 10 mils.

[0048] [Figure 42]This shows a 10 mil sintered Li7La3Zr2O12 reaction using 50% w / w lithium-filled garnet precursor and 50% w / w lithium-filled garnet powder. The scale bar in the top left image is 100 μm; the scale bar in the top right image is 10 μm; and the scale bar in the bottom image is 5 μm. The film was produced by doctor blading with a slot gap of 10 mil.

[0049] [Figure 43] Figure 1 shows reaction-sintered Li7La3Zr2O12 using 25% w / w lithium-filled garnet precursor and 75% w / w lithium-filled garnet powder. Scale bar in top left image is 100 μm; scale bar in top right image is 10 μm; scale bar in bottom image is 10 μm. Films were fabricated by doctor blading with a slot gap of 10 mils.

[0050] [Figure 44] Illustrates various layer structures that can be sintered according to the sintering methods described herein: A) free-standing lithium-filled garnet material; B) free-standing lithium-filled garnet material, optionally including active material, binder, solvent, and / or carbon; C) bilayer having one layer of lithium-filled garnet and one layer of metal powder, metal foil, or metal sheet; D) bilayer having one layer of lithium-filled garnet material, optionally including active material, binder, solvent, and / or carbon, and one layer of metal powder, metal foil, or metal sheet; E) trilayer having two layers of lithium-filled garnet and one layer of metal powder, metal foil, or metal sheet between and in contact with the garnet layers; and F) trilayer having each garnet layer having two layers of lithium-filled garnet material, optionally including active material, binder, solvent, and / or carbon, and one layer of metal powder, metal foil, or metal sheet between and in contact with the garnet layers.

[0051] [Figure 45]A sintering method is shown in which sintered electrodes in electrical contact with the membrane are deposited or sputter-deposited at two locations on the membrane surface and a current is passed between them.

[0052] [Figure 46] An optical image of a dense, free-standing garnet film pellet is shown, along with an SEM image of the free-standing film.

[0053] [Figure 47] FIG. 47 shows the conductivity plot of the SEM membrane of FIG. 46 with Ni backing.

[0054] [Figure 48] 47 shows plating / stripping at high current density for the film of FIG.

[0055] [Figure 49] 1 shows the x-ray diffraction pattern (XRD) of composition C.

[0056] [Figure 50] 1 shows the impedance spectrum of pellets of composition C measured at 30° C.

[0057] [Figure 51] 1 shows the charge-discharge curves of an electrochemical cell with pellets of composition C as the electrolyte cycled at 20 μA / cm 2 .

[0058] [Figure 52] 1 shows a plot of density (g / cm3) as a function of flux volume percent for a 1:1 molar mixture of Li2CO3 and B2O3.

[0059] [Figure 53] 1 shows the impedance spectrum of a lithium-filled garnet bilayer (garnet-Ni).

[0060] [Figure 54]Low-magnification SEM images of bilayers prepared under various oxygen partial pressure conditions are shown (scale bar in each image is 100 μm).

[0061] [Figure 55] High-magnification SEM images of garnet-nickel bilayers prepared under various oxygen partial pressure conditions are shown (scale bar in each image is 20 μm).

[0062] [Figure 56] Figure 1 shows SEM images of garnet-nickel bilayers prepared under various oxygen partial pressure conditions (scale bar in each image in the top and bottom rows is 100 μm; scale bar in each image in the middle row is 20 μm).

[0063] [Figure 57] SEM images of FAST sintered lithium-filled garnet powders are shown. (Top and bottom left: -800°C; 3 amp product) (Top and bottom right: -800°C; 2 amp product) (Top and bottom left: 100 μm scale bars) (Bottom left and bottom right: 10 μm scale bars).

[0064] [Figure 58] SEM images of FAST sintered lithium-filled garnet powder are shown. (Top and bottom left: -800°C; 2 Ampere product) (Top and bottom right: -900°C; 2 Ampere product) (Top and bottom left: 100 μm scale bars) (Bottom left and bottom right: 10 μm scale bars).

[0065] [Figure 59] A half-cell experimental setup with a garnet-nickel bilayer electrolyte is shown.

[0066] [Figure 60] 1 shows a free-standing lithium-filled garnet film.

[0067] [Figure 61]Figure 1 shows electrochemical impedance spectroscopy (EIS, y-axis is imaginary impedance in Ω and x-axis is real impedance in Ω) of lithium-filled garnets compared with Pt and ceramic setter plates and the lower area-specific resistance (ASR) of lithium-filled garnets produced by the sintering method using ceramic setter plates.

[0068] [Figure 62] 1 shows an impedance comparison for pellets sintered in Ar, Ar / H2, or air.

[0069] [Figure 63] Figure 46 shows EIS showing less than 10 Ωcm for a free-standing film, where the film was cut into a 13 mm disc with 7 mm diameter Li deposited on it. DETAILED DESCRIPTION OF THE INVENTION

[0070] (Detailed Description of the Invention) The following description is provided to enable one of ordinary skill in the art to make and use the inventions described herein and to Various modifications are provided to allow for incorporation in the context of a particular application. and various uses for different applications will be readily apparent to one skilled in the art, and are within the meaning of the terms defined herein. The general principles can be applied to a wide range of embodiments. It is not intended to be limited to the embodiments shown, but rather to be in accordance with the principles and methods disclosed herein. The broadest scope consistent with the novel features should be allowed.

[0071] The reader is directed to the following: and the contents of all such documents and documents are hereby incorporated by reference. It is incorporated in the specification. Unless otherwise explicitly stated, each disclosed feature is only one example of a series of general equivalent or similar features. Moreover, any element in a claim that does not explicitly recite a "means for" performing a particular function or a "step for" performing a particular function should not be construed as a "means" or "step" clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of "step of" or "act of" in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112.

[0072] Furthermore, any element in a claim that does not explicitly recite a "means for" performing a particular function or a "step for" performing a particular function should not be construed as a "means" or "step" clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of "step of" or "act of" in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not explicitly recite a "means for" performing a particular function or a "step for" performing a particular function should not be construed as a "means" or "step" clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of "step of" or "act of" in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not explicitly recite a "means for" performing a particular function or a "step for" performing a particular function should not be construed as a "means" or "step" clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of "step of" or "act of" in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not explicitly recite a "means for" performing a particular function or a "step for" performing a particular function should not be construed as a "means" or "step" clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of "step of" or "act of" in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112. Moreover, any element in a claim that does not explicitly recite a "means for" performing a particular function or a "step for" performing a particular function should not be construed as a "means" or "step" clause as defined in paragraph 6 of 35 U.S.C. § 112. In particular, the use of "step of" or "act of" in the claims of the present specification is not intended to invoke the provisions of paragraph 6 of 35 U.S.C. § 112.

[0073] When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object. When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object. When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object. When used, the terms right, left, front, rear, top, bottom, forward, reverse, clockwise, and counterclockwise are used for convenience only and are not intended to imply any particular fixed direction. In fact, they are used to indicate the relative positions and / or directions between various parts of an object.

[0074] (I. Definitions) As used herein, the term "NASICON" refers to a sodium (Na) superionic conductor often characterized by the chemical formula Na Zr2Si 1+x Zr2Si x P<000000-4>O 12 O, where 0 < x < 3 (optionally, where Na, Zr, and / or Si are replaced by isovalent elements). As used herein, the term "NASICON" refers to a sodium (Na) superionic conductor often characterized by the chemical formula Na O, where 0 < x < 3 (optionally, where Na, Zr, and / or Si are replaced by isovalent elements).

[0075] As used herein, the term "LISICON" refers to a lithium (Li) superionic conductor often characterized by the chemical formula Li Zn 2+2x Zn 1-xRefers to a lithium (Li) superionic conductor often characterized by GeO4 vinegar.

[0076] As used herein, the term "positive electrode" refers to the electrode towards which the battery is discharged. and positive ions, e.g., Li + This refers to an electrode in a secondary battery through which the flow of As used, the term "negative electrode" refers to the electrode from which positive ions, e.g., Ba, Li + This refers to the electrode in a secondary battery through which the lithium flows out or moves. Chemical electrodes (i.e., active materials; e.g., NiF x In a battery consisting of The electrode with the cathode chemistry is called the cathode. Instead of a cathode, an anode is used, and instead of a negative electrode, an anode is used. When charged, Li ions are transported to the positive electrode (e.g., NiF x ) towards the negative electrode (Li- metal). When a secondary battery is discharged, Li ions are transferred from the negative electrode (e.g., Li-metal; i.e., the anode) to the positive electrode. poles (e.g., NiF x ; i.e., the cathode).

[0077] As used herein, the term "current collector" refers to a metal that is used to complete an external circuit. A component or layer in a secondary battery through which electrons are conducted into or out of the electrode, In some cases, the current collector is in direct contact with the electrode that conducts current into and out of it. , metals (e.g., Al, Cu, or Ni) laminated on the positive or negative electrode, steel, alloys thereof, or During charging and discharging, electrons move in the opposite direction to the flow of Li ions. , passing through the current collector as it enters and leaves the electrode.

[0078] As used herein, the phrase "at least one member selected from the group" A, B may include a single member from the group, multiple members from the group, or a combination of members from the group. At least one member selected from the group consisting of A, B, or C may be, for example, A alone, B alone, or C alone. C only, and A and B, and A and C, and B and C, and A, B, and C, or A, B, and and any other combination of C.

[0079] As used herein, the term "slot casting" refers to casting a solution, liquid, or slurry. etc., adjacent to, in contact with, or on the substrate on which it is deposited or applied. A solution, liquid, or slurry is applied to a substrate by flowing it through a slot or mold of fixed dimensions that is positioned. In some instances, a slot is used to apply or deposit a thin film or other material. The casting contains slot openings of about 1 to 100 μm.

[0080] As used herein, the phrase "dip-casting" or "dip-coating" refers to the process of applying a coating of a substrate to a substrate by Substrates are moved, often vertically, in and out of solutions, liquids, slurries, etc. It refers to a deposition process in which a solution, liquid, slurry, etc. is applied or deposited onto a substrate.

[0081] As used herein, the term "depositing" refers to the deposition of one precursor species, e.g. , layers of lithium precursor species are successively deposited on a deposition substrate, and then further layers are deposited on a second precursor species, e.g., transition metal precursor species, are deposited successively on a previously deposited layer. This layering process is repeated to create several layers of deposited vapor. As used herein, the term "stacking" refers to stacking electrodes. a layer containing, for example, a layer containing a positive electrode or a cathode active material, with another material, for example, a garnet It also refers to the process of contacting a layer containing an electrolyte. The lamination process involves bonding a layer to the layer being laminated. or involves the reaction or use of a binder that physically maintains contact between the laminated layers. This may also be done.

[0082] As used herein, the phrase "solid catholyte" or "catholyte" refers to a The term refers to a cathode (i.e., positive electrode) active material (e.g., a metal foil optionally containing lithium). It refers to an ionic conductor intimately mixed with or surrounded by silicon dioxide (aluminum fluoride).

[0083] As used herein, the term "electrolyte" refers to an ionically conductive and electrically insulating The electrolyte refers to the material in which the ions in the electrolyte, e.g., Li + While enabling the conduction of , and is useful for electrically insulating the positive and negative electrodes of a secondary battery.

[0084] As used herein, the term "anolyte" refers to an anode material or It is mixed with the node current collector, or layered on top of it, or stacked on top of it. Refers to a layer of ionically conductive material.

[0085] As used herein, the term "green film" refers to a garnet material, a precursor of the binder, a solvent, a carbon, a dispersant, or a combination thereof. The term "unsintered membrane" refers to a green membrane that includes at least one component that is sintered.

[0086] As used herein, the phrase "depositing a cathode current collector" is not intended to be limiting. Although not required, metals such as copper, nickel, aluminum, or combinations thereof may be used as cathodes, catholyte, or a combination thereof, or anode, anolyte, or a combination thereof The metal is provided in vapor or spray form so as to contact the lamination and form an adhesive layer therewith. This refers to the process of providing or supplying a metal layer on a cathode or anode. This results in the formation of a metal layer that is in electrical communication with the cathode or anode.

[0087] As used herein, the term "fabricate" refers to forming a fabricated object. refers to a process or method of forming or causing to form. For example, Fabricating an energy storage electrode includes a process for forming an electrode for an energy storage device; The end result of the process steps or methods that comprise the fabrication of an energy storage electrode is , the creation of materials that function as electrodes.

[0088] As used herein, the phrase "energy storage electrode" refers to, for example, an energy storage electrode. For use in energy storage devices, e.g., rechargeable lithium batteries or Li-secondary batteries As used herein, such an electrode refers to an electrode suitable for rechargeable batteries. It can conduct the electrons and Li ions necessary for charging and discharging the battery.

[0089] As used herein, the phrase "provide" means the provision of something provided, production, or refers to the making, offering, or supply of

[0090] As used herein, the phrase "providing a green thin film" refers to the process of forming a green thin film. Refers to providing, generating, or presenting, or supplying. For example, providing an unsintered thin film means making the unsintered thin film available or supplying the unsintered thin film so that it can be used as described in the methods described herein. That is, it refers to a process of making the unsintered thin film available or supplying the unsintered thin film.

[0091] As used herein, the term "unsintered thin film" refers to a thin film that contains the components and materials described herein but has not been sintered by the sintering methods described herein. Thin means, for example, a film having an average thickness dimension of about 10 nm to about 100 μm. In some examples, thin refers to a film having a thickness of less than about 1 μm, 10 μm, or 50 μm.

[0092] As used herein, the term "lithium-filled garnet" refers to an oxide characterized by a crystal structure related to the garnet crystal structure. Lithium-filled garnets include those of the formula Li La A M' B M''[[ID=Y]] c M'' D Zr[[ID=La]] E O F 、Li A La B M' C M'' D Ta E O F 、or Li A La B M' C M'' D Nb E O F (where 4 < A [[ID=5Y]] < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 13, and M' and M'' are each, in each case independently, selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr​c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 13, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb ) and contains a compound as described herein. The garnets used herein also include the above garnets doped with Al2O3. The garnets used herein also include the above garnets doped such that Al 3+ replaces Li + . As used herein, lithium-filled garnets, and garnets typically, but not limited to, contain Li La3(Zr 7.0 +Nb t1 +Ta t2 )O t3 +0.35Al2O3; where (t1 + t2 + t3 = subscript 2) such that the La:(Zr / Nb / Ta) ratio is 3:2 12 . Also, the garnets used herein typically, but not limited to, contain Li<00***translate error***含まれ;ここで、La:(Zr / Nb / Ta)比が3:2となるように、(t1+t2+t3=下付き文字2)である . Also, the garnets used herein typically, but not limited to, contain Li x La3Zr2O 12 +yAl2O3 (where x is in the range of 5.5 - 9; and y is in the range of 0 - 1). In some examples , x is ⑦, and y is 1.0. In some examples, x is ⑦, and y is 0.35 . In some examples, x is ⑦, and y is 0.7. In some examples, x is ⑦ . Also, the garnets used herein typically, but not limited to, contain Li x La3Zr2O 12 +yAl2O3.

[0093] 存在翻译错误,原文中“ 含まれ;ここで、La:(Zr / Nb / Ta)比が3:2となるように、(t1+t2+t3=下付き文字2)である ”这段内容似乎不完整且表述混乱,影响了准确理解和翻译。请检查或补充完整准确的原文后再让我翻译。另外,原文中多次出现的“⑦”推测可能是特定的数字或标记,但含义不明,也请确认其准确信息。As used herein, garnet includes YAG-garnet (i.e., yttria). Y3Al5O 12 ) is not included. Garnets include pyrope, almandine, spessartine, and grosgrain. La, Hessonite, or Cinnamon Stone, Tsavorite, Uvarovite, and Ando Luddite, and the solid solutions pyrope-almandine-spessarite and Does not contain silicate garnets such as barovite, grossular, and andradite Garnets herein include those of the general formula X3Y2(SiO4)3, where X is Ca, Mg, Fe, and / or Mn. and Y is Al, Fe, and / or Cr).

[0094] As used herein, "garnet precursor chemicals" or "garnet-type electrolytes" The phrase "chemical precursor of" refers to a compound that reacts to form the lithium-loaded garnet compound described herein. These chemical precursors include lithium hydroxide (e.g., Lithium oxide (e.g., LiOH), lithium oxide (e.g., Li2O), lithium carbonate (e.g., LiCO3), zirconium oxide nium (e.g., ZrO2), lanthanum oxide (e.g., La2O3), aluminum oxide (e.g., Al2O 3), aluminum (e.g., Al), aluminum nitrate (e.g., AlNO3), aluminum nitrate nonahydrate, niobium oxide (e.g., Nb2O5), tantalum oxide (e.g., Ta2O5), Not limited to these.

[0095] As used herein, the phrase "garnet-type electrolyte" refers to the The term "garnet electrolyte" refers to an electrolyte containing a lithium-loaded garnet material or a lithium-loaded garnet material as an ionic conductor. vinegar.

[0096] As used herein, the phrase "alumina doped" refers to alumina doped with Al2O3. This means replacing certain components of another material, e.g., garnet. Lithium-filled garnets are doped with aluminum (Al). garnet, which replaces an element in the formula of smectite (which may be, for example, Li or Zr) This refers to the .

[0097] As used herein, the phrase "aluminum reaction vessel" refers to a vessel in which a chemical reaction can take place. Thus, precursor chemicals are used to form products, e.g., lithium-loaded garnet materials. Refers to the container or receptacle into which something is placed.

[0098] As used herein, the phrase "high conductivity" means a conductivity of 10 -5 More than S / cm In some instances, high conductivity refers to a conductivity of 10 at room temperature. -5 Includes conductivities greater than S / cm.

[0099] As used herein, the term "partial replacement of Zr with a higher valence species" means The phrase is Zr 4+ and, for example, 5 + or 6 + For example, some Nb 5+ exists at the lattice site in the garnet crystal structure where Zr atoms exist, and 4+ to If possible, Zr is partially replaced by Nb. This is also called niobium doping. Called.

[0100] As used herein, "subscripts and molar coefficients in empirical formulas are used in the examples given." The phrase "based on the amount of raw material initially batched to make the product" is used in conjunction with the subscript (e.g., Li7La3Zr2O 12 7, 3, 2, 12, and 0.35 in Al2O3) are the coefficients for the given material. (e.g., Li7La3Zr2O 12 ·0.35Al2O3) are used to produce chemical precursors (e.g. LiOH, La2O3, ZrO2, Al2O3).

[0101] As used herein, the phrase "electrochemical device" refers to an energy storage device. devices, such as, but not limited to, electrochemical reactions, e.g., conversion chemical reactions; for example, [ka] This refers to a Li-ion secondary battery that operates or generates electricity or current.

[0102] As used herein, the phrase "film thickness" refers to the distance between the top and bottom surfaces of a film or refers to the median measured distance. As used herein, the top and bottom surfaces are the largest surfaces. The term refers to the side of the membrane that has a cross section.

[0103] As used herein, the term "grain" refers to a grain that is separated from the rest of the material. Refers to a region of material within the bulk of the material that has a distinguishing physical boundary. For example, some In materials, there are often both crystalline and amorphous components of a material with the same chemical composition. Both are distinguished from each other by the boundary between the crystalline and amorphous components. The approximate diameter of the constituent boundaries is referred to herein as the grain size.

[0104] As used herein, "d 50 The term "diameter" includes, but is not limited to, scanning electron microscope (SEM) as measured by microscopy or other particle size analysis techniques such as microscopy or dynamic light scattering; Refers to the median diameter in the diameter distribution. D 50 has 50% of particles larger than the listed size. Small characteristic dimensions are included.

[0105] As used herein, the phrase "active electrode material" or "active material" refers to a rechargeable battery. It is suitable for use as a rechargeable Li battery and does not undergo chemical reactions during charge / discharge cycles. For example, "active cathode material" refers to the material that is used to charge and discharge a rechargeable Li battery. Between them, there is a metal fluoride which converts to lithium fluoride.

[0106] As used herein, the phrase "active anode material" is defined above. Anode materials suitable for use in rechargeable Li batteries containing active cathode materials such as In some instances, the active material is lithium metal. In some of the methods used, the sintering temperature is adjusted to the This is high enough to melt lithium metal.

[0107] As used herein, the phrase "conductive additive" refers to an additive that improves the conductivity of the cathode. This refers to a material that is mixed with the cathode active material to improve the cathode conductivity. Examples include carbon, as well as various Various forms of carbon, e.g., Ketjenblack, VGCF, acetylene black, graphite nanotubes, nanofibers, and the like, and combinations thereof. However, the present invention is not limited to these.

[0108] As used herein, the term "solvent" refers to any of the components or A liquid suitable for dissolving or solvating a material. For example, a solvent may be a garnet A liquid suitable for dissolving the components used in the sintering process, e.g., the binder, e.g. For example, toluene can be mentioned.

[0109] As used herein, the phrase "removing the solvent" refers to removing the solvent from the solution described herein. refers to the process of extracting or separating a component or material from the component or material in which it is placed. Removing the solvent includes, but is not limited to, evaporating the solvent. This involves using a vacuum or reduced pressure to drive the solvent out of the mixture, e.g., the green film. In some instances, the solvent is evaporated to reveal solvated biomass in the thin film after solvent removal. The thin film containing the binder and solvent is heated, or optionally vacuumed or It is also placed in a reducing atmosphere environment.

[0110] As used herein, the phrase "sintering a film" refers to thermal sintering or electric field assisted sintering. The use of sintering can densify (make denser or lower) the thin films described herein. Sintering refers to the process of melting a solid mass of material to a point where it completely liquefies. The process includes forming the solid mass by heat and / or pressure without melting the solid mass. nothing.

[0111] As used herein, the term "FAST" refers to the acronym for electric field assisted sintering. In some instances, FAST also refers to flash sintering.

[0112] As used herein, the phrase "applying a DC or AC electric field" refers to applying a The electric field is changed or created by a power source, and a current flows through the material, and direct current (DC) is delivered from the power source. The process of electrically connecting a power source to a material so that it produces either alternating current (AC) or alternating current (AC) Refers to...

[0113] As used herein, the term "binder" refers to a material that aids in the adhesion of other materials. For example, as used herein, polyvinyl butyral refers to a material that is It is a binder because it is useful for bonding materials together. Other binders include polymethyl methacrylate. These examples of binders are not intended to cover the entire range of binders contemplated herein. It is not intended to be limiting with respect to the present invention, but merely serves as an example.

[0114] As used herein, the phrase "casting a membrane" refers to the process by which a liquid or slurry is cast onto a membrane. a liquid or slurry into a mold or onto a substrate to form or be formed into a film. Casting refers to the process of feeding or transferring a material to a surface using a doctor blade, a Mayer rod, or a cone. Macorta, gravure coater, microgravure, reverse comma coater, slot This can be done by die, slip, and / or tape casting, as well as other methods known to those skilled in the art. This can be done.

[0115] As used herein, the phrase "applying pressure" refers to applying pressure to a subject by applying pressure to the subject using an external device, e.g. , calendering refers to the process of inducing pressure in another material.

[0116] As used herein, the term "about" refers to the limitation of the number with which it is associated. About, in some instances, means ±5% around the number qualified by the word about. For example, evaporating the solvent at about 80°C can be performed at 79°C, 80°C, or 81°C. The method includes evaporating the solvent by

[0117] As used herein, the phrase "about 1 to about 600 minutes" refers to a period of time ranging from 0.1-1.1 to 540-660 minutes. As used herein, "about 10 μm to about 100 μm" refers to a range of minute values ​​and any value therebetween. The phrase "refers to the range of 9 μm-11 μm to 90 μm-110 μm and integer values ​​therebetween."

[0118] As used herein, the phrase "about 500°C to about 900°C" refers to a temperature range from 450°C to 550°C. It refers to the range of 810℃ to 990℃ and integer temperature values ​​therebetween.

[0119] As used herein, "burning out the binder or calcining the green film" means The phrase "burn out" refers to a process for burning out or removing a binder. Chemical reactions that cause the binder to become denser or less porous, for example, combustion, or The film containing the binder is treated with an oxidizing species to induce a chemical reaction that sinters the film with the binder. , refers to the process of optionally heating in an environment containing, for example, O2.

[0120] As used herein, the phrase "composite electrode" refers to an electrode that is made up of multiple materials. For example, a composite electrode may contain active materials in an intimate mixture or in an ordered layer. a garnet-type cathode material and a garnet-type electrolyte, or the active material and the electrolyte are interdigitated. Examples of suitable active cathode materials include, but are not limited to, garnet-type electrolytes. Not determined.

[0121] As used herein, the phrase "inert setter plate" refers to a generally flat and does not react with the material being sintered. These setter plates can be metal or ceramic, and optionally are sintered. The material to be sintered is then sintered to provide for the diffusion of gases and vapors through it. , can be porous.

[0122] As used herein, the phrase "operating in a constant voltage amplitude mode" refers to a material While maintaining the amplitude of the applied DC voltage or the RMS amplitude of the AC voltage at a constant value, The electrochemical process allows the resistance, or impedance, of the material to vary as a function of Refers to the process.

[0123] As used herein, the phrase "operating in a constant current amplitude mode" refers to a constant A DC current or an AC current of RMS amplitude flows through a material while an applied voltage changes the resistance or impedance of the material. This refers to an electrochemical process that allows the electrical conductivity of a material to change as a function of temperature.

[0124] As used herein, the phrase "freestanding thin film" refers to a thin film that is adhered or supported by an underlying substrate. refers to an unsupported membrane. In some instances, a free-standing thin film has no adhesive or adhesive bonded to it. Free-standing membranes that can be mechanically manipulated or moved without the need for a fixed substrate. is.

[0125] As used herein, the term "porosity" refers to pores, e.g., nanopores, mesopores , or refers to a material containing micropores.

[0126] As used herein, the term "pyrolysis" refers to the decomposition of a material at high temperatures in the absence of oxygen. refers to the thermochemical decomposition of organic materials in

[0127] As used herein, the term "electroplating" refers to the process of depositing a material, e.g., a metal, It refers to the process of deposition in conjunction with the use of electricity.

[0128] As used herein, the phrase "average pore diameter size of about 5 nm to about 1 μm" refers to the pore wherein the inner diameter of the pores therein is, for example, about 5 nm for nanopores, or For example, micropores refer to material that is physically spaced apart by approximately 1 μm.

[0129] As used herein, the phrase "the polymer is stable at voltages above about 3.8 V" exhibits destructive chemistry when a voltage greater than 3.8 V is applied to it relative to a lithium reference electrode. As used herein, a destructive chemical reaction refers to a polymer that does not undergo a reaction. This refers to a chemical reaction that deteriorates the functionality of the polymer in which it is used. For example, if a polymer: If it is ionically conductive and useful as a Li-conductor in a Li battery, the destructive reaction is Conductivity in S / cm over the product's lifetime under useful operating conditions of temperature and cycling When measured, the polymer's ability to conduct Li-ions is reduced or deteriorated by more than 10% This is a reaction that causes

[0130] As used herein, the term "permeated" means the penetration of one material into another. It refers to the state of entering into or causing one material to come together with another. For example, when carbon is infiltrated into a porous garnet, this is because the carbon is infiltrated into the porous garnet. refers to the process of bringing a substance into contact with a substance and causing it to become intimately mixed with the substance.

[0131] As used herein, the phrase "operating with a ramp voltage" refers to operating with an applied voltage of refers to an electrical process that gradually or systematically increases or decreases voltage over a period of time.

[0132] As used herein, the phrase "operating at lamp power" refers to operating at a power refers to the process of gradually or systematically increasing or decreasing a quantity over a period of time.

[0133] As used herein, the phrase "operating with a lamp current" refers to operating with an applied current. refers to an electrical process that gradually or systematically increases or decreases voltage over a period of time.

[0134] As used herein, the terms "nanostructured" or "nano-dimensional" refer to structures Refers to composite materials in which the components are separated by nano-dimensions. For example, nano-composite materials may include Li-containing compounds, such as LiF, and Fe-containing compounds, such as Fe; Here, the Fe and LiF regions are visually contrasting regions of various nano-domains. When measured by TEM micrographs according to the identification of , or 2 to 5 nm, or 5 to 15 nm, or 5 to 20 nm, or the like.

[0135] (II. Garnet Materials) Disclosed herein are nanostructured lithium-filled garnet-based powders. Also disclosed herein are nanoparticles having physical dimensions less than 10 μm, e.g., d 50 Crystal grain size is 10 μm In some examples, the lithium-filled garnet thin film has crystal grains smaller than 1000 nm. In some of these examples, the membranes are less than 50 μm thick. , membranes with thicknesses less than 50 μm are several meters to several kilometers long. In some instances, the membrane has a high conductivity, which in some instances is greater than 10 -4 S / In some instances, the membrane is strong, has good mechanical integrity, and is lithium-ion. Prevents the ingress of lithium dendrites when used as an electrolyte in lithium secondary batteries. Some of these membranes contain a cathode active material and, optionally, a binder, a dispersant, , solvents, and other electronic and ionic conductors. Described are methods for making these exemplary films.

[0136] In another example, described herein is alumina-doped and high Several lithium-loaded gallium nitride (Li-AlN) nanocrystals possess a unique combination of ionic conductivity and small grain size. In some instances, these compositions are lithium-loaded garnets. Lower temperature and shorter reaction time conditions than previously known possible for In some instances, novel sintering methods are utilized, among which Some of the new lithium-filled gas batteries utilize an argon gas environment rather than air. Further, in some instances, finely ground garnet powder, and or garnet precursors and / or metal powders to produce unique thin film structures. is manufactured as follows. The disclosure herein describes several novel lithium-filled garnet ceramics having aluminum therein, for example, as alumina (Al2O3), which, conveniently and surprisingly, have the properties of high ionic conductivity and small crystal grain size. and which have the properties of high ionic conductivity and small crystal grain size. and which have the properties of high ionic conductivity and small crystal grain size. and which have the properties of high ionic conductivity and small crystal grain size.

[0137] (a. Lithium-filled garnet) (i. Electrolyte) In one example, the method described herein is Li A La B M' c M'' D Zr E O F Li A La B M' C M'' D T a E O F Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4, 0 ≦ C ≦ 2, 0 ≦ D ≦ 2; 0 ≦ E < 2 , 10 < F < 14, and M' and M' are each, independently in each case, selected from Al, Mo, W, Nb, Sb, Ca, Ba , Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≦ 2.5; 0 ≦ d < 2; 0 ≦ e < 2, 10 < f < 14, and Me'' is a metal selected from Nb, Ta, V , W, Mo, or Sb), a garnet-type electrolyte material selected from is included.

[0138] In one example, the method described herein is Li A La B M' c M'' D Zr E O F 、Li A La B M' C M'' D T a E O F 、Li A La B M' C M'' D Nb E O F [[ID=]](where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2 、10 < F < 13, and M' and M' are each, independently in each case, Al, Mo, W, Nb, Sb, Ca, Ba 、Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me''<00001​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​It contains a garnet-type electrolyte selected from

[0140] In one example, the method described herein is Li A La B M' C M'' D Nb E O F (where 4 < A < 8 .5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 13, and M' and M' are each, respectively independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta in each case ) and contains a garnet-type electrolyte selected from

[0141] In one example, the method described herein is Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 14, and Me'' is a metal selected from Nb, Ta, V, W , Mo, or Sb) and contains a garnet-type electrolyte selected from .

[0142] In one example, the method described herein is Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 13, and Me'' is a metal selected from Nb, Ta, V, W , Mo, or Sb) and contains a garnet-type electrolyte selected from .

[0143] In some embodiments, the garnet materials described herein are used as electrolytes . In some of these embodiments, the garnet has the formula [Chemical formula] ; where 5.0 < x < 9 and 0.1 < y < 1.5. In some of these examples , the electrolyte is Li x La3Zr2O 12 ·0.35Al2O3. In other ones of these examples , the electrolyte is Li7La3Zr2O 12 ·0.35Al2O3.

[0144] In some examples where the garnet is an electrolyte, the garnet contains neither Nb, Ta , nor W, nor Mo, which means herein that the concentration of these elements (e.g., Nb, Ta, W, or M o) is 10 parts per million (ppm) or less. In some examples , the concentration of these elements (e.g., Nb, Ta, W, or Mo) is 1 part per million (ppm) or less. In some examples, the concentration of these elements (e.g., Nb, Ta, W, or Mo) is 0.1 parts per million (ppm) or less.

[0145] In some examples, the lithium-filled garnets described herein have the general formula Li x A 3B2O 12 (where 5 < x < 7). In some of these examples , A is a large ion occupying an 8-fold coordination lattice site. In some of these examples , A is La, Sr, Ba, Ca, or a combination thereof. In some examples In this case, B is a smaller, more highly charged ion occupying an octahedral site. In some of these examples, B is Zr, Hf, Nb, Ta, Sb, V, or a combination thereof. In some of these examples, the composition is Li x A3B2O 12 0.3 to 1 mole per In some of these examples, the composition is doped with Li. x A3B2O 12 The alloy was doped with 0.35 moles of Al per mole.

[0146] In some instances, the lithium-filled garnet is Li7La3Zr2O 12 (LLZ) and In some instances, the LLZ is doped with lumina. The reactant is doped by adding Al2O3 to the precursor mixture. The LLZ is doped with aluminum in an aluminum reactor that contacts the LLZ. do.

[0147] In some instances, the alumina-doped LLZ can be, for example, 10 -4 Over S / cm It has high conductivity.

[0148] In some instances, higher conductivity can be achieved by replacing a portion of the Zr with a higher valence species, e.g., It is observed when partially substituted with Nb, Ta, Sb, or a combination of these. The conductivity is 10 -3 It can reach a height of as much as S / cm.

[0149] In some examples, the compositions described herein comprise Li x A3B2O 12 0.35 moles per Al-doped Li x A3B2O 12 In some of these examples, x is 5. In some other instances, x is 5.5. In yet other instances, x is 6.0. In some other instances, x is 6.5. In other instances, x is 7.0. In the example, x is 7.5.

[0150] In some instances, the garnet-based composition comprises Li x A3B2O 12 0.3, 0.35, 0.4, 0. 45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or 1 mole of Al was added. It is being played.

[0151] In some instances, the garnet-based composition comprises Li x A3B2O 12 0.35 moles of Al per It is grouped.

[0152] In the examples herein, the subscripts and molar coefficients in the empirical formulas are used to prepare the examples described. The amount of raw material initially batched to prepare the product is used.

[0153] In some examples, the present disclosure provides compositions comprising lithium-filled garnets and Al2O3. In one example, the lithium-filled garnet is doped with alumina. In some instances, the lithium-filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F By characterized in that: <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E≦2、10<F≦13で and M' and M'' are, independently in each occurrence, absent or selected from Al, Mo, W, Nb, Sb, Ca, are each independently selected from Ba, Sr, Ce, Hf, Rb, or Ta; and The molar ratio of the net to Al2O3 is 0.05 to 0.7.

[0154] In some examples, the present disclosure provides compositions comprising lithium-filled garnets and Al2O3. In one example, the lithium-filled garnet is doped with alumina. In some instances, the lithium-filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F By characterized in that: <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E≦2、10<F≦13で and M' and M'' are, independently in each occurrence, absent or selected from Al, Mo, W, Nb, Sb, Ca, are each independently selected from Ba, Sr, Ce, Hf, Rb, or Ta; and Li: The molar ratio of Al is 0.05 to 0.7.

[0155] In some examples, the present disclosure provides compositions comprising lithium-filled garnets and Al2O3. In one example, the lithium-filled garnet is doped with alumina. In some instances, the lithium-filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F By Characterized in that, in the formula, 2 < A < 10, 2 < B < 6, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E ≤ 3, 8 < F ≤ 14 , M' and M'' are, in each case independently, either absent or each independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta; and the garnet: the molar ratio of Al2O3 is 0.01 - 2.

[0156] In some examples, the present disclosure provides a composition comprising a lithium - filled garnet and Al2O3. In one example, the lithium - filled garnet is doped with alumina. In some examples, the lithium - filled garnet has the empirical formula Li A La B M' c M'' D Zr E O F Characterized in that, in the formula, 2 < A < 10, 2 < B < 6, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E ≤ 3, 8 < F ≤ 14<l , M' and M'' are, in each case independently, either absent or each independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta; and the molar ratio of Li:Al is 0.01 - 2.

[0157] [[ID=​​​​​​​​​​​​​​​​​- including a pant, where 0 < e < 2. In some examples, the lithium-filled garnet is the lithium-filled garnet described in U.S. Provisional Patent Application No. 61 / 887,451, filed on October 7, 2013, and titled "METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH SINTERING PROCESS", the entire content of which is hereby incorporated by reference in its entirety for all purposes. a method and system for forming garnet materials with a sintering process is.

[0158] <s In some of the above examples, A is 6. In some other examples, A is 6.5 In other examples, A is 7.0. In some other examples, A is 7.5. In still other examples, A is 8.0.

[0159] In some of the above examples, B is 2. In some other examples, B is 2.5 In other examples, B is 3.0. In some other examples, B is 3.5. In still other examples, B is 3.5. In still other examples, B is 4.0.

[0160] 0In some of the above examples, C is 0.5. In other examples, C is 0.6. In some other examples, C is 0.7. In some other examples, C is 0.8. In some other examples, C is 0.9. In other examples, C is 1.0. In still other examples, C is 1.1. In some examples, C is 1.2. In other examples, C is 1.3. In some other examples, C is 1.4. In some other examples, C is 1.5. ​In some other instances, C is 1.6. In other instances, C is 1.7. In still other instances, In some instances, C is 1.8. In some instances, C is 1.9. In yet other instances, C is 2.0. In some other examples, C is 2.1. In some other examples, C is 2.2. In some other examples, C is 2.3. In some other examples, C is 2.4. In other examples, In some instances, C is 2.5. In other instances, C is 2.6. In some instances, C is 2.7. In still other examples, C is 2.8. In other examples, C is 2.9. In another example, C is 3.0.

[0161] In some of the above examples, D is 0.5. In other examples, D is 0.6. In some other instances, D is 0.7. In some other instances, D is 0.8. In some other examples, D is 0.9. In other examples, D is 1.0. In still other examples, In some instances, D is 1.1. In some instances, D is 1.2. In other instances, D is 1.3. In some other instances, D is 1.4. In some other instances, D is 1.5. In certain other examples, D is 1.6. In other examples, D is 1.7. In still other examples, In some instances, D is 1.8. In some instances, D is 1.9. In yet other instances, D is 2.0. In some other examples, D is 2.1. In some other examples, D is 2.2. In some other examples, D is 2.3. In some other examples, D is 2.4. In other examples, In some instances, D is 2.5. In other instances, D is 2.6. In some instances, D is 2.7. In still other examples, D is 2.8. In other examples, D is 2.9. In another example, D is 3.0.

[0162] In some of the above examples, E is 0.5. In other examples, E is 0.6. In some other instances, E is 0.7. In some other instances, E is 0.8. In some other instances, E is 0.9. In other instances, E is 1.0. In still other instances, In some instances, E is 1.1. In some instances, E is 1.2. In other instances, E is 1.3. In some other instances, E is 1.4. In some other instances, E is 1.5. In certain other examples, E is 1.6. In other examples, E is 1.7. In still other examples, In some instances, E is 1.8. In some instances, E is 1.9. In yet other instances, E is 2.0. In some other examples, E is 2.1. In some other examples, E is 2.2. In some other examples, E is 2.3. In some other examples, E is 2.4. In other examples, In some instances, E is 2.5. In other instances, E is 2.6. In some instances, E is 2.7. In still other examples, E is 2.8. In other examples, E is 2.9. In another example, E is 3.0.

[0163] In some of the above examples, F is 11.1. In other examples, F is 11.2. In some other instances, F is 11.3. In some other instances, F is 11.4. In some other instances, F is 11.5. In other instances, F is 11.6. In one example, F is 11.7. In another example, F is 11.8. In another example, F is 11. In some other instances, F is 9. In some other instances, F is 12. In some other instances, F is 12. In some other instances, F is 12.2. In other instances, F is 12.3. In yet another example, F is 12.3. In one example, F is 12.4. In yet another example, In some instances, F is 12.5. In other instances, F is 12.6. In some other instances, F is 12.6. In some other instances, F is 12.8. In some other instances, E is 12. In another example, F is 13.

[0164] In some instances, provided herein are compounds having the empirical formula [ka] wherein 5.0 <x<9かつ0.1<y<1.5である。いく In some examples, x is 5. In other examples, x is 5.5. In some examples, In some examples, x is 6. In other examples, x is 7. In some examples, x is 7.5. In other examples, x is 8. In some examples, In some examples, y is 0.3. In some examples, y is 0.35. In other examples, y is 0.4. In some examples, y is 0.45. In some examples, y is 0.5. In other examples, y is 0.55. In some examples, y is 0.6. In some instances, y is 0.7. In some instances, y is 0.75. In other instances, y is 0.8. In some examples, y is 0.85. In other examples, y is 0.9. In some examples, y is 0.95. In other examples, y is 1.0.

[0165] In some examples, provided herein are compounds having the empirical formula Li 7.0 La3(Zr t1 +Nb t2 +Ta t 3) O 12 +0.35Al2O3. In this formula, La and (Zr + Nb + Ta) is 3:2, so that t1 + t2 + t3 = subscript 2.

[0166] In some examples, provided herein is a compound having the empirical formula LiLaZrO 12 0.35Al2O3 The composition is characterized by:

[0167] In some of the above examples, A is 5, 6, 7, or 8. In certain examples, A is 7.

[0168] In some of the above examples, M' is Nb and M'' is Ta.

[0169] In some of the above examples, E is 1, 1.5, or 2. In certain examples, E is 2.

[0170] In some of the above examples, C and D are 0.

[0171] In some examples, provided herein are garnets having a molar ratio of garnet:Al2O3 of 0.1 In some examples, the Li:Al ratio is between 7:0.2 and 7:1.3. In some examples, the Li:Al ratio is 7:0.3 to 7:1.2. The ratio is from 7:0.3 to 7:1.1. In some examples, the Li:Al ratio is from 7:0.4 to 7:1.0. In some examples, the Li:Al ratio is 7:0.5 to 7:0.9. The ratio is 7:0.6 to 7:0.8. In some examples, the Li:Al ratio is about 7:0.7. In that example, the Li:Al ratio is 7:0.7.

[0172] In some examples, provided herein are garnet:Al2O3 molar ratios of 0.15 The composition is 0.55.

[0173] In some examples, provided herein are garnet:Al2O3 molar ratios of 0.25 The composition is 0.45.

[0174] In some examples, provided herein are garnet:Al2O3 molar ratios of 0.35 It is a composition in which

[0175] In some examples, provided herein are crystalline ... It is a composition.

[0176] In some examples, provided herein is a lithium-filled garnet having the empirical formula Li7La3Zr2O 12 and is doped with aluminum. do.

[0177] In some instances, the lithium-filled garnet is Li7La3Zr2O 12 (LLZ) and In some instances, the LLZ is doped with lumina. The reactant is doped by adding Al2O3 to the precursor mixture. The LLZ is doped with aluminum in an aluminum reactor that contacts the LLZ. When LLZ is doped with alumina, it is possible to obtain a conductive layer that increases the conductivity of the lithium-filled garnet. In some instances, this increased conductivity is due to increased ionic conductivity. (e.g., Li + ) is called conductivity.

[0178] (ii. Catholyte) Cathodic solutions suitable for use with the components, devices, and methods described herein The material may be, but is not limited to, Li A La B M' c M'' D Zr E O F , Li A La B M' C M'' D Ta E O F , Li A La B M' C M'' D Nb E O F (where 4 <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E<2、10< F<14, and M' and M'' are each, independently in each occurrence, Al, Mo, W, Nb, Sb, Ca, Ba, Sr , Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 <a<7 .7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 14, and Me'' is a metal selected from Nb, Ta, V, W , Mo, or Sb). Examples of garnet materials include those selected from these. In some embodiments, the garnet material is Li A La B M' c M'' D Zr E O F . In some other embodiments, the garnet material is Li A La B M' C M'' D Ta E O F . In other embodiments, the garnet material is Li<000023o>La B M' C M'' D Nb E O F .

[0179] In the above examples, the values of the subscripts (4 < A < 8.5, 1. < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14) characterize the ratios of the reactants used to make the garnet material[[ID=5l]] . Some deviation from these reactant ratios may be present in the garnet product as well. As used herein, the garnet precursor refers to the reactants used to produce or synthesize the garnet

[0180] In the above examples, the values of the subscripts (e.g., 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F ≤ 13) characterize the ratios of the reactants used to make the garnet material . Some deviation from these reactant ratios may be present in the garnet product It may be. As used in this specification, the garnet precursor refers to the reactant used to produce garnet.

[0181] In the above example, as the values of the subscripts, 4 < A < 8.5, 1.5 < B < 4, C < 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14 can also be cited. In some examples, C is equal to or less than 1.99

[0182] In the above example, as the values of the subscripts, 4 < A < 8.5, 1.5 < B < 4, C < 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F ≤ 13 can also be cited. In some examples, C is equal to or less than 1.99

[0183] In one embodiment, the garnet is a lithium-filled garnet.

[0184] In some embodiments, the garnet is characterized by Li a La b Zr c Al d Me'' e O f where the subscript is characterized by the above values.

[0185] In some embodiments, the lithium-filled garnet is a lithium lanthanum zirconium oxide mixed with aluminum oxide. In some of these examples the lithium lanthanum zirconium oxide is characterized by the formula Li La3Zr2O 7.0 +0.35Al2O3, where the subscripts and coefficients represent the molar ratios determined based on the reactants used to make the garnet. 12 ​​​​​​​

[0186] In some embodiments, the ratio of La:Zr is 3:2. Garnet is Li 7.0 La3(Zr t1 +Nb t2 +Ta t3 )O 12 +0.35Al2O3; where La:(Zr / Nb / Ta) (t1+t2+t3=subscript 2) so that the ratio is 3:2.

[0187] In some instances, the garnet is Li x La3Zr2O 12 +yAl2O3, where x is 5.5 to 9; and y ranges from 0 to 1. In some examples, x is 7 and y is 0. It is 35.

[0188] The catholytes described herein may, in some embodiments, be formed by adding a carbon electronic conductive additive. The lithium conductive glass filled with the additive, the lithium conductive polymer binder, and the active material. The active material loading is high energy density. In some instances, the volume percentage may be greater than 50% to allow for a high degree of The garnet is sintered and maintains a porosity of >70% to allow for the volume of other components The disclosure herein addresses some of the problems associated with assembling solid-state energy storage devices. This overcomes the problem of, for example, but not limited to, well-developed particle indirection. contact points and reduced grain spacing allowing for greater current flow without significant voltage drop Sintering the composite electrode with electrical resistance; also, sintering the entire device (electrodes and electrolyte) in one process. manufacturing processes that use flammable liquid electrolytes, which can be a safety hazard in some cases; and a method for fabricating a solid-state energy storage device that eliminates the need for a membrane using a FAS. T sintering to reduce process time and cost in electrochemical device fabrication; and FAST Sintering is performed to densify the components of the electrode composite without significant interdiffusion or adverse chemical reactions. There is a way to do this.

[0189] (iii. Composite materials) In some embodiments, disclosed herein is a method of In some examples, the device is a composite electrochemical device fabricated by , an active electrode material, an electrolyte, a conductive additive, and combinations thereof. at least one layer containing a material; and at least one layer containing a garnet-type electrolyte. In some examples, the composite material has the structure shown in FIG. 26 or FIG.

[0190] In some embodiments, the device comprises at least one active anode material. The active anode material may be carbon, silicon, silicon oxide, tin, or any of these. and alloys thereof, and combinations thereof.

[0191] In some embodiments, disclosed herein are anodes and anode current collectors. at least one layer including a garnet solid electrolyte (SSE) in contact with the anode; at least one layer comprising porous garnet in contact with said garnet SSE; wherein the porous garnet optionally contains carbon, a lithium conducting polymer, an active cation and combinations thereof. being; and at least including an aluminum cathode current collector in contact with the porous garnet one layer (where the porous garnet layer is at least 70% porous by volume; and where the garnet is Li A La B M' c M'' D Zr E O F 、Li A La B M' C M'' D Ta E O F 、Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14, and M' and M'' are each, independently in each case, selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where here 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f ≤ 13, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb ), and is selected from the materials), and the active electrode material is NCA (lithium nickel cobalt aluminum oxide), LMNO (lithium manganese nickel oxide) ), NMC (lithium nickel manganese cobalt oxide), LCO (lithium cobalt oxide, i.e., LiCoO2), nickel fluoride (NiF x where x is from 0 to 2.5), copper fluoride (CuF y )]]、こ where y is 0 to 2.5), or FeF z (where z is selected from 0 to 3.5) In some instances, the cathode material is a layered material for an electrochemical device. The layer structure is substantially as shown in FIG.

[0192] In an embodiment, both sides of the layer comprising the anode and the anode current collector each independently comprise: In contact with the garnet SSE layer, each garnet SSE layer is independently a porous garnet is in contact with the layer.

[0193] (b. powder) (i. Nanocrystalline powder) In some instances, the lithium-filled garnet powders described herein are nano-sized. Therefore, these powders have the crystalline structure of lithium-loaded garnets. domains, where the median crystalline domain diameter is a domain having a physical dimension (e.g., diameter) of about In some examples, the crystalline domains are about 0.5 nm to about 10 μm in diameter. In some other examples, the crystalline domains are about 1 nm in diameter. In another example, the crystalline domains are about 1.5 nm in diameter. In still other examples, the crystalline domains are about 2 nm in diameter. In some instances, the crystalline domains are about 3.0 nm in diameter. In another example, the crystalline domains are about 3.5 nm in diameter. The crystalline domains are about 4.0 nm in diameter. In some examples, the crystalline domains are In some other instances, the crystalline domains are about 5.5 nm in diameter. In another example, the crystalline domains are about 6.0 nm in diameter. In another example, the crystalline domains are about 6.5 nm in diameter. In some instances, the crystalline domains are about 7.0 nm in diameter. In yet another example, the crystalline domains are about 8.0 nm in diameter. In some examples, the crystalline domains are about 8.5 nm in diameter. The crystalline domains are about 8.5 nm in diameter. In some other examples, the crystalline domains In another example, the crystalline domains are about 9 nm in diameter. In still other examples, the crystalline domains are about 10 nm in diameter. In some instances, the crystalline domains are about 10.5 nm in diameter. In yet another example, the crystalline domains are about 11.0 nm in diameter. In other examples, the crystalline domains are about 12.0 nm in diameter. In some examples, the crystalline domains are about 12.5 nm in diameter. The crystalline domains are approximately 13.5 nm in diameter. In yet another example, the crystalline domains are about 14.5 nm in diameter. In other examples, the crystalline domains are about 15.0 nm in diameter. In another example, the crystalline domains are about 15.5 nm in diameter. In another example, the crystalline domains are about 16.0 nm in diameter. In some instances, the crystalline domains are about 17 nm in diameter. In some other examples, the crystalline domains are about 17.5 nm in diameter. The crystalline domains are about 18 nm in diameter. In another example, the crystalline domains are about 18.5 nm in diameter. In some instances, the crystalline domains are about 19.5 nm in diameter. In another example, the crystalline domains are about 20 nm in diameter. In some instances, the crystalline domains are about 20.5 nm in diameter. In some other instances, the crystalline domains are about 21.5 nm in diameter. In one example, the crystalline domains are about 22.0 nm in diameter. In another example, the crystalline domains are approximately 22.5 nm in diameter. In some instances, the crystalline domains are about 23.0 nm in diameter. In yet another example, the crystalline domains are about 24.0 nm in diameter. In some instances, the crystalline domains are about 24.5 nm in diameter. In some other instances, the crystalline domains are about 25.5 nm in diameter. In another example, the crystalline domains are about 26 nm in diameter. In other instances, the crystalline domains are about 27 nm in diameter. The crystalline domains are about 27.5 nm in diameter. In some examples, the crystalline domains are In yet another example, the crystalline domains are about 28.5 nm in diameter. In other examples, the crystalline domains are about 29.0 nm in diameter. In some other examples, the crystalline domains are about 29.5 nm in diameter. In another example, the crystalline domains are about 30 nm in diameter. In yet another example, the crystalline domains are about 31 nm in diameter. In some instances, the crystalline domains are about 32 nm in diameter. In yet another example, the crystalline domains are approximately 33 nm in diameter. In another example, the crystalline domains are about 35 nm in diameter. In some instances, the crystalline domains are about 40 nm in diameter. In another example, the crystalline domains are approximately 45 nm in diameter. In yet another example, the crystalline domains are about 55 nm in diameter. In other instances, the crystalline domains are about 60 nm in diameter. In yet another example, the crystalline domains are about 65 nm in diameter. In another example, the crystalline domains are about 70 nm in diameter. In another example, the crystalline domains are about 80 nm in diameter. In some examples, the crystalline domains are about 85 nm in diameter. In another example, the crystalline domains are about 90 nm in diameter. In yet another example, the crystalline domains are about 100 nm in diameter. In still other examples, the crystalline domains are about 150 nm in diameter. In one example, the crystalline domains are about 200 nm in diameter. The crystalline domains are about 250 nm in diameter. In some instances, the crystalline domains are about 350 nm in diameter. In some other examples, the crystalline domains are about 400 nm in diameter. In yet another example, the crystalline domains are about 450 nm in diameter. In another example, the crystalline domains are about 500 nm in diameter. In some instances, the crystalline domains are about 600 nm in diameter. In some examples, the crystalline domains are about 650 nm in diameter. The domains are about 700 nm in diameter. In some instances, the crystalline domains are about In some other instances, the crystalline domains are about 800 nm in diameter. In another example, the crystalline domains are about 850 nm in diameter. In another example, the crystalline domains are about 900 nm in diameter. In some instances, the crystalline domains are about 950 nm in diameter. 0nm.

[0194] (ii. Microcrystalline granular powder) Grain size, as used herein, unless otherwise specified, is determined by microscopy, e.g. , measured by transmission electron microscopy or scanning electron microscopy, or by x-ray diffraction. can be.

[0195] In some examples, provided herein are nanoparticles having a d of less than 10 μm. 50Crystals with diameter In some instances, the membrane has grains of d less than 9 μm. 50 The grains have a diameter In other examples, the grains have a diameter of less than 8 μm. 50 In some instances, , the grain size is less than 7 μm 50 In some instances, the membrane has a diameter of less than 6 μm. 50 Diameter In another example, the film has grains having a d of less than 5 μm. 50 The grains have a diameter In some instances, the membrane has a d of less than 4 μm. 50 It has grains with a diameter. In an example, the membrane has a d of less than 3 μm. 50 In some instances, the film has grains with a diameter , d less than 2 μm 50 In another example, the film has grains with a diameter of less than 1 μm. 50 straight It has crystal grains with a diameter.

[0196] As used herein, the microcrystalline grains in the films described herein are between 10 nm and 10 μm d 50 In some examples, the crystallites in the films described herein have a diameter of 1 00nm~10μm d 50 It has a diameter.

[0197] In some examples, the films described herein have a Young's modulus of about 130-150 GPa. In some other examples, the films described herein have a Vickers hardness of about 5-7 GPa. It has a quality.

[0198] In some instances, the membranes described herein have a porosity of less than 20%. In examples, the membranes described herein have a porosity of less than 10%. In some instances, the membranes described herein have a porosity of less than 5%. The membranes described herein have a porosity of less than 3%. In some instances, the porosity is , measured by pycnometry or mercury porosimetry.

[0199] (c.membrane) (i. Uncalcined film) Described herein are films comprising garnet precursors, optionally including calcined garnet. These films and powders are then heated or heated to form lithium-loaded garnets. These films and powders are then heated to a temperature of 1000°C for 1 hour before the precursors have had sufficient time to react to form the film. In some instances, several layers of lithium-loaded garnet are fabricated. To achieve this, a slurry of the following garnet precursors was added to the calcined film of lithium-loaded garnet: In some instances, the calcined lithium-loaded garnet is layered, deposited, or laminated. A slurry of the following garnet precursors was added to the sintered glass so that it penetrated into the open or porous spaces within the glass. is overlaid, deposited, or laminated onto the calcined film of lithium-loaded garnet.

[0200] In some instances, the present disclosure provides a garnet precursor or optionally a hypothetical In some instances, the thin, free-standing garnet film comprises a fused garnet. These films contain at least one selected from a binder, a solvent, a dispersant, or a combination thereof. In some examples, the garnet solids loading is at least 30% by weight. (w / w). In some instances, the membrane thickness is less than 100 μm.

[0201] In certain instances, the dispersant is fish oil, Mehaden Blown Fish Oil, phosphate esters, rhodal ine(trademark), Rhodoline 4160, phospholan-131(trademark), BYK(trademark) 22124, BYK-22146(trademark) ), Hypermer KD1™, Hypermer KD6™, and Hypermer KD7™.

[0202] In some instances, the membrane includes a substrate adhered thereto. is a polymer, a metal foil, or a metal powder. The substrate is a metal foil. In some examples, the substrate is a metal powder. In some of the above, the metal is Ni, Cu, Al, steel, an alloy thereof, or a combination thereof. is selected from the combination.

[0203] 10. The membrane of claim 1, wherein the solids loading is at least 35% w / w.

[0204] In some instances, the membrane has a solids loading of at least 40% w / w. In some instances, the membrane has a solids loading of at least 45% w / w. Thus, the membrane has a solids loading of at least 50% w / w. In some other examples, the solids loading is at least 60 In some instances, the solids loading is at least 65% w / w. In some other instances, the solids loading is at least 70% w / w. The solids loading is at least 75% w / w. In some instances, the solids loading is less than 75% w / w. At most 80% w / w.

[0205] In some instances, the uncalcined film has a thickness of less than 75 μm and greater than 10 nm. In some examples, the uncalcined film has a thickness of less than 50 μm and more than 10 nm. In the uncalcined membrane, the particles have a maximum physical dimension of less than 1 μm. In some instances, the uncalcined membrane has a median grain size of 0.1 μm to 10 μm. In the examples, the uncalcined film is not adhered to any substrate.

[0206] In some instances, the present disclosure provides a garnet precursor or optionally a hypothetical In some instances, the thin, free-standing garnet film comprises a fused garnet. These films contain at least one selected from a binder, a solvent, a dispersant, or a combination thereof. In some examples, the garnet solids loading is at least 30% by volume. (v / v). In some instances, the membrane thickness is less than 100 μm.

[0207] In some instances, the membrane has a solids loading of at least 40% v / v. In some instances, the membrane has a solids loading of at least 45% v / v. In other examples, the membrane has a solids loading of at least 50% v / v. In some other examples, the solids loading is at least 60% v / v. In some instances, the solids loading is at least 65% v / v. In some other instances, the solids loading is at least 70% v / v. The solids loading is at least 75% v / v. In some instances, the solids loading is less than 75% v / v. At most 80% v / v.

[0208] (a. Calcined film) The uncalcined film described herein is a film that has been heated to about 200°C to 1200°C for about 20 minutes to 10 hours or The calcination can be carried out by heating until the calcination occurs.

[0209] (ii. Unsintered Membrane) In some instances, the garnet-based films are unsintered, referred to as "green" films. and is kilometres long.

[0210] In one embodiment, the present disclosure provides herein a method for making an energy storage electrode. 1. A method for producing a thin film of garnet-type electrolyte comprising: providing a thin film of garnet-type electrolyte; , an active electrode material, a conductive additive, a solvent, a binder, and combinations thereof. and removing solvent, if present in the green thin film. optionally laminating the film to a surface; removing the binder, if present in the film. sintering the film (wherein sintering may be thermal sintering or electric field assisted sintering (FAST)); wherein thermal sintering includes sintering the film at a temperature ranging from about 700°C to about 1200°C for about 1 to about 600°C. minutes and in an atmosphere having an oxygen partial pressure of 1e-1 atmosphere to 1e-15 atmosphere; and ST sintering is performed by heating the film in the range of about 500°C to about 900°C and applying DC or The method includes applying an AC electric field.

[0211] In some of the methods disclosed herein, the green thin film may be from about 10 μm to about 100 μm. In some other of the methods disclosed herein, The green thin film has a thickness of about 20 μm to about 100 μm. In some cases, the green thin film has a thickness of about 30 μm to about 100 μm. In other of the methods described, the green thin film has a thickness of about 40 μm to about 100 μm. In yet another method disclosed herein, the green thin film has a thickness of about 50 μm to about 100 μm. In still other methods disclosed herein, the green thin film has a thickness of about 60 μm. In still other methods disclosed herein, the method comprises: The green thin film has a thickness of about 70 μm to about 100 μm. In some cases, the green thin film has a thickness of about 80 μm to about 100 μm. In some other of the methods described, the green film is about 90 μm to about 100 μm thick. It has a thickness.

[0212] In some of the methods disclosed herein, the green thin film may be from about 10 μm to about 90 μm. In some other of the methods disclosed herein, The green thin film has a thickness of about 20 μm to about 80 μm. In the present invention, the green thin film has a thickness of about 30 μm to about 70 μm. In other of the methods, the green thin film has a thickness of about 40 μm to about 60 μm. In yet another method disclosed herein, the green thin film has a thickness of about 50 μm to about 90 μm. In still other methods disclosed herein, the green thin film has a thickness of about 60 μm to about 90 μm. In still other methods disclosed herein, the green thin film has a thickness of The thickness of the film is about 70 μm to about 90 μm. In this case, the green thin film has a thickness of about 80 μm to about 90 μm. In some others, the green thin film has a thickness of about 30 μm to about 60 μm.

[0213] In some instances, the green film is about 50 percent larger in volume than the sintered film. In some examples, the sintered film has a thickness of about 1 to 150 μm. In some instances, the sintered film has a thickness of about 1 μm. In some examples, the sintered film has a thickness of about 3 μm. In some examples, the sintered film has a thickness of about 4 μm. In some instances, the sintered film has a thickness of about 6 μm. In some of the examples, the sintered film has a thickness of about 7 μm. In some other examples, the sintered film has a thickness of about 9 μm. In one example, the sintered film has a thickness of about 10 μm.

[0214] In some instances, sintering can increase the length of the film by about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 , 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25% The thickness of the film is reduced by about 50, about 40, about 30, about 20, about 10, or about 5% without any increase in thickness. As used herein, thickness refers to the average thickness in the z-direction (as shown in FIG. 23). As used herein, length refers to the average length in the x- or y-direction (as shown in FIG. 23). In some instances, the sintering described herein occurs in a manner that is proportionally greater in the z-direction than in the x- or y-directions. In some instances, sintering occurs primarily in the x- or y-direction, resulting in a reduction in the thickness of the film in the x- or y-direction (as shown in Figure 23). reduces the film thickness in the z-direction proportionally more than in either the y-direction. In this example, sintering reduces the film length in either the x- or y-direction proportionally more than sintering reduces the film length in either the x- or y-direction. Substantially significantly reduces the thickness of the film in the z-direction (as shown in Figure 23). Substantially greater means at least 50%, at least 60%, at least 70%, or less Examples of such a concentration include, but are not limited to, at least 80%, at least 90%, or at least 100%.

[0215] (iii. Sintered film) In some of these examples, the sintered film has a thickness of about 10 nm. In another example, the sintered film has a thickness of about 11 nm. In one example, the sintered film has a thickness of about 12 nm. In some other instances, the sintered film has a thickness of about 13 nm. In some examples, the sintered film has a thickness of about 14 nm. In some of these examples, the sintered film has a thickness of about 16 nm. In some examples, the sintered film has a thickness of about 17 nm. In one example, the sintered film has a thickness of about 18 nm. In another example, the sintered film has a thickness of about 19 nm. In some of these examples, the sintered film has a thickness of about 20 nm. In some other examples, the sintered film has a thickness of about 21 nm. In some other examples, the sintered film has a thickness of about 23 nm. In some other examples, the sintered film has a thickness of about 24 nm. has a thickness of about 25 nm. In some instances, the sintered film has a thickness of about 26 nm. In some of these examples, the sintered film has a thickness of about 27 nm. In some examples, the sintered film has a thickness of about 28 nm. In some examples, the sintered film has a thickness of about 30 nm. In some of these, the sintered film has a thickness of about 31 nm. In one example, the sintered film has a thickness of about 32 nm. In another example, the sintered film has a thickness of about 33 nm. In certain other instances, the sintered film has a thickness of about 34 nm. The sintered film has a thickness of about 35 nm. In some examples, the sintered film has a thickness of about 36 nm. In some of these examples, the sintered film has a thickness of about 37 nm. In some examples, the sintered film has a thickness of about 38 nm. In one example, the sintered film has a thickness of about 40 nm. In some of the examples, the sintered film has a thickness of about 41 nm. In one example, the sintered film has a thickness of about 42 nm. In another example, the sintered film has a thickness of about 43 nm. In certain other examples, the sintered film has a thickness of about 44 nm. In some instances, the sintered film has a thickness of about 45 nm. In some instances, the sintered film has a thickness of about 46 nm. In some of these examples, the sintered film has a thickness of about 47 nm. In some examples, the sintered film has a thickness of about 48 nm. The sintered film has a thickness of about 49 nm. In one example, the sintered film has a thickness of about 50 nm. In some of these examples, the sintered film has a thickness of about 51 nm. In some examples, the sintered film has a thickness of about 52 nm. In some other instances, the sintered film has a thickness of about 54 nm. In some examples, the sintered film has a thickness of about 55 nm. In some of these examples, the sintered film has a thickness of about 57 nm. In some examples, the sintered film has a thickness of about 58 nm. In one example, the sintered film has a thickness of about 59 nm. In another example, the sintered film has a thickness of about 60 nm. do.

[0216] In some of these examples, the sintered film has a thickness of about 11 μm. In other examples, the sintered film has a thickness of about 12 μm. In some other examples, the sintered film has a thickness of about 14 μm. In some other instances, the sintered film has a thickness of about 15 μm. The membrane has a thickness of about 16 μm. In some of these examples, the sintered membrane has a thickness of about 17 μm. In some instances, the sintered film has a thickness of about 18 μm. In some other examples, the sintered film has a thickness of about 19 μm. In some of these examples, the sintered film has a thickness of about 21 μm. In some other examples, the sintered film has a thickness of about 22 μm. In some instances, the sintered film has a thickness of about 23 μm. In other instances, the sintered film has a thickness of about 24 μm. In some other examples, the sintered film has a thickness of about 25 μm. In some examples, the sintered film has a thickness of about 26 μm. In some instances, the sintered film has a thickness of about 27 μm. In some instances, the sintered film has a thickness of about 28 μm. In some other examples, the sintered film has a thickness of about 29 μm. In some of these examples, the sintered film has a thickness of about 30 μm. The sintered film has a thickness of about 31 μm. In some other examples, the sintered film has a thickness of about 32 μm. In some examples, the sintered film has a thickness of about 33 μm. In some instances, the sintered film has a thickness of about 34 μm. In some other instances, the sintered film has a thickness of about 35 μm. In some examples, the sintered film has a thickness of about 36 μm. In some of the examples, the sintered film has a thickness of about 37 μm. In some instances, the sintered film has a thickness of about 38 μm. In some other instances, the sintered film has a thickness of about 39 μm. In some examples, the sintered film has a thickness of about 40 μm. In some examples, the sintered film has a thickness of about 41 μm. The sintered membrane has a thickness of about 42 μm. In one example, the sintered membrane has a thickness of about 43 μm. In some other examples, the sintered film has a thickness of about 44 μm. In some instances, the sintered membrane has a thickness of about 45 μm. In some instances, the sintered membrane has a thickness of about 46 μm. In some of these examples, the sintered film has a thickness of about 47 μm. In some examples, the sintered film has a thickness of about 48 μm. In one example, the sintered film has a thickness of about 49 μm. In another example, the sintered film has a thickness of about 50 μm. In some of these examples, the sintered film has a thickness of about 51 μm. In some other examples, the sintered film has a thickness of about 52 μm. In some instances, the sintered film has a thickness of about 53 μm. In other instances, the sintered film has a thickness of about 54 μm. In some other instances, the sintered film has a thickness of about 55 μm. The conjunctiva has a thickness of about 56 μm. In some of these examples, the sintered membrane is about 5 In some instances, the sintered film has a thickness of about 58 μm. In some other examples, the sintered film has a thickness of about 59 μm. , having a thickness of about 60 μm.

[0217] In some of these examples, the sintered film has a thickness of about 61 μm. In another example, the sintered film has a thickness of about 62 μm. In some other examples, the sintered film has a thickness of about 64 μm. In some other instances, the sintered film has a thickness of about 65 μm. The membrane has a thickness of about 66 μm. In some of these examples, the sintered membrane has a thickness of about 67 μm. In some instances, the sintered film has a thickness of about 68 μm. In some other examples, the sintered film has a thickness of about 69 μm. In some of these examples, the sintered membrane has a thickness of about 71 μm. In some other examples, the sintered film has a thickness of about 72 μm. In some instances, the sintered membrane has a thickness of about 73 μm. In other instances, the sintered membrane has a thickness of about 74 μm. In some other examples, the sintered film has a thickness of about 75 μm. In some examples, the sintered film has a thickness of about 76 μm. In some instances, the sintered film has a thickness of about 77 μm. In some instances, the sintered film has a thickness of about 78 μm. In some other examples, the sintered film has a thickness of about 79 μm. In some of these examples, the sintered film has a thickness of about 80 μm. The sintered membrane has a thickness of about 81 μm. In some other examples, the sintered membrane has a thickness of about 82 μm. In one example, the sintered film has a thickness of about 83 μm. In some instances, the sintered film has a thickness of about 84 μm. In some other instances, the sintered film has a thickness of about 85 μm. In some examples, the sintered film has a thickness of about 86 μm. In some of the examples, the sintered film has a thickness of about 87 μm. In some instances, the sintered film has a thickness of about 88 μm. In some other instances, the sintered film has a thickness of about 89 μm. In some examples, the sintered film has a thickness of about 90 μm. In some examples, the sintered film has a thickness of about 91 μm. The sintered membrane has a thickness of about 92 μm. In one example, the sintered membrane has a thickness of about 93 μm. In some other examples, the sintered film has a thickness of about 94 μm. In some instances, the sintered membrane has a thickness of about 95 μm. In some instances, the sintered membrane has a thickness of about 96 μm. In some of these examples, the sintered film has a thickness of about 97 μm. In some examples, the sintered film has a thickness of about 98 μm. In one example, the sintered film has a thickness of about 99 μm. In another example, the sintered film has a thickness of about 100 μm. do.

[0218] In certain other instances, the sintered film has a thickness of about 100 nm. In some other examples, the sintered film has a thickness of about 1 μm. In some examples, the sintered film has a thickness of about 2 μm. In some other instances, the sintered film has a thickness of about 2 μm. In some examples, the sintered film has a thickness of about 5 μm. The film has a thickness of about 3 μm. In another example, the sintered film has a thickness of about 4 μm. In some examples, the sintered film has a thickness of about 300 nm. The sintered film has a thickness of about 400 nm. In some instances, the sintered film has a thickness of about 200 nm. .

[0219] In some of these examples, the sintered film has a thickness of about 101 μm. In other examples, the sintered film has a thickness of about 102 μm. In some instances, the sintered film has a thickness of about 103 μm. In some other instances, the sintered film has a thickness of about 105 μm. The conjunctiva has a thickness of about 106 μm. In some of these examples, the sintered membrane is about In some instances, the sintered film has a thickness of about 107 μm. In some other examples, the sintered film has a thickness of about 109 μm. In some of these examples, the sintered film has a thickness of about 111 μm. In some other instances, the sintered film has a thickness of about 112 μm. In some instances, the sintered film has a thickness of about 113 μm. In some other instances, the sintered film has a thickness of about 115 μm. In some examples, the sintered film has a thickness of about 116 μm. In some cases, the sintered film has a thickness of about 117 μm. In some other examples, the sintered film has a thickness of about 119 μm. In some examples, the sintered film has a thickness of about 120 μm. In some instances, the sintered film has a thickness of about 121 μm. In one example, the sintered film has a thickness of about 122 μm. In other examples, the sintered film has a thickness of about 124 μm. The membrane has a thickness of about 125 μm. In some instances, the sintered membrane has a thickness of about 126 μm. In some of these examples, the sintered film has a thickness of about 127 μm. In some instances, the sintered film has a thickness of about 128 μm. The conjunctiva has a thickness of about 129 μm. In some instances, the sintered membrane has a thickness of about 130 μm. In some of these examples, the sintered film has a thickness of about 131 μm. In other examples, the sintered film has a thickness of about 132 μm. In some instances, the sintered film has a thickness of about 133 μm. In some other instances, the sintered film has a thickness of about 135 μm. The conjunctiva has a thickness of about 136 μm. In some of these examples, the sintered membrane is about In some instances, the sintered film has a thickness of about 137 μm. In some other examples, the sintered film has a thickness of about 139 μm. has a thickness of about 140 μm.

[0220] In some of these examples, the sintered film has a thickness of about 141 μm. In other examples, the sintered film has a thickness of about 142 μm. In some instances, the sintered film has a thickness of about 143 μm. In some other instances, the sintered film has a thickness of about 145 μm. The conjunctiva has a thickness of about 146 μm. In some of these examples, the sintered membrane is about In some instances, the sintered film has a thickness of about 147 μm. In some other examples, the sintered film has a thickness of about 149 μm. has a thickness of about 150 μm.

[0221] (iv. Nanocrystalline Films and Microcrystalline Granular Films) In some examples, provided herein are polymers having a d of less than 10 nm. 50 Crystals with diameter In some instances, the film has grains of d less than 9 nm. 50 It has grains with a diameter In other examples, the grains have a diameter of less than 8 nm. 50 In some instances, the diameter The grain size is less than 7 nm. 50 In some instances, the membrane has a diameter of less than 6 nm. 50 Has a diameter In another example, the film has grains with a d of less than 5 nm. 50 having grains with a diameter In some instances, the film has a d of less than 4 nm. 50 Other examples include grains with a diameter. In this case, the film has a d of less than 3 nm. 50 In some instances, the film has grains having a diameter of: d less than 2nm 50 In another example, the film has grains with a diameter of less than 1 nm. 50 diameter The crystal grains have the following structure:

[0222] In some examples, provided herein are nanoparticles having a d of less than 10 μm. 50 Crystals with diameter In some instances, the membrane has grains of d less than 9 μm. 50 The grains have a diameter In other examples, the grains have a diameter of less than 8 μm. 50 In some instances, , the grain size is less than 7 μm 50 In some instances, the membrane has a diameter of less than 6 μm. 50 diameter In other examples, the film has grains having a d of less than 5 μm. 50 Grains with diameter In some instances, the membrane has a d of less than 4 μm. 50 having grains with a diameter In other examples, the membrane has a d of less than 3 μm. 50 It has grains with a diameter. The membrane has a d of less than 2 μm. 50In another example, the film has grains having a diameter of 1 μm. d less than m 50 It has grains with a diameter.

[0223] As used herein, the microcrystalline grains in the films described herein are between 10 nm and 10 μm d 50 In some examples, the crystallites in the films described herein have a diameter of 1 00nm~10μm d 50 It has a diameter.

[0224] (v. free-standing membrane) In some instances, the present disclosure provides methods for producing a medicament for the treatment of ... describes a free-standing thin film garnet-type electrolyte fabricated by

[0225] In some embodiments, disclosed herein is a method of The electrolyte is a free-standing thin film garnet-type electrolyte manufactured by

[0226] In some embodiments, the free-standing membrane has a thickness of less than 50 μm. In some embodiments, the membrane has a thickness of less than 40 μm. In some other embodiments, the membrane is less than 20 μm thick. In an embodiment, the thickness of the membrane is less than 10 μm. The thickness is less than 5 μm.

[0227] In some embodiments, the membrane has a thickness of less than 45 μm. In some embodiments, the thickness of the membrane is less than 35 μm. In some embodiments, the thickness of the membrane is less than 25 μm. In some other embodiments, the membrane has a thickness of less than 15 μm. In some embodiments, the thickness of the membrane is less than 5 μm. It is less than 1 μm.

[0228] In some embodiments, the thickness of the membrane is from about 1 μm to about 50 μm. In some embodiments, the thickness of the film is about 10 μm to about 50 μm. In some other embodiments, the thickness of the membrane is from about 20 μm to about 50 μm. In another embodiment, the thickness of the membrane is about 40 μm to about 50 μm. do.

[0229] In some embodiments, the thickness of the membrane is from about 1 μm to about 40 μm. In some embodiments, the thickness of the film is about 10 μm to about 40 μm. In some other embodiments, the thickness of the membrane is from about 20 μm to about 40 μm. In another embodiment, the thickness of the membrane is about 20 μm to about 30 μm. do.

[0230] In some examples, described herein are thin, free-standing sintered garnets. a film, wherein the film thickness is less than 50 μm and greater than 10 nm, and the film is substantially flat. and the garnet optionally includes a metal or metal powder on at least one side of the film. It is bonded to the current collector (CC) membrane.

[0231] In some instances, the thin, free-standing sintered garnet film is less than 20 μm or less than 10 μm. In some instances, the thin, free-standing sintered garnet film has a thickness of less than 5 μm. In some instances, the thin, free-standing sintered garnet film has a surface roughness of less than In some instances, thin, free-standing sintered garnet The sintered glass film has a surface roughness of less than 2 μm. In some examples, the sintered glass film is thin and free-standing. The garnet film has a surface roughness of less than 1 μm. In one example, the garnet has a surface roughness of less than 0.1 μm. In some instances, the garnet has a median grain size of 2.0 μm to 5.0 μm. The grain size is 0.015 μm.

[0232] (vi. Substrate-bound membrane) In some of the membranes described herein, the membrane is made of a polymer, glass, or metal. In some of these examples, the membrane is attached to a substrate selected from the group consisting of: In some of these examples, the substrate to which the film is bonded is a current collector (CC). is made from nickel (Ni), copper (Cu), steel, stainless steel, combinations of these, and alloys of these. In some of these examples, the film comprises a metal selected from the group consisting of: In some other examples, the membrane is bonded to a metal current collector (CC) on one side of the membrane. In yet another example, the CC is bonded to a metal current collector (CC) at the two garnet films. is disposed between and in contact with the

[0233] (vii. Double and triple layers) In some examples, described herein are two different lithium-loaded garnets. a triple layer including a metal foil or metal powder disposed between and in contact with thin metal films; In some instances, the middle layer is a metal foil. The middle layer is a metal powder. In some instances, the metal is Ni. In other instances, In some instances, the metal is Al. In other instances, the metal is Fe. In some instances, The metal is steel or stainless steel. In some examples, the metal is Ni, Cu, Al, or Fe. In some examples, the triple layer has the structure shown in FIG. In some examples, the triple layer has the structure shown in Figure 4 below. In some examples, the triple layer has the structure shown in Figure 29 below. The stack has the structure shown in Figure 44(E)(F).

[0234] In some examples, the present invention provides a method for manufacturing a lithium-filled garnet thin film. In some instances, the bilayer comprises a metal foil or metal powder placed in contact with the surface of the substrate. In another example, one layer of the bilayer is a metal foil. In another example, one layer of the bilayer is a metal powder. In some examples, the metal is Ni. In other examples, the metal is Al. In other instances, the metal is Fe. In some instances, the metal is steel or stainless steel. In some instances, the metal is an alloy or combination of Ni, Cu, Al, or Fe. In some instances, the bilayer has the structure shown in Figure 44(C)(D). In some instances, the bilayer has the structure shown between the sintered plates of FIG. 20 or FIG. do.

[0235] In some of the bilayers and trilayers described herein, the garnet has the formula : LiALaBM'cM''DZrEOF, LiALaBM'CM''DTaEOF, LiALaBM'CM''DNbEOF (where, 4 <A<8.5、 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F ≤ 13, and M' and M'' are each independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta) , or LiaLabZrcAldMe''eOf (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f ≤ 13, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb) ); LiALaBM'cM''DZrEOF (where the molar ratio of Al2O3 to garnet is 0.05 - 0.7); or LigLa3Zr2O12 - Al2O3 (where 5.5 < g < 8.5 and the molar ratio of Al2O3 to garnet is 0.05 - 1.0), characterized by one of them. (viii. Multilayer) In some examples, what is described herein is a number of stacks or combinations of the aforementioned layers, bilayers, and / or trilayers. In some examples, two or more bilayers are stacked in a continuous

[0236] combination. In some other examples, two or more trilayers are stacked in a continuous combination. In some examples, what is inserted between these continuous combination stacks is a cathode active material, an anode active material, and / or a current collector. (ix. Film Dimensions) In some examples, the thin films described herein have a thickness of less than 50 μm. In some other examples, the thin films described herein have a thickness of less than 45 μm. In one example , the thin films described herein have a thickness of less than 40 μm. In still other examples .

[0237] (ix. Film Dimensions) In some examples, the thin films described herein have a thickness of less than 50 μm. In some other examples, the thin films described herein have a thickness of less than 45 μm. In one example[[ID=...]] ​​In some instances, the thin films described herein are less than 35 μm in thickness. The thin films described herein are less than 30 μm in thickness. The thin films described herein are less than 25 μm in thickness. In other examples, the thin films described herein are less than 20 μm thick. In some instances, the thin films described herein have a thickness of less than 15 μm. In some other examples, the thin films described herein have a thickness of less than 5 μm. In certain instances, the thin films described herein are less than 0.5 μm in thickness. In still other instances, the thin films described herein are less than 0.1 μm in thickness.

[0238] In some examples, provided herein are films having a thickness of about 100 nm to about 100 μm. In some instances, the thickness is less than 50 μm. In other instances, the thickness is less than 40 μm. In some instances, the thickness is less than 30 μm. In other instances, the thickness is less than 20 μm. In certain instances, the thickness is less than 10 μm. In other instances, the thickness is less than 5 μm. In some instances, the thickness is less than 1 μm. In yet another example, the thickness is 0.5 μm.

[0239] In some of these examples, the membrane is 1 mm in length. In some others, the membrane is 5 mm in length. The membrane is 10 mm in length. In another example, the membrane is 15 mm in length. In one example, the membrane is 25 mm in length. In another example, the membrane is 30 mm in length. In some instances, the membrane is 35 mm in length. In some other instances, the membrane is In another example, the membrane is 40 mm in length. In another example, the membrane is 45 mm in length. In some instances, the membrane is 50 mm in length. In other instances, the membrane is 30 mm in length. In some instances, the membrane is 55 mm in length. In some other instances, the membrane is 60 mm in length. In yet another embodiment, the membrane is 65 mm in length. In some instances, the membrane is 70 mm in length. In other instances, the membrane is 75 mm in length. In some instances, the membrane is 80 mm in length. In some instances, the membrane is 85 mm in length. In another example, the membrane is 90 mm in length. In yet another example, the membrane is 95 mm in length. In some instances, the membrane is 100 mm in length. In other instances, the membrane is is 30mm.

[0240] In some instances, the membrane is 1 cm in length. In another example, the membrane is 2 cm in length. In another example, the membrane is 3 cm in length. In some instances, the membrane is 4 cm in length. In some instances, the membrane is 5 cm in length. In an example, the membrane is 6 cm in length. In yet another example, the membrane is 7 cm in length. In some other examples, the membrane is 8 cm in length. The membrane is 9 cm long. In another example, the membrane is 10 cm long. In some examples, the membrane is 11 cm in length. In some other examples, the membrane is 12 cm in length. In another example, the membrane is 13 cm in length. In yet another example, the membrane is In some instances, the membrane is 15 cm in length. In one example, the membrane is 16 cm in length. In yet another example, the membrane is 17 cm in length. In some other examples, the membrane is 18 cm in length. In some instances, the membrane is 19 cm in length. In other instances, the membrane is 20 cm in length. In some instances, the membrane is 21 cm in length. In some other instances, the membrane is 22 cm in length. In another example, the membrane is 23 cm in length. In yet another example, the membrane is In some instances, the membrane is 24 cm in length. In other instances, the membrane is 25 cm in length. The membrane is 26 cm in length. In yet another example, the membrane is 27 cm in length. In another example, the membrane is 28 cm in length. In yet another example, the membrane is In some instances, the membrane is 29 cm in length. In other instances, the membrane is 30 cm in length. The membrane is 31 cm in length. In some other instances, the membrane is 32 cm in length. In one example, the membrane is 33 cm in length. In yet another example, the membrane is 34 cm in length. In some instances, the membrane is 35 cm in length. In other instances, the membrane is In yet another example, the membrane is 37 cm in length. In one example, the membrane is 38 cm in length. In yet another example, the membrane is 39 cm in length. In other examples, the membrane is 40 cm in length. In some examples, the membrane is In some other examples, the membrane is 42 cm in length. In one example, the membrane is 43 cm in length. In yet another example, the membrane is 44 cm in length. In some instances, the membrane is 45 cm in length. In other instances, the membrane is In still other examples, the membrane is 47 cm in length. In one example, the membrane is 48 cm in length. In yet another example, the membrane is 49 cm in length. In other instances, the membrane is 50 cm in length. In some instances, the membrane is In some other examples, the membrane is 52 cm in length. In some examples, the membrane is 53 cm in length. In other examples, the membrane is 54 cm in length. In some instances, the membrane is 55 cm in length. In other instances, the membrane is 56 cm in length. In still other examples, the membrane is 57 cm in length. The membrane is 58 cm in length. In yet another example, the membrane is 59 cm in length. In some examples, the membrane is 60 cm in length. In some examples, the membrane is 61 cm in length. In some other examples, the membrane is 62 cm in length. In yet another example, the membrane is 64 cm in length. In an example, the membrane is 65 cm in length. In another example, the membrane is 66 cm in length. In still other instances, the membrane is 67 cm in length. In yet another example, the membrane is 69 cm in length. In some instances, the membrane is 70 cm in length. In some instances, the membrane is 71 cm in length. In some other instances, the membrane is 72 cm in length. In still other examples, the membrane is 74 cm in length. In one example, the membrane is 75 cm in length. In another example, the membrane is 76 cm in length. In other instances, the membrane is 77 cm in length. In some other instances, the membrane is In yet another embodiment, the membrane is 78 cm in length. In some instances, the membrane is 80 cm in length. In some instances, the membrane is 81 cm in length. In some other examples, the membrane is 82 cm in length. In still other examples, the membrane is 84 cm in length. The membrane is 85 cm in length. In another example, the membrane is 86 cm in length. In some instances, the membrane is 87 cm in length. In some other instances, the membrane is 88 cm in length. In yet another embodiment, the membrane is 89 cm in length. In some instances, the membrane is 90 cm in length. In some instances, the membrane is 91 cm in length. In another example, the membrane is 92 cm in length. In another example, the membrane is 93 cm in length. In still other examples, the membrane is 94 cm in length. In some examples, the membrane is In another example, the membrane is 96 cm in length. In some instances, the membrane is 97 cm long. In some other instances, the membrane is 98 cm long. In yet another embodiment, the membrane is 99 cm in length. In some instances, the membrane is 101 cm in length. In one example, the membrane is 102 cm long. In another example, the membrane is 103 cm long. In still other examples, the membrane is 104 cm in length. In some examples, the membrane is In another example, the membrane is 106 cm in length. In some instances, the membrane is 107 cm in length. In some other instances, the membrane is 108 cm in length. In yet another embodiment, the membrane is 109 cm in length. In some instances, the membrane is 110 cm in length. In some instances, the membrane is 111 cm in length. In another example, the membrane is 112 cm in length. In another example, the membrane is 113 cm in length. In still other examples, the membrane is 114 cm in length. The membrane is 115 cm in length. In another example, the membrane is 116 cm in length. In some examples, the membrane is 117 cm in length. In some other examples, the membrane is 1 In yet another embodiment, the membrane is 119 cm in length. The membrane is 120 cm long.

[0241] In some instances, garnet-based films can be used as monoliths useful in lithium secondary battery cells. In some of these cells, the garnet-based film form factor is , about 10cm 2 In one cell, the membrane has an upper surface area of ​​about 100 cm 2 The upper surface area of The shape element of the garnet-based film.

[0242] In some examples, the films described herein have a Young's modulus of about 130-150 GPa. In some other examples, the films described herein have a Vickers hardness of about 5-7 GPa. It has a quality.

[0243] In some instances, the membranes described herein have a porosity of less than 20%. In examples, the membranes described herein have a porosity of less than 10%. In some instances, the membranes described herein have a porosity of less than 5%. The membranes described herein have a porosity of less than 3%.

[0244] (x. Composite materials) For Li secondary battery applications, the energy density depends on the electrolyte, catholyte, and alkali that may be present. The amount of electrolyte, catholyte, or anolyte material used is inversely proportional to the amount of As a given battery capacity is used, more positive electrode active material (e.g., FeF3, CoF2 , NiF2, CoF2) and more anode materials (e.g., Li-metal) can be incorporated into the same capacity. This increases the energy density of the battery, e.g., the energy per unit volume. Thus, in some instances, the thickness may be less than 500 μm but greater than 1 nm. or less than 450 μm but more than 1 nm, or less than 400 μm but more than 1 nm, or is less than 350 μm but more than 1 nm, or less than 300 μm but more than 1 nm, or 250 Less than μm but more than 1 nm, or less than 200 μm but more than 1 nm, or less than 150 μm less than 100 μm but more than 1 nm, or less than 50 μm but more than 1 nm, or less than 45 μm but more than 1 nm, or less than 40 μm but more than 1 nm More than 10 μm, or less than 30 μm but more than 1 nm, or less than 35 μm but more than 1 nm or less than 25 μm but more than 1 nm, or less than 20 μm but more than 1 nm, or Less than 15 μm but more than 1 nm, or less than 10 μm but more than 1 nm, or less than 9 μm but more than 1 nm, or less than 8 μm but more than 1 nm, or less than 7 μm More than 1 nm, or less than 6 μm but more than 1 nm, or less than 5 μm but more than 1 nm or less than 4 μm but more than 1 nm, or less than 3 μm but more than 1 nm, or 2 Less than μm but more than 1 nm, or less than 1 μm but more than 1 nm, or less than 90 nm but more than 1 nm, or less than 85 nm but more than 1 nm, or less than 80 nm but more than 1 nm More than 1 nm, or less than 75 nm μm but more than 1 nm, or less than 70 nm but more than 1 nm or less than 60 nm but more than 1 nm, or less than 55 nm but more than 1 nm, or 50 Less than 1 nm but more than 1 nm, or less than 45 nm but more than 1 nm, or less than 40 nm but more than 1 nm, or less than 35 nm but more than 1 nm, or less than 30 nm but 1 nm or less than 25 nmμm but more than 1 nm, or less than 20 nm but more than 1 nm or less than 15 nm but more than 1 nm, or less than 10 nm but more than 1 nm, or 5 nm less than 1 nm but more than 1 nm, or less than 4 nm but more than 1 nm, or less than 3 nm and producing a film thickness of less than 2 nm but more than 1 nm, or less than 2 nm but more than 1 nm, It is advantageous to use the method described.

[0245] In certain instances, the garnet materials described herein are combined with a polymer. In these examples, the polymers include polyethylene oxide (PEO), polypropylene Polypropylene oxide (PPO), PEO-PPO block copolymer, styrene-butadiene, polystyrene (PS ), acrylate, diacrylate, methyl methacrylate, silicone, acrylamide , t-butylacrylamide, styrenics, t-alpha methylstyrene, acrylonitrile nitrile, and vinyl acetate.

[0246] The present invention relates to a method for preparing a binder (e.g., in a slurry or in a green film) In the examples of the specification, the binder is polypropylene (PP), polyvinyl butyral (PVB) , polyvinylpyrrolidone (PVP), atactic polypropylene (aPP), isotactic (iso active) Polypropylene Ethylene Propylene Rubber (EPR), Ethylene Pentene Copolymer (EP C), polyisobutylene (PIB), ZEON (trademark), styrene butadiene rubber (SBR), polyolefin Polyethylene-co-poly-1-octene (PE-co-PO); PE-co-poly(methylenecyclopentane) ) (PE-co-PMCP); stereoblock polypropylene, polypropylene polymethylpenteneco The polymer may be selected from the group consisting of: a polymer, and a silicone.

[0247] (II. Lithium secondary battery) In some instances, the disclosure herein provides a method for manufacturing a lithium-loaded garnet as described herein. The present invention describes a battery having a catholyte, electrolyte, and / or anolyte, which is composed of a There are.

[0248] (a. Battery structure) In some examples, the batteries described herein may include a current collector substrate coated on both sides. In these examples, the garnet electrolyte contains a positive electrode (e.g., cathode) active material. It may also be applied to or within the cathode active material.

[0249] In some instances, the disclosure herein provides a method for producing a compound according to the invention. The present invention describes a composite electrochemical device comprising: an active electrode material, a lithium the group consisting of: aluminium-filled garnet electrolytes or catholytes, conductive additives, and combinations thereof; In some examples, the device comprises at least one layer comprising a material selected from The material also includes at least one layer containing a garnet-type electrolyte.

[0250] In another embodiment, the present disclosure provides herein an anode and an anode current collector. at least one layer comprising a garnet solid electrolyte (SSE); at least one layer comprising a porous garnet in contact with the SSE; The cot may optionally be made of carbon, lithium conducting polymers, active cathode materials, and combinations thereof. and the porous garnet is permeated with at least one member selected from the group consisting of: at least one layer comprising an aluminum cathode current collector in contact with a cathode electrode, wherein: The porous garnet layer is at least 70% porous by volume; and the garnet is Li A La B M ' c M'' DZr E O F 、Li A La B M' C M'' D Ta E O F 、Li A La B M' C M'' D Nb E O F (where 4 < A < 8.5, 1.5 < B < 4 , 0 ≤ C ≤ 2, 0 ≤ D ≤ 2; 0 ≤ E < 2, 10 < F < 14, and M' and M'' are each, in each case independently selected from Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 < a < 7.7; 2 < b < 4; 0 < c ≤ 2.5; 0 ≤ d < 2; 0 ≤ e < 2, 10 < f < 14, and Me'' is a metal selected from Nb, Ta, V, W, Mo, or Sb) is selected as the material; and the active electrode material is NCA (lithium nickel cobalt aluminum oxide), LMNO (lithium manganese nickel oxide), NMC (lithium nickel manganese cobalt oxide), LCO (lithium cobalt oxide, i.e., LiCoO2), nickel fluoride (NiF x , where x is 0 to 2.5), copper fluoride (CuF y , where y is 0 to 2.5), or FeF z ( where z is selected from 0 to 3.5) is a cathode material selected from, an electrochemical device is described for a layered material. In some examples, 10 < F < 13. In some examples, 0 < c ≤ 2.

[0251] (b) A garnet catholyte, an electrolyte, and a battery component suitable for use with the catholyte. minutes) Suitable current collectors for use with the garnet materials described herein include gold. Metal foils, metal sheets, metal wires, and metal powders, where the metal is aluminum. Aluminum, copper, gold, nickel, cobalt, steel, stainless steel, lithium metal, and alloys thereof , a mixture, or a combination. Provided herein is a lithium alumina doped composite as described in this application. Electrochemical devices with electrolytes composed of filled garnets. In the present application, provided herein is an alumina-doped quartz crystal, as described herein. The present invention relates to an electrochemical device having a catholyte composed of lithium-loaded garnet.

[0252] In some embodiments disclosed herein, the electrode contains a conductive additive that is carbon. In some embodiments, the carbon is selected from the group consisting of Ketjen black, VGCF, acetylene black, and the like. graphite, graphene, nanotubes, nanofibers, and combinations thereof In one embodiment, the carbon is a member selected from the group consisting of ketjen. In some other embodiments, the carbon is VGCF. In another embodiment, the carbon is graphite. In some embodiments, the carbon is graphene. In some embodiments, the carbon is a nanotube. In other embodiments, the carbon is a nanofiber.

[0253] c. Cathode Materials Suitable for Use with the Garnet Materials Described Herein The garnet materials described herein can be used in conjunction with a variety of cathode or positive electrode active materials. In particular, garnets are suitable for use in conversion chemistry cathode activity. Materials, including, but not limited to, electrochemical conversion Nanostructured Materials for Electrochemical Conversion Reactions No. 13 / 922,214, filed May 8, 2014, entitled "CONTENTS"; PROTECTIVE COATINGS FOR CONVERSION MATERI U.S. Nonprovisional Patent Application No. 14 / 272,518, filed July 23, 2014, entitled "AL CATHODES"; In addition, hybrid electrodes (H) containing both intercalation and conversion materials A US provisional patent application entitled "YBRID ELECTRODES WITH BOTH INTERCALATION AND CONVERSION MATERIALS" was filed. Patent Application No. 62 / 027,908; and also, filed on November 26, 2013, for energy storage. Iron Oxyfluoride Electrodes for Energy Storage Provisional Patent Application No. 14 / 090,990; also filed October 25, 2013, entitled "Metals for Self-Forming Batteries" A paper entitled "METAL FLUORIDE COMPOSITIONS FOR SELF-FORMED BATTERIES" was published. Because it is chemically compatible with the active materials described in US Nonprovisional Patent Application No. 14 / 063,966, The contents of these patent applications are not to be construed as limiting the scope of the present invention. , which is incorporated herein by reference in its entirety.

[0254] The garnet materials described herein are compatible with other catholyte and electrolyte materials, e.g. Although not specified, Li, filed on May 15, 2014 A MP B S C (M=Si, Ge, and / or Sn) SOLID STATE CATHOLYTE OR ELECTROLYTE FOR BATT ERY USING Li A MP B S C (M = Si, Ge, and / or Sn)) The present invention is also suitable for use with the catholyte and electrolyte materials described in US Pat. No. 6,499,499.

[0255] Active electrodes suitable for use with the compositions, devices, and methods described herein The material may be, but is not limited to, NCA (lithium nickel cobalt aluminum oxide) oxide), NMC (lithium nickel manganese cobalt oxide), LMNO (lithium manganese nickel Cobalt oxide), LCO (lithium cobalt oxide, i.e., LiCoO2), nickel fluoride (NiFx, where x is 0 to 2.5), copper fluoride (CuF y , where y is 0 to 2.5), or FeF z (here and z is selected from 0 to 3.5. In one embodiment, the active electrode material is In some embodiments, the active cathode electrode material is NCA (Non-Cu-Acetonitrile). In certain other embodiments, the active material is a tungsten-based compound (e.g., tungsten nickel cobalt aluminum oxide). The active cathode electrode material is LMNO (lithium manganese nickel oxide). In embodiments, the active cathode electrode material is LCO (lithium cobalt oxide, i.e., Li In yet another embodiment, the active cathode electrode material is NMC. In certain other embodiments, the active cathode electrode material is nickel fluoride (NiF x , where , x is 0 to 2.5). In some other embodiments, the active cathode electrode material is copper fluoride (CuF y In some other embodiments, the The active cathode electrode material is FeF z (where z is selected from 0 to 3.5).

[0256] III. METHODS OF MAKING THE MATERIALS DETAILED HEREIN (a. Thin film lithium conductive powder material derived from deposition flux) In some examples, described herein are ceramic electrolyte materials (e.g., A process for making battery components including lithium-loaded garnet powders or films, comprising: and forming a ceramic flux on or around the substrate using one or more flux materials having a melting point lower than The process involves mixing, dissolving, and / or densifying the mixture.

[0257] In some instances, the ceramic electrolyte powder material, or components thereof, may be mixed in two or more flash The fluxed powder material is mixed with the fluxed material at a temperature below 400°C to form a fluxed powder material. The fluxed powder material is compacted and reheated at temperatures below 400°C to form a high density lithium conductor. A conductive material is formed.

[0258] The deposition methods described herein are useful for depositing materials such as, but not limited to, garnet, Suitable for lithium filled garnet, perovskite, NASICON and LISICON structures.

[0259] In some examples, the deposition method includes adding a lithium conductive ceramic powder material in a predetermined amount. and density. In some instances, the powder has an average particle size of about 100 nm to 10 μm. In some examples, the powder is characterized by or is ground to an average particle size of The average particle size is 800 nm to 2 μm. In some of these examples, the flux material is provided in a second predetermined amount and density. In some instances, the second provided flux The flux material is less than 51% (w / w) of the first powder material. This flux material is typically heated to about 500°C. It is a lithium-containing material that melts at ~800°C. Additional flux material is provided in the reaction mixture. In some instances, various combinations of powder and flux materials may be used. In some of these examples, the eutectic mixture is In some further examples, the eutectic mixture has a melting point of about 100-50°C. In some instances, the heated mixture is mixed. In examples, the mixture is then heated and formed into, but not limited to, a sheet, thick film (greater than 100 μm thick), , thin film (thickness less than 100 μm), roll, sphere, disk, sheet, pellet, and cylinder After a reaction time and / or further heating, the powder and flux material are In some instances, the flux is dissolved in a solvent, such as, but not limited to, The product formed therein is prepared using water, acetone, ethanol, or a combination thereof. In some instances, further heating may be performed to a temperature below 500°C. This method and its variations produce high density lithium conductive ceramic powders. This often results in a density that is 20% higher than the starting density of the reactants and / or flux. In some instances, the powder and flux material may include formed garnet, e.g. For example, Li7La3Zr2O 12 and oxides such as LiOH, La2O3, and ZrO2. In some instances, the garnet powder may be a garnet precursor, such as, but not limited to, Not limited to, but includes LiOH, L2CO3, La2O3, ZrO2, Nb2O5, Ta2O5, Al nitrate, Al nitrate hydrate, or These combinations are formed by mixing.

[0260] In some examples, the garnet materials described herein can be prepared by adding a garnet precursor For example, but not limited to, LiOH, La2O3, ZrO2, Nb2O5, Ta2O5, Al nitrate, or any of these. The mixture is then heated to 600°C. , 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150 ℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, or 1450℃. In this example, the mixture is heated at 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, or 1100°C. In some examples, the mixture is calcined at 800° C. In some instances, the mixture is calcined at 850°C. In some instances, the mixture is calcined at 900°C. In some examples, the mixture is calcined at 950° C. In some examples, the mixture is calcined at 1 In some examples, the mixture is calcined at 1000°C. In some examples, the mixture is calcined at 1050°C. In some of these examples, the mixture is calcined at 1100°C. The mixture is calcined for 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 hours. The mixture is calcined for 4, 5, 6, 7, or 8 hours. In some instances, the mixture is calcined for 4 hours. In some examples, the mixture is calcined for 5 hours. In some instances, the mixture is calcined for 7 hours. In this case, the calcination temperature is achieved by a heat ramp rate of about 1 C / min or about 5 C / min or about 10 C / min. In some of these examples, the calcined mixture is then crushed to form a mixture agglomerate. In some of these examples, the calcined mixture is then crushed and flattened. In one example, the milled calcined mixture is then heated at 600°C for 6 50℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, Sintering is performed at temperatures of 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or 1450°C. Some examples: In this case, sintering was performed at 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, and 1350°C. , 1400°C, or 1450°C. In some instances, sintering is performed at temperatures of 1000°C, 1200°C, In these examples, sintering is carried out at a temperature of 1, 2, 3, 4, 5, 6, 7 , 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, It lasts for 28, 29, or 30 minutes.

[0261] In some instances, the flux may comprise an inorganic salt, such as lithium, sodium, or potassium. Some examples include ammonium and rubidium salts. For example, LiF, LiCl, LiBr, and / or LiI. In the present invention, the flux contains inorganic oxides such as LiOH and Li2CO3. may also include alkali metal hydroxides, chlorides, nitrates, sulfates, and combinations thereof. Specific combinations that are useful are LiOH, LiCl, LiBr, LiI, LiNO, LiSO, LiO-SiO, LiO -B2O3, Li2O-PbO, Li2O-Bi2O3, NaOH, NaCl, NaNO3, NaSO4, NaBr, Na2CO3, KOH, KCl, K A mixture of any one or more members selected from the group consisting of NO3, KSO4, KBr, and K2CO3 include.

[0262] The flux comprises a eutectic mixture of materials, wherein the eutectic mixture is composed of the constituents of the mixture. For example, a mixture of 0.3 LiOH and 0.7 NaOH has a melting point lower than that of either The mixture melts at around 250° C., which is lower than the melting point of either LiOH or NaOH.

[0263] In some examples, the powder, flux, and reaction mixture are applied to a current collector, a positive electrode, a negative electrode, , or deposited in the electrolyte.

[0264] In some instances, the powders synthesized herein may be dissolved in a flux component. The powder is then mixed with the flux components. The solution is cast onto a plate to form a film having a thickness of about 10 nm to about 250 μm. The casting onto the substrate can be by slot casting, doctor blade casting, or by casting the substrate through a flat This is achieved by dip coating into the paint.

[0265] In some other instances, the compounds described herein are used to prepare a slurry of these components. The resulting powder is mixed with the flux components and also mixed with a liquid or solvent. The mixture is cast onto a substrate to form a film having a thickness of about 10 nm to about 250 μm. In the method, the casting onto the substrate is performed by slot casting, doctor blade casting, or by casting onto the substrate. This is achieved by dipping the solder into the flux. The slurry is then dried. The solvent is removed, and the flux components and powders are optionally melted and mixed. wherein heating is at 1°C / min to about 200°C, or about 250°C, or about 300°C, or about 350°C, A temperature of about 350°C, or about 400°C, or about 450°C, or about 500°C is achieved. In order to completely dissolve the powder in the flux, more In other instances, not all of the powder in the flux is dissolved. To avoid this, more synthetic powder is used than flux.

[0266] In some examples, the positive electrode active material is mixed with garnet powder and also with flux components. The mixture is applied to one, two, or more of the current collectors. The flux can be processed and optionally deposited on the side as described herein. When removed, the intimate mixture of garnet and active material is in direct contact with the current collector. Remain.

[0267] In any of these examples, the substrate, e.g., the current collector, may be a garnet, a garnet precursor, or a by dip-applying a flux having a precursor, an active material, or a combination thereof; The substrate can be coated with a garnet material, optionally including a positive electrode active material. In any of the examples, the substrate, e.g., the current collector, is provided with a garnet, a garnet precursor, an active A flux having a conductive material, a conductive material, or a combination thereof is cast onto the substrate. Garnet materials, optionally including active materials, can be applied. The casting can be doctor blade casting. In these examples, the casting is performed by a slot In these examples, the casting can be dip coating. .

[0268] In some examples, the methods herein include adding one or more lithium conductive ceramic powder materials to a providing a eutectic mixture of the above flux materials; heating the mixture at a temperature of about 400°C to about 800°C. optionally, casting the flux material; and forming a high density lithium conductive gas. In some instances, the formed material includes In some instances, the first flux is at least 20% denser than the precursor. one or more materials selected from H, LiCl, LiBr, LiNO3, LiSO4, or combinations thereof; The second flux is NaOH, NaCl, NaNO3, NaSO3, NaSO4, NaBr, Na2CO3, or a combination thereof. Two flux materials are used, one or more of which are selected from the following: In some examples, the powder material is a lithium-filled garnet. The powder material optionally comprises a perovskite material. In some examples, the powder material comprises: In some instances, the third film may comprise a NASICON, LISICON, or tungsten / bronze material. A lux is provided in this manner and is selected from KOH, KCl, KNO3, KSO4, KBr, and / or K2CO3. It is one or more materials that can be used.

[0269] Further details, examples, and embodiments of these methods for making garnet materials can be found in, for example, , the contents of which are incorporated herein by reference in their entirety for all purposes, 2013 A method and system for forming garnet materials using a sintering process, filed on October 7th, Titled "METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH SINTERING PROCESS" No. 61 / 887,451 filed on Dec. 1, 2002, which is hereby incorporated by reference.

[0270] In some instances, the precursor material is optionally ground and mixed with the flux, as shown in Figure 1. The precursors are mixed together (step a) and heated to dissolve the precursors in the flux (step b). The flux containing the material is cast (step c) and calcined (step d) to react the precursor material and form a more Larger and more crystalline particles are formed (step e), which are then densified with a flux. In some instances, the flux is removed (step f).

[0271] (b. Solutions and Slurries) In some examples, the methods herein involve the preparation of solutions and sprays that are cast or deposited onto a substrate. In some instances, the garnet precursor may be a powder as described herein. In some instances, these precursors are formulated into a slurry. In some instances, these milled precursors are formulated into a slurry. After milling, in some instances, the precursor is mixed with a coating formulation, such as a binder and a solvent. These slurries and formulations, solvent, binder, dispersant, and a surfactant. In some instances, the binder is polyvinyl butyral (PVB). The solvent is toluene and / or ethanol and / or diacetone alcohol. In some instances, PVB is both a binder and a dispersant. As binders, PVB, PVP, ethyl cellulose, cellulose, PVA, and PVDF are also used. In some examples, dispersants include surfactants, fish oil, fluorinated surfactants, Activators include Triton, PVB, and PVP. In some slurries, 10% to 60% by weight The slurry is a solid precursor. The binder and dispersant each contain several In this slurry, the solvent can make up 50% w / w of the slurry, with the remaining weight percentage Includes content.

[0272] In some examples disclosed herein, the slurry contains a conductive additive that is carbon. In some embodiments, the carbon is selected from the group consisting of Ketjen black, VGCF, and acetylene black. , graphite, graphene, nanotubes, nanofibers, etc., and combinations thereof In some embodiments, the carbon is a member selected from the group consisting of: In some other embodiments, the carbon is VGCF. In some embodiments, the carbon is acetylene black. In other embodiments, the carbon is graphite. In some embodiments, the carbon is graphene. The carbon is a nanotube. In another embodiment, the carbon is a nanofiber.

[0273] In some examples, the solvent is toluene, ethanol, toluene:ethanol, or In some embodiments disclosed herein, the binder may be selected from any of these combinations. In some embodiments disclosed herein, the polymer is polyvinyl butyral (PVB). The binder is polypropylene carbonate. In this case, the binder is polymethyl methacrylate.

[0274] In some examples, the solvent is toluene, ethanol, toluene:ethanol, or In some instances, the binder is polyvinyl butyral (PVB In another example, the binder is polypropylene carbonate. In the example, the binder is polymethyl methacrylate.

[0275] In some embodiments disclosed herein, removing the solvent comprises evaporating the solvent. In some of these embodiments, removing the solvent In some embodiments, the removing step comprises heating the film. In yet another embodiment, the removing includes using a vacuum to In yet another embodiment, the removing step comprises heating the film to remove the solvent. , including using a vacuum to drive off the solvent.

[0276] (c. Catholyte) As shown in Figure 25, one method of making embodiments of the invention disclosed herein is to depositing a dense solid separator electrolyte for the node and optionally sintering the electrolyte. In some embodiments, the method includes depositing a porous garnet catholyte; and sintering the catholyte to achieve a porosity of greater than 70%. wherein the method is by a method selected from chemical vapor deposition (CVD), pyrolysis, or related techniques. This also includes filling the porous catholyte with less than 10% by volume of carbon. In this manner, the method includes providing a porous catholyte with an ion-conducting material such as a liquid, gel, or polymer. In some embodiments, the method further comprises filling the conductive flowable material. In some embodiments, the method includes loading the active material with greater than 40% by volume. In some embodiments, the method includes laminating or depositing a cathode current collector. This also includes putting it on.

[0277] In some embodiments, disclosed herein are methods for producing integrated electrochemical devices. 1. A method for manufacturing an anode comprising the steps of: providing an anode layer comprising an anode current collector; providing a garnet-type solid electrolyte (SSE) layer in contact with at least one side of the node layer; optionally, sintering the SSE; providing a porous garnet layer in contact with the SSE layer; and optionally sintering the porous garnet layer; optionally, adding carbon, lithium, or the like to the porous garnet layer. a polymer selected from the group consisting of a conductive polymer, an active cathode material, and combinations thereof; and infiltrating at least one member into the porous garnet layer; and In some examples, these methods include, in any order, providing a dielectric layer. are performed sequentially in the order in which they are listed.

[0278] In some examples, the methods described herein involve the production of garnet-type solid electrolytes (SSEs). on two independent sides of the anode current collector layer.

[0279] In some instances, sintering includes thermal sintering or electric field assisted sintering (FAST). Here, thermal sintering refers to sintering garnet at a temperature in the range of about 800°C to about 1200°C for about 1 to about 600 minutes. and FAST sintering includes heating the garnet to a temperature in the range of about 600°C to about 800°C. This involves heating and applying a DC or AC electric field to the garnet.

[0280] In some instances, infiltrating the porous garnet layer with carbon may be performed by chemical vapor deposition. This includes using chemical vapor deposition (CVD) or pyrolysis.

[0281] In some instances, infiltrating the porous garnet layer with the active material may be performed by vapor / liquid This includes using plasma deposition or electrophoretic deposition.

[0282] In some instances, providing a cathode current collector in contact with the porous garnet layer. The current collector is laminated, electroplated, or vapor-deposited on the porous garnet layer. include.

[0283] In some instances, the porous garnet layer is at least 1000 nm in volume after it is sintered. It is also 70% porous.

[0284] In some instances, the porous garnet layer is characterized by a Li conductivity of 1e-3 S / cm or greater at 60°C. In some examples, the lithium conducting polymer has a Li conductivity of 1e-4 S / cm or greater at 60°C. The materials described herein are characterized by a Li conductivity of 1e-4 S / cm or greater at 60°C. In some examples, the conductivity is a measure of bulk conductivity. In this case, the conductivity is determined by the fact that the conduction occurs within the material but is not affected by the porosity of the material. It is measured as follows.

[0285] In some examples, the porous garnet layer has an average pore diameter size of about 5 nm to about 1 μm. It has holes.

[0286] In some instances, the polymer is stable at voltages greater than about 3.8V.

[0287] In some examples, the porous garnet layer has a melting point of about σ at 60° C. i Conductivity >1e-3S / cm It is a sign.

[0288] In some examples, the porous garnet layer contains more than 40% by volume of active cathode material. In some instances, the porous garnet layer is infiltrated with more than 55% by volume of The active cathode material is infiltrated.

[0289] In some examples, the garnet is stable at a voltage between about 1.3V and about 4.5V.

[0290] In some instances, the garnet may contain Li A La B M' c M'' D Zr E O F , Li A La B M' C M'' D Ta E O F , Li A La B M' C M'' D Nb E O F (where 4 <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2; 0≦E<2、10< F<13, and M' and M'' are each, independently in each occurrence, Al, Mo, W, Nb, Sb, Ca, Ba, Sr , Ce, Hf, Rb, or Ta), or Li a La b Zr c Al d Me'' e O f (where 5 <a<7 .7; 2 <b<4; 0<c≦2.5; 0≦d<2; 0≦e<2、10<f<13であり、Me''は、Nb、Ta、V、W , Mo, or Sb).

[0291] In some instances, the active electrode material is NCA (lithium nickel cobalt aluminum Lithium manganese nickel oxide), LMNO (lithium manganese nickel oxide), LCO (lithium cobalt oxide), LiCoO2), NMC, nickel fluoride (NiF x , where x is 0 to 2.5), copper fluoride (Cu F y , where y is 0 to 2.5), or FeF z (where z is selected from 0 to 3.5) It is a cathode material that is used.

[0292] In some instances, disclosed herein are methods for producing a medicament for the treatment of a cancer, comprising: It is an electrochemical device manufactured using

[0293] As shown in Figures 27 and 29, the method herein involves dissolving electrolyte particles prior to sintering. The present study describes a process for fabricating composite electrodes for solid-state batteries consisting of active electrode materials interspersed with nanoparticles. In some embodiments, the layer contains a conductive additive (e.g., carbon). You can also do this.

[0294] As shown in Figure 31, the electrolyte and electrode materials have improved interfacial contact after sintering. In some embodiments, the free-standing bilayer or trilayer described herein comprises: The Li-garnet interface in these examples is They also have a low area specific resistance (ASR). In some examples, the ASR is 5 ohm cm at 80°C. 2 Not yet In some examples, the ASR is less than 100 ohm cm at 80°C. 2 Less than some In the example, the ASR is approximately 1 ohm cm at 80°C. 2 In some examples, ASR is 6 ohm cm 2 is less than.

[0295] In some embodiments, Li is added to the sintered garnet film (free-standing bilayer or trilayer). It is deposited or laminated and has a low ASR. In some examples, the ASR is 5 ohm cm at 80°C. 2 In some examples, the ASR is less than 100 ohm cm at 80°C. 2 Less than. In this example, the ASR is approximately 1 ohm cm at 80°C. 2 In some examples, the ASR is 6 ohms cm 2 is less than.

[0296] As shown in Figures 15, 16, 17, 20, 21, and 28, a setter plate is used. In some instances, AC current can be applied, and in some other instances, DC current. A power supply can be used to sinter the particles.

[0297] As shown in FIG. 4, an electrochemical device is fabricated by the sintering method described herein. In FIG. 4, for example, electrolyte powder, catholyte particles (e.g., garnet tocasolite), and active electrode particles (e.g., cathode active particles) are layered and mixed, and the It can then be sintered according to the novel methods described herein.

[0298] In some examples, the films described herein are prepared using an organic binder-solvent system (e.g., Powder ceramic component(s) using polyvinyl butyral in toluene:ethanol ( For example, electrolyte: lithium-filled garnet, lithium lanthanum, zirconium oxide; electrodes: By producing a slurry of lithium-nickel-manganese-cobalt oxide, In some examples of composite electrodes, In addition to the electrolyte and active electrode materials, conductive additives such as carbon black are added. This can also increase the electrical conductivity of the final product. It can be cast as a thin layer of any thickness and the solvent is allowed to evaporate, leaving behind a flexible film. This membrane is easy to handle and can be applied with low pressure (<1000 psi) at moderate temperatures (80°C). For example, Li conductive garnet can be stacked on other such layers by Green composite thin films of lithium electrolyte and high voltage cathode material (NMC) are shown in Figure 27. There are.

[0299] Some of the example methods described herein involve thermal sintering.

[0300] In some instances, after a binder burnout step to remove the binder (e.g., PVB), 27, the composite electrode, for example, the composite electrode shown in FIG. 27, is heated to a high temperature (for example, 800 to 1200°C), Holding for a period of time (1-600 min) induces sintering of the particles, forming a much higher density matrix. In some of these examples, the bonds between the individual components can be The grains fuse together, significantly increasing their contact area, as shown, for example, in FIG. In some instances, it may be advantageous to use finely divided powders, particularly for the electrolyte components. This is because it increases the sintering reaction rate and allows densification at lower temperatures. To maintain the flatness of the thin film under this process, the film is covered with porous zirconia. The membrane can be sandwiched between an inert setter plate such as a nickel plate. This helps to maintain the membrane in a layered form. Not only does it maintain the binder, but it also provides a route for the release of binder decomposition products. The microstructure of the sintered electrode composite material is shown in, for example, FIGS. 30 and 31.

[0301] Some of the example methods described herein involve electric field assisted sintering (i.e., FAST) sintering. This includes concluding.

[0302] One disadvantage of the traditional sintering process is that it operates at high temperatures where several detrimental phenomena can occur. For example, lithium is a highly volatile species and requires a long dwell time. , evaporates from the solid electrolyte material, thereby reducing its ionic conductivity and creating a highly resistive surface. This can induce a plane depletion layer or even cause the material to decompose. Once fused, the electrolyte and electrode components continue to interact, and they The components can interdiffuse to such an extent that their electrochemical properties are lost, i.e., the electrolyte loses its ionic The electrode may lose its conductivity or its ability to store active ions (e.g., lithium). Therefore, to overcome all these problems, the sintering process In some instances, this can be achieved using electric field assisted sintering. This is achieved through

[0303] 16, 17, 18, 19, 20, 21, and 22 show the conventional sintering process disclosed herein. Lower temperatures (for example, 600 to 800°C or less) than the process (up to 1100°C) or (400 to 1000°C) 1 shows a schematic diagram of the setup for FAST sintering of an electrolyte membrane at 1000 K (°C). The membrane is then bonded to two conductive metal plates. Place the plate between the plates and heat in an oven at a moderate temperature (800°C) where lithium evaporation is not significant. An electric field is then applied to the sample to induce FAST sintering. In some instances, the ionic species may not disperse significantly under the stimulus. AC electric fields are advantageous because their frequencies can be chosen high enough to avoid separation. The power supply to the sample must be controlled to avoid excessive Joule heating of the material. In some instances, this is initially operated in a constant voltage amplitude mode, allowing sintering to begin and the sample This can be achieved by switching to a constant current when the impedance of the Sintering of the electrolyte membrane to full density in a much shorter time and at a lower temperature than conventional processes It can be sintered at

[0304] In some instances, FAST sintering also overcomes the problem of interdiffusion in composite electrode layers. Figure 29 shows a schematic diagram of the layout of a complete solid-state battery configuration under FAST sintering. Before sintering, the electrolyte The advantage of the FAST sintering process is that the voltage drop (i.e., the electric field) is preferentially compared to high impedance areas, which are always poorly contacted areas (i.e., non-calcined areas). Therefore, when two types of particles are sintered together, the contact between the constituent particles The contact improves and the resistance drops. As a result, the electric field distribution moves to the adjacent unsintered particles. In this way, the driving force for sintering is transferred from the grains that have already fused together to the grains that have already fused together. Interdiffusion is limited.

[0305] These sintering methods have the advantages of fast sintering times, limited interdiffusion between components in the composite electrode, and Furthermore, the ability to prepare a complete solid-state battery configuration allows for solid-state batteries and and its components.

[0306] d. Doped Compositions In some examples, provided herein are aluminum-doped lithium A method for making ammonium-filled garnets comprising providing garnet precursors in a predetermined combination. In some examples, the method includes incubating the combination for 5 to 10 hours. In another example, the method further comprises grinding the combination in a vessel at about 500° C. The method further includes calcining the mixture at about 1200°C for about 4 to about 10 hours to form garnet. In an example, the method comprises: 50 Grind until particle size is 200-400nm In still another example, the method further comprises: Some of these examples further include mixing the binder with the cellulose acetate solution to form a slurry. In some cases, before sintering the slurry, the method includes casting the slurry as a film. In another example, the method includes providing a green film by: In still other examples, the method optionally further comprises filtering the filtered slurry. In some of these examples, the method further includes providing a pellet of the Before sintering the slurry, the method includes forming a green film by casting the slurry. In still another example, the method includes sintering the filtered slurry. In an example of sintering the slurry, the sintering may further include a setting press. applying pressure to the slurry using a gas turbine; heating the slurry under flowing inert gas at 140°C; Heating at 400°C for about 1 to about 6 hours, and then thermal sintering or electric field assisted sintering for about 10 minutes to about 10 hours. This includes:

[0307] In one example, the garnet precursor is prepared from LiOH, La2O3, ZrO2, and Al(NO3)3.9H2O. be selected.

[0308] In some examples, the garnet precursor is calcined in a vessel at 900° C. for 6 hours. In an example, the vessel is an alumina (ie, Al2O3) vessel.

[0309] In certain instances, crushing the formed garnet may include crushing the formed garnet. d 50 In some other instances, the formed garnet is pulverized. The crushing process is carried out to remove the d of the formed garnet. 50 This is continued until the particle size reaches approximately 100 nm. In some instances, crushing the formed garnet reduces the d5 In some cases, the formed garnet is crushed until the particle size is about 200 nm. This means that the d of the formed garnet 50 This is continued until the particle size reaches approximately 250 nm. The crushing of the formed garnet reduces the d of the formed garnet. 50 Particle size is approximately 350 In some instances, grinding the garnet is performed until the formed garnet is -Net's d 50 This is continued until the particle size reaches about 400 nm.

[0310] In some instances, the crushed formed garnet is mixed with a binder to form a slurry. In some examples, the binder is about 4% w / w. is polyvinyl butyral.

[0311] In some instances, filtering the slurry includes filtering using an 80 mesh sieve. This includes:

[0312] In some instances, providing pellets of the filtered slurry includes pellets having a diameter of 13 mm. In some examples, the pellet has a diameter of 10 mm, It has a diameter of 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm.

[0313] In some instances, applying pressure to the slurry using a setting plate , including applying a pressure of 3 metric tons. Applying pressure to the slurry using a plate is equivalent to applying 2 metric tons of pressure. In some instances, pressure is applied to the slurry using a setting plate. In some instances, setting involves applying a pressure of 1 metric ton. Pressurizing the slurry with plates exerts a pressure of 3.5 metric tons. Includes:

[0314] In some examples, the setter plate is a Pt setter plate. In one example, the setter plate is a garnet setter plate. In yet another example, the setter plate is a porous setter plate. In yet another example, the setter plate is a porous garnet setter plate. The plate is a porous zirconia setter plate.

[0315] In some examples, the method includes using a flow rate of 315 sccm of argon gas. Contains inert gas.

[0316] In some examples, the methods described herein involve treating the slurry under flowing inert gas. This involved heating at 160°C and 330°C for two hours (hr), respectively, under a humidified argon flow. Includes various dwells.

[0317] (e. Microcrystalline lithium-filled garnet) In some examples, provided herein are alumina-doped lithium A method for producing thin films using fine grains of filled garnet. To create these fine grains, the films described herein are heated to a maximum temperature of 1150°C. In some instances, to create these microcrystalline grains, the methods described herein are used. The resulting film is thermally sintered at a maximum temperature of 1150°C for a period of 6 hours or less. To create these fine grains, the films described herein are thermally sintered at a maximum temperature of 1075°C. In some instances, the methods described herein are used to create these fine grains. The resulting film is thermally sintered at a maximum temperature of 1075°C for a period of up to 6 hours. In one example, the film is sintered for 15 minutes. If only sintering is performed, a maximum thermal sintering temperature of 1200°C is used.

[0318] As the temperature increases, the grains grow larger. As the growth increases, the dwell time at that temperature also increases. The method described in the above involves thermal sintering at a temperature of less than 1200°C, or less than 1150°C, or less than 1075°C. In some of these instances, the methods described herein include In some instances, the method described herein includes thermally sintering the mixture at a temperature of 100° C. for a period of 6 hours or less. The described method includes heat sintering for a period of 15 minutes or less. In some other examples, the methods described herein include thermal sintering at 1050°C. In some other examples, the method described herein involves thermal sintering at 1000°C. In some other cases, the method described herein involves thermal sintering at 950°C. In some examples, the methods described herein involve thermal sintering at 900°C. In another example, the methods described herein include thermal sintering at 850°C. In some other examples, the methods described herein include thermal sintering at 800°C. In some other examples, the methods described herein include thermal sintering at 750°C. In some other examples, the methods described herein include thermal sintering at 700°C. In some other examples, the methods described herein include thermal sintering at 650° C. In some other examples, the methods described herein include thermal sintering at 600°C. In some other examples, the methods described herein include heating at 550° C. In some other examples, the methods described herein include sintering at 500° C. In some other examples, the methods described herein include thermally sintering at 45 In some other examples, the methods described herein include thermal sintering at 0° C. In some other examples, the methods described herein include thermal sintering at 400°C. The method includes thermal sintering at 350° C. In some other examples, the methods described herein The method includes thermal sintering at 300° C. In some other examples, the method described herein The method described herein includes thermal sintering at 250° C. The method described involves thermal sintering at 200° C. In some other examples, The method described in the document involves thermal sintering at 150°C.

[0319] In some instances, the lower amount of Li in the lithium-filled garnet is This results in fewer grains in the films described.

[0320] (f. Casting) In some examples, the slurries described herein are applied by slot die coating, slot Casting, doctor blade casting, mold casting, roll coating, gravure, microgravure a. Using casting techniques, including screen printing, flexography, and / or other related methods; Deposited on a substrate.

[0321] Another casting method is to cast garnet materials using a sintering process, which was filed on October 7, 2013. METHOD AND SYSTEM FOR FORMING GARNET MATERIALS WITH U.S. Provisional Patent Application No. 61 / 887,451, entitled "SINTERING PROCESS," filed January 13, 2014; U.S. Provisional Patent Application entitled "GARNET THIN FILM ELECTROLYTE" filed No. 61 / 926,910, filed June 4, 2014, and a patent application filed June 4, 2014, which discloses a method for forming garnet materials by reaction sintering. METHODS AND SYSTEMS FOR FORMING GARNET MATERIAL WITH RE No. 62 / 007,417, filed July 18, 2014, entitled "ACTIVE SINTERING" Fine-grained lithium-ion conductive thin film garnet ceramics U.S. Provisional Patent Application No. 62 / 026,271 entitled "Ium-Ion Conducting Thin Film Garnet Ceramics" No. 2014 / 07 / 18, and Garnet Catholyte and Solid-State Electrochemical Devices filed on July 18, 2014. GARNET CATHOLYTE AND SINTERING OF SOLID STATE ELECTROCHEMICAL D This is described in U.S. Provisional Patent Application No. 62 / 026,440, entitled "Devices and Components." Each of these provisional patent applications is incorporated herein by reference in its entirety for all purposes. can be.

[0322] (g. Sintering method) The specific solid ionic conductor was compressed into a small pellet approximately 10 mm in diameter and 2 mm thick. Although thin films of garnet-based materials can be sintered by conventional processes, Known methods for fabricating membranes for battery applications require membrane lateral dimensions of approximately 10 cm and thicknesses of 100 nm to 50 μm. is insufficient.

[0323] Applying current and voltage can be used to form thin films, particularly garnets (e.g., lithium-filled garnets). It is inherently difficult to sinter films containing ZnO (ZnO-based nanowires). Resistive heating occurs within the net material as it flows through it, thereby producing a sintering effect. Related: For example, sintering garnets using electricity, as is done in FAST sintering. When this occurs, the electricity resistively heats and sinters the garnet material, which is where the impedance becomes maximum. As the garnet sinters and its impedance decreases, the current passing through the garnet The resistance heat associated with the garnet material also decreases. So, the current will mainly follow the path of least resistance (i.e. the path with the smallest impedance) This avoids resistive heating of the unsintered part of the garnet, which has a significantly higher impedance. As more garnet sinters and the impedance decreases, the remaining garnet It becomes more difficult to sinter the green part, and the impedance is at its highest. This is particularly difficult due to the garnet portion having the lowest impedance.

[0324] To overcome this difficulty, cylindrical shaped elements, such as those shown in FIG. Some people transfer an applied current between spaced electrodes at the extreme longitudinal ends of a cylinder. By doing so, these people overcome the aforementioned difficulties because the electric current However, in this specification and in this patent application For some of the applications considered for this, thin film form factors are required. In some instances, this form element is rectangular in shape. In the example, the form element is rectangular in shape. The rectangular and rectangular shaped elements are difficult to sinter, in part because the electrodes through which the current is applied For thin films, the applied current is: Through the z-direction of the membrane, which is one of the shorter paths through the bulk of the material.

[0325] In addition to the difficulties mentioned above, for many applications, thin films must be primarily Densification in the z-direction is preferred (as shown in Figure 23), because shrinkage of the membrane occurs primarily in the z-direction. This means that the density is greater than that occurring in either the x- or y-direction. Achieving densification and shrinkage is also a challenge addressed by the present application. Several sintering methods are described that overcome these and other sintering difficulties.

[0326] As shown in FIG. 24 or FIG. 45, an exemplary sintering method is to apply current through the film in the z-direction. In this manner, FAST sintering involves placing an electrode on a thin film element. It is utilized according to the sintering method described.

[0327] Another exemplary sintering method involves the use of sintering plates, as shown in FIG. In some examples, the applied current passes through the sintering plate. During the passage through the sintering plate, pressure is applied in accordance with the pressure values ​​listed herein and above in this application. In some other instances, the setter plate is , independently, apply pressure according to the pressure values ​​listed herein and above in this application. In another example, one or more metal foil layers are interposed between the setter plate and the thin film to apply pressure. Electric current is applied to the inserted metal foil. Figure 20 shows the metal foil is connected to the sintered membrane and the setter plate. 10 shows an example in which the .lambda.

[0328] In some instances, the metal powder is a garnet film to be sintered with the setter plate. In some of these examples, as the garnet film is sintered, As the metal powder is sintered and bonded to the film during sintering, Figure 21 shows the metal powder bonding to the sintered film and setter. The example shown is arranged between two plates.

[0329] In some of these examples, the setter plate is a porous setter plate. In some of these examples, the setter plate is a garnet-based setter. In some of these examples, the setter plate is a perforated In some of these examples, the setter A garnet plate is a metal setter plate. The garnet-based setter plate may include a setter plate comprising the garnet material described herein. Examples include:

[0330] As shown in FIG. 17, in some instances, the sintering and optionally the application of pressure The plates used for this purpose are positioned so that the applied current is directed to specific locations on the film being sintered. It can have individually addressable contact points. As shown in Figure 17, multiple trapezoids The tapered ends of the profile (100) represent these individually addressable contact points. As used herein, individually addressable means controllably addressable to separate contact points. A controllable and individual current or voltage is applied to one contact point, which may be different from the applied current or voltage. This refers to the ability to apply

[0331] In some instances, a preform used for sintering and optionally applying pressure The port may have a grid structure. In some examples, this grid structure The sintering process is carried out in such a way that it can be placed on the sintering film at various positions during the sintering process. It is movable.

[0332] In some instances, the thin film feature may be formed by calendering the thin film feature as shown in FIG. In these examples, the calender rollers are sintered as they move through the calender. Apply pressure according to the pressure value specified in the manual, and apply the current or The large non-circular electrodes in FIG. 18, parallel to the x-direction of the membrane, also provide a conduit for the applied voltage. The arrows on either side indicate the direction of movement of the film as it moves through the calender rollers during sintering. are.

[0333] As shown in Figure 19, thin film features are sintered while moving through the calender rollers. In some of these, the calender rollers apply current or voltage at various positions during sintering. Individually addressable contacts can be applied to the membranes in a controllable and individual manner. It has contact points (200).

[0334] As shown in Figure 19, thin film features are sintered while moving through the calender rollers. In some of the above, one of the calender rollers is a ground electrode.

[0335] As shown in Figure 22, an example in which thin film features are sintered while moving through a calender roller. In some of these, one of the calender rollers rotates about its longitudinal axis, The spiral design allows the device to move parallel to the longitudinal axis of the print. An applied current or voltage can be directed to the film during sintering.

[0336] (i. Reaction Sintering) In some examples, described herein are reactive sintering processes. In these examples, the garnet precursors are mixed to form a mixture. Precursors include the garnet precursors described in this patent application. In some examples, the mixture is milled according to the milling method described in this patent application. In this example, the mixture is formulated as a slurry of milled precursor materials, and the slurry is In some instances, the slurry is then applied to, but not limited to, a doctor It is applied onto the substrate by methods such as blade casting, slot casting, or dip coating. In some other examples, the slurry is applied to a substrate according to the casting methods described in this patent application. In some of these examples, the slurry is then dried to In some instances, the dried slurry is then cooled to remove the solvent or liquid therein. In some further examples, the dried slurry is applied to other layers of the battery components. In some of these examples, pressure is applied to bond or adhere the laminated layers together. In some instances, the dried slurry layer under pressure is bonded to the surface of the substrate as described herein. Sintering is carried out according to the method described in the present application. In the example carried out using garnet precursors, sintering is carried out by chemical reaction of the garnet precursors. occurs simultaneously, resulting in the formation of sintered garnet.

[0337] In some instances, reaction sintering converts a garnet precursor into a preformed garnet. powder and sintering the mixture using temperature and / or applied current. In some instances, the ratio of garnet precursor to garnet powder is 10:90. In some instances, the ratio of garnet precursor to garnet powder is 20:80. In some instances, the ratio of garnet precursor to garnet powder is 25:75. In some instances, the ratio of garnet precursor to garnet powder is 50:50. In some examples, the ratio of garnet precursor to garnet powder is 60:40. In some examples, the ratio of garnet precursor to garnet powder is 70:30. In this example, the ratio of garnet precursor to garnet powder is 75:25. In some examples, the ratio of garnet precursor to garnet powder is 80:20. In the above, the ratio of garnet precursor to garnet powder is 90:10.

[0338] (ii. Tape Casting) In some examples, described herein are methods for tape casting to produce thin films. In these processes, ceramic powder is mixed with a dissolved binder and optionally a granular material. The powder is dispersed in a liquid or solvent containing the powder to form a homogeneous mixture. The thick mixture or "slip" is cast onto a substrate using a doctor blade casting method. In some examples, the substrate may be a coated substrate such as, but not limited to, silicone coated MYLAR. The liquid or solvent is then evaporated to form a dry "green film." In some instances, the green film is peeled from the MYLAR and formed into a specific shape, e.g. For example, cut into square, rectangular, circular or oval shapes. In this method, the thickness of the slices can be reduced to 0.1 to 200 μm. A metal powder is optionally incorporated into the membrane or adhered to one side of the membrane. In these examples, the metal powders may be Ni, Cu, Ni-garnet mixtures, C In some examples, the ZnO-based garnet is selected from the group consisting of ZnO, ... Tape casting involves the use of openings of about 1 to 100 μm through which tape is cast during deposition. The extension will be carried out.

[0339] (iii. Hot pressing) In some examples, described herein are methods for fabricating thin garnet films. In these examples, the green tape is processed as shown in Figure 4. In some cases, the binder is first removed and then sintered. In these particular examples, the binder is heated to a temperature of about 200, 300, 400, 500, or 600°C. The binder can be removed by burning at high temperatures. The film is heated to a sintering temperature of about 800°C to about 1200°C under a uniaxial loading pressure of about 10 to about 100 MPa. In these examples, the applied pressure is such that the film does not deform or warp during sintering. Further advantages are obtained for preventing sintering in the direction perpendicular to the membrane surface and for producing high density membranes. Provides driving force.

[0340] In some instances, green films are prepared by first casting the film onto a metal foil. In some instances, sintering is performed after the binder is burned out. In some of these examples, sintering involves attaching the film to one of the metal foil substrates under pressure. This involves heating to a temperature below the melting point of the metal or metals. When using a Cu-substrate, a higher sintering temperature can be used compared to when using a Cu-substrate. can.

[0341] (iv. Constrained Sintering) In some instances, the green film can be formed by placing it between setter plates. Although sintering can be achieved by applying a small amount of pressure, it is possible to constrain the membrane and initiate the sintering process. These examples can prevent inhomogeneities that stress the membrane and cause it to warp during the process. In some of the above, the setter plate is porous, e.g., porous yttria. It is beneficial to fabricate stabilized zirconia. The binder allows the binder to diffuse out of the film during the burnout or sintering process. In some cases, burnout and sintering processes are performed in part to remove these porous setter plates. In some instances, a slight amount of pressure can be applied to the sintering process. During the sintering process, a pressure plate is placed on the green film without any further external pressure. In some cases, the pressure exerted by the weight of the setter plate is The constrained sintering is carried out substantially as shown in FIG. 4 and / or FIG.

[0342] (v. vacuum sintering) In some instances, sintering is carried out as described above, but during sintering in a vacuum chamber. In this example, a vacuum is applied to trap the particles within the ceramic during sintering. In some of these cases, trapped gases are expelled from the ceramic. The trapped gases create pore spaces that can prevent sintering ceramics from densifying beyond a certain point. The pressure inside the ceramic prevents further sintering. The trapped gas is removed by sintering the pores that contained the gas and removing the trapped gas from the vacuum system. to densify more than would be possible if the trapped gas had not been expelled. can be done.

[0343] (vi. Electric Field Assisted Sintering, FLASH Sintering, and FAST Sintering) Electric field assisted sintering technology (FAST) sintering can enhance the sintering reaction rate. This causes the electrons, holes, and / or ions in the sintered material to move, which subsequently The material is heated by Joule heating. The heating occurs at the point of maximum resistance (P=I 2 R, where I is the current and R is the resistance). This point is located at the particle-particle neck. These are the very points where sintering is desired, so FAST sintering is particularly effective. Standard garnet sintering procedures are, in some instances, 1050-1200°C. In contrast, FAST sintering of garnet can take 6-36 hours at 600°C and less than 5 minutes. It can be carried out. The advantages are lower-cost processing (higher throughput), lower reactivity ( at lower temperatures, garnet is less likely to react with other components), and less lithium loss (lithium evaporation is a major failure mode that hinders effective sintering). FAST sintering of garnet is most effective at low current and short time [inserted data]. Since garnet materials have high ionic conductivity, a low current is preferred, similar to AC current, so that bulk transport of ions does not occur. The parameters are: 1 minute < time < 1 hour, 500 < temperature < 1050 °C, 1 Hz < frequency < 1 MHz, 1 V < VAC rms < 20 V. In some examples, FAST sintering is combined with hot pressing that includes uniaxially pressing the film during sintering. In some examples, FAST sintering is combined with hot pressing onto a permanent substrate, such as a metal, such as a current collector. In some examples, FAST sintering is combined with constrained sintering that fixes or physically constrains the film without applying a significant amount of pressure. In some examples, FAST sintering is combined with bilayer sintering (and trilayer sintering, such as electrolyte-metal-electrolyte) to provide mechanical support and simultaneously form the current collector in one step. In some

[0344] examples, what is disclosed herein is a method of fabricating a thin film, the method including providing an unsintered thin film; where the unsintered thin film comprises at least one member selected from the group consisting of garnet-type electrolytes, active electrode materials, conductive additives, solvents, binders, and combinations thereof. In Further comprising removing the solvent, if present in the green thin film. The method optionally includes laminating a film to the surface. In some examples, the method includes: and removing the binder, if present in the film. includes sintering the film, wherein the sintering is performed by thermal sintering or electric field assisted sintering (FAST). In some of these examples, the thermal sintering includes sintering the film for about 70 In the range of 0°C to about 1200°C, for about 1 to about 600 minutes, and * 10 -1 ~1 * 10 -15 The partial pressure of oxygen in the atmosphere range In another example, the FAST sintering step involves heating the film in an atmosphere having a temperature of about 500°C. This involves heating the thin film in the range of 100°C to about 900°C and applying a DC or AC electric field to the thin film.

[0345] In some embodiments, disclosed herein is a method of making a membrane, providing a green thin film; wherein the green thin film is a garnet The electrolyte, active electrode (e.g., cathode) material, conductive additives, solvents, binders, and In some examples, the composition includes at least one member selected from the group consisting of: In some cases, the method further comprises removing the solvent, if present in the green thin film. In some examples, the method optionally includes laminating a film to the surface. In some embodiments, the method includes removing the binder, if present in the film. wherein the method includes sintering the film, wherein sintering includes thermal sintering. In some of these examples, thermal sintering includes sintering the film at temperatures between about 700°C and In the range of about 1200°C, for about 1 to about 600 minutes, and * 10 -1 ~1 * 10 -15 It has an oxygen partial pressure in the atmospheric range. This includes heating in an atmosphere containing

[0346] In some embodiments, disclosed herein is a method of making a membrane, providing a green thin film; wherein the green thin film is a garnet The electrode material comprises a conductive electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and a combination thereof. In some examples, the method includes at least one member selected from the group consisting of: Further comprising removing the solvent, if present in the sintered thin film. The method optionally includes laminating a film to the surface. In some examples, the method includes laminating a film In some instances, the method includes removing the binder, if present in the composition. sintering the film, wherein the sintering comprises electric field assisted sintering (FAST). In some of these examples, FAST sintering is performed by sintering the film at temperatures ranging from about 500°C to about 900°C. It involves heating and applying a DC or AC electric field to the thin film.

[0347] In any of the methods described herein, the green thin film is a lithium-loaded garnet. In any of the methods described herein, The green thin film may include an alumina-doped lithium-loaded garnet electrolyte.

[0348] In any of the methods described herein, the thermal sintering may involve heating the film to a temperature of about 400°C to about 1200°C; or about 500°C to about 1200°C; or about 900°C to about 1200°C; or about 1000°C to about 1200°C; or This may include heating in the range of about 1100°C to about 1200°C.

[0349] In any of the methods described herein, the method includes heating the film for about 1 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about 20 In any of the methods described herein, the method may include heating for about 600 minutes. The method may include heating the film for about 30 to about 600 minutes. In either case, the method may include heating the film for about 40 to about 600 minutes. In any of the methods described above, the method includes heating the film for about 50 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about 60 to about 600 In any of the methods described herein, the method may include heating for 1 minute. Any of the methods described herein may include heating the film for about 70 to about 600 minutes. In the method, the method may include heating the film for about 80 to about 600 minutes. In any of the methods described above, the method may include heating the film for about 90 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 100 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about In any of the methods described herein, the method may include heating for 120 to about 600 minutes. The method may include heating the film for about 140 to about 600 minutes. In any of the above, the method may include heating the membrane for about 160 to about 600 minutes. In any of the methods described in the document, the method comprises heating the membrane for about 180 to about 600 minutes. In any of the methods described herein, the method may include filtering the membrane for about 200 to about 6 In any of the methods described herein, the method may include heating for 0.5 minutes. Any of the methods described herein may include heating the film for about 300 to about 600 minutes. In the method, the film may be heated for about 350 to about 600 minutes. In any of the methods described above, the method may include heating the film for about 400 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 450 to about 600 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating for about 500 to about 600 minutes. The method may include heating the film for about 1 to about 500 minutes. In any of the above, the method may include heating the film for about 1 to about 400 minutes. In any of the methods described above, the method includes heating the film for about 1 to about 300 minutes. In any of the methods described herein, the method may include heating the membrane for about 1 to about 200 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating the mixture for about 1 to about 100 minutes. The method may include heating the membrane for about 1 to about 50 minutes.

[0350] In any of the methods described herein, FAST sintering the film can be performed at temperatures between about 400°C and This may involve heating in the range of about 1200° C. and applying a DC or AC electric field to the thin film. In some instances, FAST sintering involves heating the film in the range of about 400°C to about 900°C. and applying a DC or AC electric field to the thin film. The method involves heating the film in the range of about 600°C to about 1150°C and applying a DC or AC electric field to the thin film. In some examples, FAST sintering involves applying a temperature of about 700°C to about 9 This involves heating the thin film in the range of 00°C and applying a DC or AC electric field to the thin film. In this example, FAST sintering involves heating the film in the range of about 800°C to about 900°C and In some instances, fast sintering involves applying a DC or AC electric field to the film. The method involves heating the film in the range of about 500°C to about 800°C and applying a DC or AC electric field to the thin film. In some examples, FAST sintering includes sintering the film at a temperature in the range of about 500°C to about 700°C. These include heating the thin film with a high temperature and applying a DC or AC electric field to the thin film. Therefore, FAST sintering involves heating the film in the range of about 500℃ to about 600℃ and applying DC or involves applying an AC electric field.

[0351] In any of the methods described herein, FAST sintering the film can be performed at temperatures between about 400°C and This may involve heating in the range of about 1000°C and applying a DC electric field to the thin film. In this example, FAST sintering involves heating the film in the range of about 600°C to about 900°C and In some instances, FAST sintering involves applying a DC electric field to the film. This involves heating the thin film to a temperature in the range of about 600°C to about 900°C and applying a DC electric field to the thin film. In some examples, FAST sintering involves heating the film in the range of about 700°C to about 900°C and and applying a DC electric field to the thin film. In some examples, FAST sintering includes: This involves heating the film in the range of about 800°C to about 900°C and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film in the range of about 500°C to about 800°C. and applying a DC electric field to the thin film. In some instances, FAST sintering The method involves heating the film in the range of about 500°C to about 700°C and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500°C to about 600°C. This involves applying a DC electric field to the thin film.

[0352] In any of the methods described herein, FAST sintering the film can be performed at temperatures between about 400°C and This may include heating in the range of about 1000° C. and applying an AC electric field to the thin film. In any of the methods described above, the FAST sintering may be performed by sintering the film at a temperature in the range of about 500°C to about 900°C. This may include heating the thin film in a heated atmosphere and applying an AC electric field to the thin film. FAST sintering involves heating the film in the range of about 600°C to about 900°C and applying an AC electric field to the thin film. In some examples, FAST sintering involves applying a temperature of about 700°C to about 9 In some examples, this involves heating the thin film in the range of 0 to 100°C and applying an AC electric field to the thin film. In this case, FAST sintering involves heating the film in the range of about 800°C to about 900°C and applying AC In some examples, FAST sintering involves applying an electric field to the film at about 500°C. Some of these include heating the thin film to temperatures in the range of 1000 to 800°C and applying an AC electric field to the thin film. In an example, FAST sintering involves heating the film in the range of about 500°C to about 700°C and In some instances, FAST sintering involves applying an AC electric field to the film. This involves heating in the range of 500°C to about 600°C and applying an AC electric field to the thin film.

[0353] In certain instances, the methods described herein may be performed in accordance with the casting methods described in this disclosure. The method includes providing a green thin film by casting the film.

[0354] In some of the methods disclosed herein, sintering is carried out using an inert setter plate. In some instances, sintering is performed between inert setter plates. In some cases, pressure is applied to the membrane during sintering by a setter plate. The pressure is between 1 and 1000 pounds per square inch (PSI). In some examples, the pressure is 1 PSI. In another example, the pressure is 10 PSI. In another example, the pressure is 20 PSI. In some other instances, the pressure is 30 PSI. In some instances, the pressure is 40 PSI. In still other instances, the pressure is 50 PSI. In some instances, the pressure is 60 PSI. In yet another example, the pressure is 70 PSI. In one example, the pressure is 80 PSI. In another example, the pressure is 90 PSI. In yet another example, the pressure is 100 PSI. In some instances, the pressure is 110 PSI. In other instances, the pressure is 120 PSI. In other instances, the pressure is 130 PSI. In some other instances, the pressure is 140 PSI. In one example, the pressure is 150 PSI. In yet another example, the pressure is 160 PSI. In some instances, the pressure is 170 PSI. In yet other instances, the pressure is 180 PSI. In one example, the pressure is 190 PSI. In another example, the pressure is 200 PSI. In another example, the pressure is 210 PSI.

[0355] In some of the above examples, the pressure is 220 PSI. In other examples, the pressure is 23 In some other examples, the pressure is 240 PSI. The force is 250 PSI. In some instances, the pressure is 260 PSI. In yet other instances, the pressure is In some instances, the pressure is 280 PSI. In yet other instances, The pressure is 290 PSI. In some instances, the pressure is 300 PSI. In other instances, the pressure is 31 In still other examples, the pressure is 320 PSI. In some examples, the pressure In another example, the pressure is 340 PSI. In yet another example, the pressure is 35 In some other instances, the pressure is 360 PSI. In some instances, the pressure is In still other instances, the pressure is 380 PSI. In some instances, the pressure is The force is 390 PSI. In yet another example, the pressure is 400 PSI. In some examples, the pressure In another example, the pressure is 420 PSI. In yet another example, the pressure is In some other instances, the pressure is 440 PSI. In still other examples, the pressure is 460 PSI. The pressure is 470 PSI. In yet another example, the pressure is 480 PSI. In one example, the pressure is In another example, the pressure is 500 PSI. In yet another example, the pressure is is 510 PSI.

[0356] In some of the above examples, the pressure is 520 PSI. In other examples, the pressure is 53 In some other examples, the pressure is 540 PSI. The force is 550 PSI. In some instances, the pressure is 560 PSI. In yet other instances, the pressure is In some instances, the pressure is 570 PSI. In other instances, the pressure is 580 PSI. The pressure is 590 PSI. In some instances, the pressure is 600 PSI. In other instances, the pressure is 61 In still other examples, the pressure is 620 PSI. In some examples, the pressure In another example, the pressure is 640 PSI. In yet another example, the pressure is 65 In some other instances, the pressure is 660 PSI. In some instances, the pressure is In still other instances, the pressure is 680 PSI. In some instances, the pressure is In yet another example, the pressure is 700 PSI. In another example, the pressure is 720 PSI. In yet another example, the pressure is In some other instances, the pressure is 740 PSI. In still other examples, the pressure is 760 PSI. The pressure is 770 PSI. In yet another example, the pressure is 780 PSI. In one example, the pressure is In another example, the pressure is 800 PSI. In yet another example, the pressure is is 810 PSI.

[0357] In another example, the pressure is 820 PSI. In one such example, the pressure is 830 PSI. In other instances, the pressure is 840 PSI. In some other instances, the pressure is 850 PSI. In one example, the pressure is 860 PSI. In yet another example, the pressure is 870 PSI. In some instances, the pressure is 880 PSI. In yet other instances, the pressure is 890 PSI. In one example, the pressure is 900 PSI. In another example, the pressure is 910 PSI. In still other instances, the pressure is 920 PSI. In some instances, the pressure is 930 PSI. In another example, the pressure is 940 PSI. In yet another example, the pressure is 950 PSI. In some other instances, the pressure is 960 PSI. In some instances, the pressure is 970 PSI. In still other instances, the pressure is 980 PSI. In some instances, the pressure is 990 PSI. In yet another example, the pressure is 1000 PSI.

[0358] In some instances, the setter plate can be porous. In other instances, the setter plate is not porous. The lithium activity in the plate is relatively high, i.e., the lithium concentration is In another example, the setter plate has at least 10 atomic percent of the SiO 2 content. In some examples, the setter plate may be made of a garnet material. can be a porous garnet setter plate. The plate may be made of zirconia. In some examples, the setter plate In another example, the setter plate may be a porous zirconia setter plate. The plate may be made of a metallic material as described herein. The setter plate can be a porous metal setter plate.

[0359] In some instances, garnet-based setter plates provide beneficial surface properties to the sintered film. These beneficial surface properties include flatness and surface roughness useful in battery applications. These beneficial properties include the prevention of Li evaporation during sintering. These beneficial properties include a preference for specific garnet crystal structures. In some methods disclosed herein, the inert setter plate may be porous. The conductive material is selected from conductive zirconia, graphite, or conductive metal plates. In some others, the inert setter plate is graphite. In yet another alternative, the inert setter plate is a conductive metal plate.

[0360] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Operate in amplitude mode, then switch to constant current mode once the membrane impedance has decreased by at least one order of magnitude. This includes operating in width mode.

[0361] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Then, when the impedance of the sintered film decreases by an order of magnitude, the sintered film is operated in constant current amplitude mode. This includes operating with a keyboard.

[0362] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Then, when the impedance of the sintered film decreases by two orders of magnitude, the sintered film is operated in constant current amplitude mode. This includes operating with a keyboard.

[0363] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Then, when the impedance of the sintered film decreases by three orders of magnitude, the sintered film is operated in constant current amplitude mode. This includes operating with a keyboard.

[0364] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Then, when the impedance of the sintered film decreases by four orders of magnitude, the sintered film is operated in constant current amplitude mode. This includes operating with a keyboard.

[0365] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The impedance of the sintered film is then reduced from 1-100 megaohm-cm to about 1-10 Once the resistance is reduced to 1,000 ohm-cm, the device is operated in a constant current amplitude mode.

[0366] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant voltage.

[0367] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at constant power.

[0368] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant current.

[0369] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. until the density is at least 20, 30, 40, or 50% greater than the film before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. and operating at constant power until the cell has a high density. In some cases, FAST sintering results in a film that is at least slightly thicker than the film before sintering. The method also includes operating at a constant current until the density is 20, 30, 40, or 50% greater.

[0370] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. have an impedance at least 1, 2, 3, or 4 orders of magnitude lower than the membrane had before freezing occurred. In some of the methods disclosed herein, the method comprises operating at a constant voltage until the FAST sintering allows the film to have at least 1.2 times the thickness of the film before sintering occurs. This includes operating at constant power until the device has an impedance that is three, four, or even three orders of magnitude lower. In some of the disclosed methods, FAST sintering is performed by sintering the membrane. Apply constant voltage until the membrane has an impedance at least 1, 2, 3, or 4 orders of magnitude lower than before. This involves operating in a flow.

[0371] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. an impedance at least one order of magnitude lower or at most ten orders of magnitude lower than the membrane had before sintering occurred Some of the methods disclosed herein include operating at a constant voltage until the In the present invention, FAST sintering is performed to make the film at least as thick as the film before sintering. This includes operating at constant power until the device has an impedance that is one order of magnitude lower or at most ten orders of magnitude lower. In some of the methods disclosed herein, FAST sintering is performed to ensure that the film is sintered. The membrane has an impedance at least one order of magnitude lower than that of the membrane before the This involves operating at a constant current until

[0372] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. Operate at a constant voltage until the membrane has an impedance approximately two orders of magnitude lower than that which the membrane would have before sintering. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance that is about two orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method comprises operating at constant power at FAST sintering results in a film with an impedance approximately two orders of magnitude lower than the film had before sintering took place. This involves operating at a constant current until the

[0373] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. Operate at a constant voltage until the membrane has an impedance approximately six orders of magnitude lower than that which the membrane would have before sintering occurred. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance that is about six orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method comprises operating at constant power at FAST sintering results in a film with an impedance approximately six orders of magnitude lower than the film had before sintering took place. This involves operating at a constant current until the

[0374] In some of the methods disclosed herein, FAST sintering is performed at a constant voltage. In some of the methods disclosed herein, FAST sintering Some of the methods disclosed herein include operating at constant power. In this case, FAST sintering involves operating at a constant current.

[0375] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Operate in amplitude mode, then switch to constant current mode once the membrane impedance has decreased by at least one order of magnitude. This includes operating in width mode.

[0376] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median size at least twice the median size of the garnet grains before sintering. The method includes operating at a ramp voltage until the voltage reaches a desired value. In some cases, FAST sintering means that the garnet particles are in the same state as the garnet particles before sintering. The lamp power is operated until the particles have a median dimension at least twice that of the toner particles. In some of the methods disclosed herein, the FAST sintering includes: The garnet grains are at least twice the median dimension of the garnet grains before sintering. This includes operating the lamp at a current until it has a median dimension equal to or greater than the specified value.

[0377] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the thickness of the film. In some instances, sintering is applied until the film is 50 μm thick. In another example, sintering is applied until the film is 40 μm thick. In another example, sintering is applied until the film is 20 μm thick. In another example, sintering is applied until the film is 10 μm thick. In one embodiment, sintering is applied until the film is 5 μm thick. In another example, sintering is continued until the film is 0.5 μm thick. As used in this paragraph, thickness refers to the average dimension of the membrane in the z-direction (as shown in Figure 23). (Refers to the

[0378] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the conductivity of the membrane. For example, Sintering can be applied until the film has a conductivity of 1e-4 S / cm. Sintering can be applied until the film has a conductivity of 1e-5 S / cm. In another example, sintering can be applied until the film has a conductivity of 1e-6 S / cm. , can be applied until the film has a conductivity of 1e-7 S / cm. It can be applied until the film has a conductivity of 1e-8 S / cm.

[0379] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the impedance of the membrane. For example, sintering can be applied until the impedance of the film is 500 ohm-cm.

[0380] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the grain size within the film.

[0381] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the density of the film.

[0382] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the optical density of the film.

[0383] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the temperature of the film. Sintering can be applied until the film has a temperature of 50° C. In another example, sintering In another example, sintering can be applied until the film has a temperature of 150°C. In another example, sintering can be applied until the film has a temperature of 200° C. In another example, sintering can be applied until the film has a temperature of 250°C. In another example, sintering can be performed until the film has a temperature of 300° C. In another example, sintering is applied until the film has a temperature of 350°C. In another example, sintering can be applied until the film has a temperature of 400°C. In another example, sintering can be applied until the film has a temperature of 450°C. In another example, sintering can be applied until the film has a temperature of 500°C. In one example, sintering can be applied until the film has a temperature of 550° C. In another example, sintering can be applied until the film has a temperature of 600°C. In another example, sintering may be performed until the film has a temperature of 650°C. In another example, sintering may be applied until the film has a temperature of 700° C. In another example, sintering can be applied until the film has a temperature of 800°C. In another example, sintering can be applied until the film has a temperature of 850° C. In another example, sintering can be applied until the film has a temperature of 900°C. In another example, sintering can be performed until the film has a temperature of 950°C. In another example, sintering can be applied until the film has a temperature of 1000°C. In another example, sintering can be applied until the film has a temperature of 1150°C. In another example, sintering can be applied until the film has a temperature of 1200°C. In another example, sintering can be applied until the film has a temperature of 1250°C. In one example, sintering can be applied until the film has a temperature of 1300° C. In this case, sintering can be applied until the film has a temperature of 1350°C.

[0384] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. The run is continued until the film has a density at least 20, 30, 40, or 50% greater than the film before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. The method disclosed herein includes operating the lamp at a high power until the lamp has a high density. In some cases, FAST sintering results in a film that is less porous than the film before sintering. This includes operating the lamp current until it has at least 20, 30, 40, or 50% greater density. In some of the methods disclosed herein, FAST sintering is performed to ensure that the film is sintered. impedance that is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower than the film has before The method of the present invention includes operating at a ramp voltage until the voltage reaches a predetermined value. In some cases, FAST sintering allows the film to have a higher melting point than the film had before sintering. Operate lamps with power levels up to 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower impedance In some of the methods disclosed herein, FAST sintering is means that the film has 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 times more pore size than the film has before sintering occurs. This involves operating the lamp current until it has an order of magnitude lower impedance.

[0385] In some of the methods disclosed herein, the FAST sintering is performed using a lamp current. In some of the methods disclosed herein, the FAST firing step involves operating at high pressure. The sintering includes operating at lamp power. In some cases, FAST sintering involves operating with a lamp current.

[0386] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Operate in amplitude mode, then switch to constant current mode once the membrane impedance has decreased by at least one order of magnitude. In some of the methods disclosed herein, the method includes operating in a width mode. FAST sintering is performed by operating in a constant voltage amplitude mode, after which the impedance of the sintered film is 1 If the current is reduced by an order of magnitude, this includes operating in a constant current amplitude mode. In some of these, FAST sintering is performed by operating in a constant voltage amplitude mode and then sintering. This involves operating in constant current amplitude mode once the membrane impedance has decreased by two orders of magnitude. In some of the methods disclosed in the document, the FAST sintering is performed in a constant voltage amplitude mode. Then, when the impedance of the sintered film decreases by three orders of magnitude, operate in constant current amplitude mode. In some of the methods disclosed herein, FAST sintering is It is operated in constant voltage amplitude mode, and then the impedance of the sintered film decreases by four orders of magnitude. This includes operating in a constant current amplitude mode.

[0387] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. The impedance of the sintered film is then reduced from 1-100 megaohm-cm to about 1-10 Once the resistance is reduced to 1,000 ohm-cm, the device is operated in a constant current amplitude mode.

[0388] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant voltage.

[0389] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at constant power.

[0390] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median dimension that is twice as large as that of the garnet grains before sintering. This includes operating at a constant current.

[0391] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. until the density is at least 20, 30, 40, or 50% greater than the film before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. and operating at constant power until the cell has a high density. In some cases, FAST sintering results in a film that is at least slightly thicker than the film before sintering. The method also includes operating at a constant current until the density is 20, 30, 40, or 50% greater.

[0392] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. have an impedance at least 1, 2, 3, or 4 orders of magnitude lower than the membrane had before freezing occurred. In some of the methods disclosed herein, the method comprises operating at a constant voltage until the FAST sintering allows the film to have at least 1.2 times the thickness of the film before sintering occurs. This includes operating at constant power until the device has an impedance that is three, four, or even three orders of magnitude lower. In some of the disclosed methods, FAST sintering is performed by sintering the membrane. Apply constant voltage until the membrane has an impedance at least 1, 2, 3, or 4 orders of magnitude lower than before. This involves operating in a flow.

[0393] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. an impedance at least one order of magnitude lower or at most ten orders of magnitude lower than the membrane had before sintering occurred Some of the methods disclosed herein include operating at a constant voltage until the In the present invention, FAST sintering is performed to make the film at least as thick as the film before sintering. This includes operating at constant power until the device has an impedance that is one order of magnitude lower or at most ten orders of magnitude lower. In some of the methods disclosed herein, FAST sintering is performed to ensure that the film is sintered. The membrane has an impedance at least one order of magnitude lower than that of the membrane before the This involves operating at a constant current until

[0394] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. Operate at a constant voltage until the membrane has an impedance approximately two orders of magnitude lower than that which the membrane would have before sintering. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance that is about two orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method comprises operating at constant power at FAST sintering results in a film with an impedance approximately two orders of magnitude lower than the film had before sintering took place. This involves operating at a constant current until the

[0395] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. Operate at a constant voltage until the membrane has an impedance approximately six orders of magnitude lower than that which the membrane would have before sintering occurred. In some of the methods disclosed herein, FAST sintering is That is, the film has an impedance that is about six orders of magnitude lower than the film had before sintering occurred. In some of the methods disclosed herein, the method comprises operating at constant power at FAST sintering results in a film with an impedance approximately six orders of magnitude lower than the film had before sintering took place. This involves operating at a constant current until the

[0396] In some of the methods disclosed herein, FAST sintering is performed at a constant voltage. In some of the methods disclosed herein, FAST sintering Some of the methods disclosed herein include operating at constant power. In this case, FAST sintering involves operating at a constant current.

[0397] In some of the methods disclosed herein, the FAST sintering is performed by a constant voltage oscillation. Operate in amplitude mode, then switch to constant current mode once the membrane impedance has decreased by at least one order of magnitude. This includes operating in width mode.

[0398] In some of the methods disclosed herein, the FAST sintering is performed by sintering garnet. The garnet grains have a median size at least twice the median size of the garnet grains before sintering. The method includes operating at a ramp voltage until the voltage reaches a desired value. In some cases, FAST sintering means that the garnet particles are in the same state as the garnet particles before sintering. The lamp power is operated until the particles have a median dimension at least twice that of the toner particles. In some of the methods disclosed herein, the FAST sintering includes: The garnet grains are at least twice the median dimension of the garnet grains before sintering. This includes operating the lamp at a current until it has a median dimension equal to or greater than the specified value.

[0399] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the thickness of the film. In some instances, sintering is applied until the film is 50 μm thick. In another example, sintering is applied until the film is 40 μm thick. In another example, sintering is applied until the film is 20 μm thick. In another example, sintering is applied until the film is 10 μm thick. In one embodiment, sintering is applied until the film is 5 μm thick. In another example, sintering is continued until the film is 0.5 μm thick. As used in this paragraph, thickness refers to the average dimension of the membrane in the z-direction (as shown in Figure 23). (Refers to the

[0400] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the conductivity of the membrane. For example, Sintering can be applied until the film has a conductivity of 1e-4 S / cm. Sintering can be applied until the film has a conductivity of 1e-5 S / cm. In another example, sintering can be applied until the film has a conductivity of 1e-6 S / cm. , can be applied until the film has a conductivity of 1e-7 S / cm. It can be applied until the film has a conductivity of 1e-8 S / cm.

[0401] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the impedance of the membrane. For example, sintering can be applied until the impedance of the film is 500 ohm-cm.

[0402] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the grain size within the film.

[0403] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the density of the film.

[0404] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the optical density of the film.

[0405] In some embodiments, the FAST sintering is operated by feedback control. wherein the applied voltage, applied power, or applied current satisfies a predetermined value during sintering. In some instances, these values ​​include the temperature of the film. Sintering can be applied until the film has a temperature of 50° C. In another example, sintering In another example, sintering can be applied until the film has a temperature of 150°C. In another example, sintering can be applied until the film has a temperature of 200° C. In another example, sintering can be applied until the film has a temperature of 250°C. In another example, sintering can be performed until the film has a temperature of 300° C. In another example, sintering is applied until the film has a temperature of 350°C. In another example, sintering can be applied until the film has a temperature of 400°C. In another example, sintering can be applied until the film has a temperature of 450°C. In another example, sintering can be applied until the film has a temperature of 500°C. In one example, sintering can be applied until the film has a temperature of 550° C. In another example, sintering can be applied until the film has a temperature of 600°C. In another example, sintering may be performed until the film has a temperature of 650°C. In another example, sintering may be applied until the film has a temperature of 700° C. In another example, sintering can be applied until the film has a temperature of 800°C. In another example, sintering can be applied until the film has a temperature of 850° C. In another example, sintering can be applied until the film has a temperature of 900°C. In another example, sintering can be performed until the film has a temperature of 950°C. In another example, sintering can be applied until the film has a temperature of 1000°C. In another example, sintering can be applied until the film has a temperature of 1150°C. In another example, sintering can be applied until the film has a temperature of 1200°C. In another example, sintering can be applied until the film has a temperature of 1250°C. In one example, sintering can be applied until the film has a temperature of 1300° C. In this case, sintering can be applied until the film has a temperature of 1350°C.

[0406] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. The run is continued until the film has a density at least 20, 30, 40, or 50% greater than the film before sintering. In some of the methods disclosed herein, the FA ST sintering is performed to ensure that the film is at least 20, 30, 40, or 50% thicker than the film before sintering. The method disclosed herein includes operating the lamp at a high power until the lamp has a high density. In some cases, FAST sintering results in a film that is less porous than the film before sintering. This includes operating the lamp current until it has at least 20, 30, 40, or 50% greater density.

[0407] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. The impedance is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower than the membrane had before freezing. The method disclosed herein includes operating at a ramp voltage until the device has a In some cases, FAST sintering allows the film to have a higher melting point than the film had before sintering took place. Operate the lamp power until it has 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower impedance. This includes creating

[0408] In some of the methods disclosed herein, FAST sintering allows the membrane to be sintered. The impedance is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 orders of magnitude lower than the membrane had before freezing. This involves operating the lamp current until it has a

[0409] In some of the methods disclosed herein, the FAST sintering is performed using a lamp current. In some of the methods disclosed herein, the FAST firing step involves operating at high pressure. The sintering includes operating at lamp power. In some cases, FAST sintering involves operating with a lamp current.

[0410] In any of the methods described herein, FAST sintering the film can be performed at temperatures between about 400°C and This may involve heating in the range of about 1000° C. and applying a DC or AC electric field to the thin film. In some instances, FAST sintering involves heating the film in the range of about 500°C to about 900°C. and applying a DC or AC electric field to the thin film. The method involves heating the film in the range of about 600°C to about 900°C and applying a DC or AC electric field to the thin film. In some examples, FAST sintering includes applying a temperature of about 700°C to about 900°C. These include heating in the range of °C and applying a DC or AC electric field to the thin film. In an example, FAST sintering involves heating the film in the range of about 800°C to about 900°C and In some instances, FAST sintering involves applying a DC or AC electric field to the The thin film is heated to a temperature in the range of about 500°C to about 800°C and a DC or AC electric field is applied to the thin film. In some examples, FAST sintering includes sintering the film at a temperature in the range of about 500°C to about 700°C. This includes heating and applying a DC or AC electric field to the thin film. FAST sintering involves heating the film in the range of about 500°C to about 600°C and applying DC or It involves applying an AC electric field.

[0411] In any of the methods described herein, FAST sintering the film can be performed at temperatures between about 400°C and This may involve heating in the range of about 1000°C and applying a DC electric field to the thin film. In this example, FAST sintering involves heating the film in the range of about 600°C to about 900°C and In some instances, FAST sintering involves applying a DC electric field to the film. This involves heating the thin film to a temperature in the range of about 600°C to about 900°C and applying a DC electric field to the thin film. In some examples, FAST sintering involves heating the film in the range of about 700°C to about 900°C and and applying a DC electric field to the thin film. In some examples, FAST sintering includes: This involves heating the film in the range of about 800°C to about 900°C and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film in the range of about 500°C to about 800°C. and applying a DC electric field to the thin film. In some instances, FAST sintering The method involves heating the film in the range of about 500°C to about 700°C and applying a DC electric field to the thin film. In some instances, FAST sintering involves heating the film to a temperature in the range of about 500°C to about 600°C. This involves applying a DC electric field to the thin film.

[0412] In any of the methods described herein, FAST sintering the film can be performed at temperatures between about 400°C and This may include heating in the range of about 1000° C. and applying an AC electric field to the thin film. In any of the methods described above, the FAST sintering may be performed by sintering the film at a temperature in the range of about 500°C to about 900°C. This may include heating the thin film in a heated atmosphere and applying an AC electric field to the thin film. FAST sintering involves heating the film in the range of about 600°C to about 900°C and applying an AC electric field to the thin film. In some examples, FAST sintering involves applying a temperature of about 700°C to about 9 In some examples, this involves heating the thin film in the range of 0 to 100°C and applying an AC electric field to the thin film. In this case, FAST sintering involves heating the film in the range of about 800°C to about 900°C and applying AC In some examples, FAST sintering involves applying an electric field to the film at about 500°C. Some of these include heating the thin film to temperatures in the range of 1000 to 800°C and applying an AC electric field to the thin film. In an example, FAST sintering involves heating the film in the range of about 500°C to about 700°C and In some instances, FAST sintering involves applying an AC electric field to the film. This involves heating in the range of 500°C to about 600°C and applying an AC electric field to the thin film.

[0413] In certain instances, the methods described herein can be used to produce green thin films by casting the films. This includes providing:

[0414] (vii. Composite materials) In another embodiment, the present disclosure provides a method for making a composite electrochemical device. The method comprises the steps of: providing an anode layer comprising an anode current collector; providing a garnet-type solid electrolyte (SSE) layer in contact with at least one side of the oxide layer; and optionally sintering the SSE; providing a porous garnet layer in contact with the SSE layer; and optionally sintering the porous garnet layer; optionally adding carbon, a lithium conducting polymer, an active cathode material, and a combination thereof; and infiltrating at least one member into contact with the porous garnet layer. The present invention describes a method that includes, in any order, the steps of providing a metal oxide film and a metal current collector layer.

[0415] In some examples, described herein are thin, free-standing garnet films. A method for sintering, comprising the steps of: casting a garnet slurry to form a garnet powder; providing a garnet tape, wherein the slurry comprises a garnet precursor, a garnet, a bar at least one selected from the group consisting of binders, solvents, plasticizers, dispersants, and combinations thereof; sintering the green tape between setter plates; wherein the sintering is performed by thermal sintering, spark plasma sintering, or and sintering the film using the setter plate. Optionally, applying pressure to the

[0416] In some of these aforementioned examples, the slurry is ground and calcined. In some instances, the solids loading of the green tape is at least 30% In some instances, the solids loading of the green tape is at least 40% w / w In some instances, the solids loading of the green tape is at least 50% w / w. In some instances, the solids loading of the green tape is at least 60% w / w. In some instances, the solids loading of the green tape is at least 70% w / w. In some of these examples, the membrane is sintered directly to the metal. In some instances, the metal is a metal powder or a metal foil. It is located between and in contact with one side of the loop and one setter plate. In this example, a layer of metal powder is placed between and in contact with two green tapes. wherein the green tape is between and in contact with the setter plates. In some examples, the metal powder is Ni or Cu powder. In some, a source of Li is placed near the film being sintered during sintering. In particular examples, the setter plate may be made of YSZ, graphite, YSZ, Mg-SZ, zirconia, , porous zirconia, SiO2, SiO2 sand, Al2O3, Al2O3 powder, Al2O3 paper, nickel, Nickel powder, garnet, garnet powder, sacrificial garnet film, LiAlO2, LiLaO2, Li2ZrO 3. In some instances, two different setter plates are used. In some of these examples, the zirconia setter plate comes into contact with the metal powder. In some examples, the applied pressure is between 0.001 MPa and 200 MPa.

[0417] (viii. Two-layer and three-layer sintering) In some instances, the sintered film may contain a metal layer that later contacts the garnet-electrolyte layer. A non-limiting example is shown in FIG. 4 or FIG. 29. show.

[0418] (ix. Thermal Sintering) In some embodiments, disclosed herein are methods for fabricating energy storage electrodes. 1. A method of forming a thin film of a sintered material comprising: providing a thin green film; The membrane comprises a garnet-type electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and In some examples, the composition includes at least one member selected from the group consisting of: The method further includes removing solvent, if present in the green thin film. In some examples, the method optionally includes laminating the film to a surface. In the method, the method includes removing the binder, if present in the film. In some instances, the method includes sintering the film, wherein sintering includes thermal firing. In some of these examples, thermal sintering includes sintering the film to a temperature of: The temperature range is from about 700°C to about 1200°C for about 1 to about 600 minutes, and the oxygen partial pressure is from 1e-1 to 1e-15 atmospheres. This includes heating in an atmosphere containing

[0419] In some embodiments, disclosed herein are methods for fabricating energy storage electrodes. 1. A method of forming a thin film of a sintered material comprising: providing a thin green film; The membrane comprises a garnet-type electrolyte, an active electrode material, a conductive additive, a solvent, a binder, and In some examples, the composition includes at least one member selected from the group consisting of: The method further includes removing solvent, if present in the green thin film. In some examples, the method optionally includes laminating the film to a surface. In the method, the method includes removing the binder, if present in the film. In some examples, the method includes sintering the film, wherein sintering comprises applying an electric field In some of these examples, FAST sintering is This means that the film is heated in the range of about 500°C to about 900°C and a DC or AC electric field is applied to the thin film. This includes adding

[0420] In any of the methods described herein, the green thin film comprises a garnet-type electrolyte. In other methods, the green thin film may include the active electrode material. In some methods, the green thin film may include a conductive additive. In some methods, the green thin film may include a binder.

[0421] In any of the methods described herein, the thermal sintering may involve heating the film to a temperature of about 700°C to about 1200°C; or about 800°C to about 1200°C; or about 900°C to about 1200°C; or about 1000°C to about 1200°C; or Any of the methods described herein may include heating in the range of about 1100°C to about 1200°C. In this case, the thermal sintering may be performed by heating the film to a temperature of about 700°C to about 1100°C; or about 700°C to about 1000°C; or may include heating in the range of about 700°C to about 900°C; or about 700°C to about 800°C. In any of the methods described herein, thermal sintering may involve sintering the film at about 700° C., about 7 50℃, approximately 850℃, approximately 800℃, approximately 900℃, approximately 950℃, approximately 1000℃, approximately 1050℃, approximately 1100℃, approximately 1150℃ or about 1200° C. Any of the methods described herein may include heating to about 1200° C. In this case, thermal sintering is performed to form the film at 700°C, 750°C, 850°C, 800°C, 900°C, 950°C, 10 This can include heating to 100°C, 1050°C, 1100°C, 1150°C, or 1200°C. In any of the methods described in the document, the thermal sintering includes heating the film to 700°C. In any of the methods described herein, the thermal sintering may include Any of the methods described herein can include heating the film to 750° C. In the present specification, the thermal sintering may include heating the film to 850°C. In any of the methods described in , the thermal sintering comprises heating the film to 900°C. In any of the methods described herein, the thermal sintering can include: Any of the methods described herein may include heating the film to 950° C. In the present invention, the thermal sintering may include heating the film to 1000°C. In any of the methods described, the thermal sintering includes heating the film to 1050°C. In any of the methods described herein, the thermal sintering can include forming a film. In any of the methods described herein, the method may include heating the mixture to 1100°C. In this case, thermal sintering can include heating the film to 1150°C. In any of the methods described, the thermal sintering includes heating the film to 1200°C. It is possible.

[0422] In any of the methods described herein, the method includes heating the film for about 1 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about 20 In any of the methods described herein, the method may include heating for about 600 minutes. The method may include heating the film for about 30 to about 600 minutes. In either case, the method may include heating the film for about 40 to about 600 minutes. In any of the methods described above, the method includes heating the film for about 50 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about 60 to about 600 In any of the methods described herein, the method may include heating for 1 minute. Any of the methods described herein may include heating the film for about 70 to about 600 minutes. In the method, the method may include heating the film for about 80 to about 600 minutes. In any of the methods described above, the method may include heating the film for about 90 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 100 to about 600 minutes. In any of the methods described herein, the method may include subjecting the membrane to about In any of the methods described herein, the method may include heating for 120 to about 600 minutes. The method may include heating the film for about 140 to about 600 minutes. In any of the above, the method may include heating the membrane for about 160 to about 600 minutes. In any of the methods described in the document, the method comprises heating the membrane for about 180 to about 600 minutes. In any of the methods described herein, the method may include filtering the membrane for about 200 to about 6 In any of the methods described herein, the method may include heating for 0.5 minutes. Any of the methods described herein may include heating the film for about 300 to about 600 minutes. In the method, the film may be heated for about 350 to about 600 minutes. In any of the methods described above, the method may include heating the film for about 400 to about 600 minutes. In any of the methods described herein, the method includes heating the membrane for about 450 to about 600 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating for about 500 to about 600 minutes. The method may include heating the film for about 1 to about 500 minutes. In any of the above, the method may include heating the film for about 1 to about 400 minutes. In any of the methods described above, the method includes heating the film for about 1 to about 300 minutes. In any of the methods described herein, the method may include heating the membrane for about 1 to about 200 minutes. In any of the methods described herein, the method may include heating the membrane. In any of the methods described herein, the method may include heating the mixture for about 1 to about 100 minutes. The method may include heating the membrane for about 1 to about 50 minutes.

[0423] (x. Lamination) In some of the methods described herein, the lamination is subjected to a pressure of 1000 pounds per square inch. In another embodiment, the method includes applying a pressure of less than 100 psi and heating the membrane. Lamination involves applying pressure of less than 750 pounds per square inch (PSI) and heating the film. In some other embodiments, the lamination is performed at a pressure of less than 700 pounds per square inch (PSI). In another embodiment, the lamination comprises applying a pressure of 650 lbs. Some other methods involve applying pressure less than 1000 psi and heating the membrane. In this embodiment, the lamination is performed by applying a pressure of less than 600 pounds per square inch (PSI) and In another embodiment, the lamination is performed at a temperature of 550 pounds per square inch (PSI). In some other embodiments, the method further comprises applying a pressure of less than 1000 kJ / cm and heating the membrane. The lamination involves applying a pressure of less than 500 pounds per square inch (PSI) and heating the membrane. In other embodiments, the lamination applies a pressure of less than 450 pounds per square inch (PSI). In some other embodiments, the lamination comprises heating the film to 400 lbs. Other embodiments include applying a pressure of less than 1000 psi per square inch (PSI) and heating the membrane. In this manner, the lamination is performed by applying a pressure of less than 350 pounds per square inch (PSI) and heating the membrane. In some other embodiments, the laminate is heated to 300 pounds per square inch (PS In another embodiment, the lamination comprises applying a pressure of less than I) and heating the film. This involves applying a pressure of less than 250 pounds per square inch (PSI) and heating the membrane. In some other embodiments, the lamination is performed under pressure of less than 200 pounds per square inch (PSI). In another embodiment, the lamination includes heating the film at 150 pounds per square meter. This involves applying pressure of less than 1 / 4 inch (PSI) and heating the membrane.

[0424] In some other embodiments, the lamination is performed at a pressure of less than 100 pounds per square inch (PSI). In another embodiment, the lamination comprises adding 50 pounds per square meter of water and heating the film. Some other methods involve applying pressure of less than 1 / 4 inch per square inch (PSI) and heating the membrane. In an embodiment, lamination is performed by applying a pressure of less than 10 pounds per square inch (PSI) and pressing the membrane. Some of the lamination methods described herein involve heating the film. Some of the lamination methods described herein involve heating the The heated film is heated to a temperature of about 25°C to about 180°C.

[0425] In some of the methods disclosed herein, the deposition step involves depositing a green thin film electrolyte. into a composite electrode; wherein the composite electrode comprises an electrolyte, an active electrode material, a conductive and combinations thereof. In some of these embodiments, the composite electrode includes an electrolyte. In certain other embodiments, the composite electrode includes an active electrode material. In some other embodiments, the composite electrode includes a conductive additive.

[0426] (xi. Setter plate) In some of the methods disclosed herein, sintering is carried out using an inert setter plate. In some instances, sintering is performed between inert setter plates. In some cases, pressure is applied to the membrane during sintering by a setter plate. The pressure may be between 1 and 1000 pounds per square inch (PSI). In some instances, the pressure may be 1 PSI. In another example, the pressure is 10 PSI. In yet another example, the pressure is 20 PSI. In some other instances, the pressure is 30 PSI. In some instances, the pressure is 40 PSI. In yet other instances, the pressure is 50 PSI. In some instances, the pressure is 60 PSI. In yet another example, the pressure is 70 PSI. In some examples, the pressure is 80 PSI. In some examples, the pressure is 90 PSI. In other examples, the pressure is 100 PSI. In some instances, the pressure is 110 PSI. In other instances, the pressure is 120 PSI. In some examples, the pressure is 130 PSI. In some other examples, the pressure is 140 PSI. In one example, the pressure is 150 PSI. In yet another example, the pressure is 160 PSI. In some instances, the pressure is 170 PSI. In still other instances, the pressure is 180 PSI. In one example, the pressure is 190 PSI. In another example, the pressure is 200 PSI. In another example, the pressure is 210 PSI.

[0427] In some of the above examples, the pressure is 220 PSI. In other examples, the pressure is 23 In some other examples, the pressure is 240 PSI. The force is 250 PSI. In some instances, the pressure is 260 PSI. In yet other instances, the pressure is In some instances, the pressure is 280 PSI. In yet other instances, The pressure is 290 PSI. In some instances, the pressure is 300 PSI. In other instances, the pressure is 31 In still other examples, the pressure is 320 PSI. In some examples, the pressure In another example, the pressure is 340 PSI. In yet another example, the pressure is 35 In some other instances, the pressure is 360 PSI. In some instances, the pressure is In still other instances, the pressure is 380 PSI. In some instances, the pressure is The force is 390 PSI. In yet another example, the pressure is 400 PSI. In some examples, the pressure In another example, the pressure is 420 PSI. In yet another example, the pressure is In some other instances, the pressure is 440 PSI. In still other examples, the pressure is 460 PSI. The pressure is 470 PSI. In yet another example, the pressure is 480 PSI. In one example, the pressure is In another example, the pressure is 500 PSI. In yet another example, the pressure is is 510 PSI.

[0428] In some of the above examples, the pressure is 520 PSI. In other examples, the pressure is 53 In some other examples, the pressure is 540 PSI. The force is 550 PSI. In some instances, the pressure is 560 PSI. In yet other instances, the pressure is In some instances, the pressure is 570 PSI. In other instances, the pressure is 580 PSI. The pressure is 590 PSI. In some instances, the pressure is 600 PSI. In other instances, the pressure is 61 In still other examples, the pressure is 620 PSI. In some examples, the pressure In another example, the pressure is 640 PSI. In yet another example, the pressure is 65 In some other instances, the pressure is 660 PSI. In some instances, the pressure is In still other instances, the pressure is 680 PSI. In some instances, the pressure is In yet another example, the pressure is 700 PSI. In another example, the pressure is 720 PSI. In yet another example, the pressure is In some other instances, the pressure is 740 PSI. In still other examples, the pressure is 760 PSI. The pressure is 770 PSI. In yet another example, the pressure is 780 PSI. In one example, the pressure is In another example, the pressure is 800 PSI. In yet another example, the pressure is is 810 PSI.

[0429] In another example, the pressure is 820 PSI. In one such example, the pressure is 830 PSI. In other instances, the pressure is 840 PSI. In some other instances, the pressure is 850 PSI. In one example, the pressure is 860 PSI. In yet another example, the pressure is 870 PSI. In some instances, the pressure is 880 PSI. In yet other instances, the pressure is 890 PSI. In one example, the pressure is 900 PSI. In another example, the pressure is 910 PSI. In still other instances, the pressure is 920 PSI. In some instances, the pressure is 930 PSI. In another example, the pressure is 940 PSI. In yet another example, the pressure is 950 PSI. In some other instances, the pressure is 960 PSI. In some instances, the pressure is 970 PSI. In still other instances, the pressure is 980 PSI. In some instances, the pressure is 990 PSI. In yet another example, the pressure is 1000 PSI.

[0430] In some instances, garnet-based setter plates provide beneficial surface properties to the sintered film. These beneficial surface properties include flatness and surface roughness useful in battery applications. These beneficial properties include the prevention of Li evaporation during sintering. These beneficial properties include a preference for specific garnet crystal structures. It can also be done as follows.

[0431] In certain methods disclosed herein, the inert setter plate is made of porous zirconia. The method is selected from the following: alumina, graphite, or conductive metal plate. In some cases, the inert setter plate is porous zirconia. In some others, the inert setter plate is graphite. In yet another approach, the inert setter plate is a conductive metal plate.

[0432] (h. oxygen partial pressure) In some instances, the sintering method involves placing an acid in the atmosphere in contact with the garnet material being sintered. In some examples, the oxygen partial pressure is controlled by controlling the oxygen concentration in the argon and water mixture. By flowing a mixture of nitrogen and water (i.e., H2O) in contact with the garnet material being sintered. In some instances, the oxygen partial pressure is controlled by the flow rate of argon, hydrogen, or water, Alternatively, by adjusting the flow rate of all three gases or any combination of these gases. In some instances, the oxygen partial pressure is 2E-1 (i.e., 20% O2). In other instances, the oxygen partial pressure is 1E-2. In some instances, the oxygen partial pressure is 1E-3. In other instances, the oxygen partial pressure is 1E-4. In some other instances, the oxygen partial pressure is 1E In some instances, the oxygen partial pressure is 1E-6. In other instances, the oxygen partial pressure is In some other instances, the oxygen partial pressure is 1E-8. In some other examples, the oxygen partial pressure is 1E-9. In some instances, the oxygen partial pressure is 1E-11. In other instances, the oxygen partial pressure is 1E-3. In some examples, the oxygen partial pressure is 1E-12. In some other examples, the oxygen partial pressure is 1E-13. In other examples, the oxygen partial pressure is 1E-14. In some other examples, the oxygen partial pressure is In some instances, the oxygen partial pressure is 1E-16. In other instances, the oxygen In some other examples, the oxygen partial pressure is 1E-18. In some instances, the oxygen partial pressure is 1E-19. In other instances, the oxygen partial pressure is 1E-20. In other instances, the oxygen partial pressure is 1E-21. In some instances, the oxygen partial pressure is 1E-22. In other examples, the oxygen partial pressure is 1E-23. In some other examples, the oxygen partial pressure is is 1E-24. In some instances, the oxygen partial pressure is 1E-25.

[0433] (i. Grinding Method) As described herein, some of the recited methods include method steps related to mixing and The present invention includes method steps relating to grinding and / or milling. Milling includes ball milling. Milling is not limited to However, ethanol, isopropanol, toluene, ethyl acetate, methyl acetate, acetone, Also included are methods of grinding using inert solvents such as acetonitrile, acetonitrile, or combinations thereof. Depending on the materials used, the solvent may not be inert. The grinding may be carried out in a solvent such as, but not limited to, ethanol, isopropanol, toluene, ethyl acetate, Milling with solvents such as methyl acetate, acetone, acetonitrile, or combinations thereof include.

[0434] In some instances, the milling is ball milling. In some instances, the milling is In some instances, the grinding is attritor grinding. In some instances, the milling is immersion milling. In some instances, the milling is high-energy milling. In some instances, the high energy milling process 50 is 100nm of crushed particle size In some instances, the milling is immersion milling.

[0435] In some instances, a high energy milling process is used to 50 Particle size distribution of approximately 100 nm In some examples, the solvent is toluene. The solvent is isopropyl alcohol (IPA). In some instances, the solvent is ethanol. In some instances, the solvent is diacetone alcohol. In the examples, the solvent is 50 A suitable polar solvent is used to achieve this diameter.

[0436] In some instances, the milling is performed using 0.3 mm yttria-stabilized zirconium oxide grinding media. In some instances, this includes a high energy wet milling process using beads. Crushing, horizontal milling, attritor milling, or immersion milling can be used. In this case, a high-energy milling process is used to produce approximately d 50 has a particle size distribution of ~100 nm Glass. [Example]

[0437] IV. EXAMPLES In the examples described herein, the product lithium formed by the methods herein The subscript values ​​of the um-filled garnets are used to make the claimed compositions. represents the elemental molar ratios of the precursor chemicals used.

[0438] a. Example 1 - Flux Deposition of Li-Conductive Ceramics In some embodiments, preformed garnet material, i.e., a seed crystal, is used to grow other garnets. A net material is produced. In this example, 100 grams (g) of LiLaZrO 12 31.03g of Li2CO3 , 58.65 g of La2O3, and 29.57 g of ZrO2. The resulting mixture is dissolved in isopropanol. The mixture was then ball milled at 900°C for 24 hours. The product was then sintered at 1100°C for 12 hours. , reducing the average particle size to 1 μm.

[0439] b. Example 2 - Flux Deposition of Li-Conductive Ceramics In this example, a thin film garnet electrolyte of 3 μm to 50 μm is produced. The garnet precursor was LiOH / Li2CO3 / LiO2 / La2O3 / ZrO2. 0.3 mm yttria stabilized The precursor was milled using zirconium oxide grinding media beads. The mixture was dispersed in a slurry formulation, and the slurry was deposited on a metal foil. The slurry was then dried. The film was then pressed with a plate and heated to sinter the components therein. Doped compositions were prepared using Al2O3 as the source of Al, Nb2O5 as the source of Nb, and Ta. 2O5 was used as the source of Ta.

[0440] The garnet precursor slurry was deposited onto a metal foil substrate. A piece of nickel approximately 0.5 mil thick was used. The substrates were prepared using a cleaning method. In some cases, the IPA solution was used. The residual organic matter on the surface of the metal foil was removed using a solvent. Gas plasma treatment, and chemical treatment (ammonium hydroxide or light acids such as citric acid / acetic acid) Using other surface cleaning methods, such as base solutions, to prepare the surface for slurry application. It is also possible to use a doctor blade and adjust the doctor blade gap to 3um to 100 A film thickness of 100 μm was achieved.

[0441] Next, the deposited film was dried. After the film was dried, the deposited film was subjected to a calendering treatment to heat the film. A dense film was achieved before the process. Depending on the starting thickness, up to 50% thickness reduction was achieved by calendering. This was achieved after the step. The next step involved applying pressure to the membrane. A maximum pressure of 20 MPa was applied.

[0442] Next, a sintering process was carried out. The size of the sintered grains varied depending on the degree of sintering carried out. Sintering was carried out at a temperature range of approximately 900°C to 1200°C with a dwell time of only 15 to 90 minutes. provided.

[0443] The sintering process increases the density and uniformity of the garnet thin film. The garnet phase was confirmed by XRD analysis of the thin garnet film fabricated as a garnet film. As shown by XRD.

[0444] c. Example 3 - Densification with Bismuth Flux In this example, the lithium-loaded garnet powder was composed of a 1:1 mixture of Li2CO3 and B2O3. The powder was densified using a flux that is suitable for this purpose.

[0445] Figure 52 shows the resulting lithium-loaded garnet films as a function of flux heating conditions. The resulting densities are shown: 900°C, 30 min (bottom curve); 950°C, 30 min (second-to-bottom curve). line); 950°C, 6 hours (third curve from the bottom); 100°C, 30 minutes (top curve).

[0446] (d. Example 4 - Preparation of Microcrystalline Granular Li-Ion Conductive Garnet Ceramics) In this example, LiOH, La2O3, ZrO2, and Al(NO3).9H2O were combined in various ratios to form The mixture was mixed by dry ball milling for 8 hours, after which it was placed in an alumina crucible in air. The mixture was calcined at 800 to 1000°C for 4 to 8 hours.

[0447] As mentioned above, Li7La3Zr2O 12 · To produce 0.35Al2O3 phase, the molar ratio of Li:La:Zr:Al2 The above reactants were mixed in a ratio of 7:3:2:0.35.

[0448] (Using yttria-stabilized zirconia grinding media (approximately 2-10 hours) and an 80 mesh sieve) 64.6 grams (g) of dried and ground LiOH was mixed with 184.5 g of La2O3, 93.9 g of ZrO2, and 96.3 g of Al(NO3 Composition C (the XRD of which is shown in Figure 49) was prepared by reacting HCl with HCl. The reactant powder was dried at 120° C. for about 1 hour. The powder was then heated in an alumina crucible in air. The mixture was calcined at 800 to 1000°C for 4 to 8 hours.

[0449] The product (as measured by light scattering) 50 The powder was milled with a solvent until the particle size reached about 300 nm, and then dried. This dry powder was dissolved in isopropanol at 4% w / w of polyvinyl bromide. By mixing with chiral, removing the isopropanol, and passing through an 80-mesh sieve, A pellet was formed.

[0450] This binder is used to make pellets with a diameter of 13 mm and a thickness of about 1.2 to 1.4 mm, under about 3 metric tons. Pressure was applied from the applied powder. The pellets were placed between setter plates and dried. The powders were sintered in a tubular furnace with Ar (flow rate 315 sccm) at 150-180°C for 1-4 hours. Then, heat sintering at 300-350°C for 1-4 hours, then at 1000-1200°C for 3-9 hours, and then The cooling included:

[0451] The mass and dimensions of the sintered pellets were measured to determine the geometric density and subjected to scanning electron microscopy. The grain size on the fracture surface was determined using this method.

[0452] Figure 9 shows a map of the compositional space that was explored. Compositional variables include lithium and aluminum. The lanthanum to zirconium ratio was maintained at 3:2 throughout the study. Figure 9 shows that the investigated phase space contains highly conductive (>10 -4 S / cm) area exists. This zone is larger for the lower sintering temperature (1075°C compared to 1150°C). The high temperature, short dwell conditions (1200°C, 15 min) are comparable to the samples produced at lower temperatures. Some of the compositions disclosed in this study, e.g. For example, compositions A, B, C, and D produce high conductivity (as shown in FIG. 9).

[0453] Composition A is Li 6.3 La3Zr2O 12 Characterized by 0.35Al2O3.

[0454] Composition B is Li 6.3 La3Zr2O 12 · Characterized by 0.67Al2O3.

[0455] Composition C is Li7La3Zr2O 12 · Characterized by 0.67Al2O3.

[0456] Composition D is Li7La3Zr2O 12 · Characterized by Al2O3.

[0457] Figure 10 shows a cross section through the phase space map (Figure 9) and also shows the associated density and grain size. do.

[0458] The processing and sintering of garnet ceramics described herein is comparable to other known techniques. In comparison, a relatively short reaction time and moderate temperature were utilized. The garnet grain size remains relatively small (i.e., <10um), above which the crystal grain size becomes too large (i.e., >100um), This indicates that Bell is present.

[0459] FIG. 11 provides a comparative analysis of known garnet compositions and those described herein. These other studies show that for all aluminum contents studied, It is clear that it functions in the "high lithium" region. Furthermore, the known sintering temperature of garnet Most of the processing was performed at temperatures above 1200°C and for long periods (e.g., over 10 hours). This results in large grain growth and is incompatible with the powders, films, and devices described in this application. The present application provides garnet films with conductivity values ​​suitable for use in secondary battery applications. It shows unexpectedly short processing dwell times and unexpectedly low temperature processing conditions.

[0460] The examples described herein limit the Li content and sintering temperature to minimize the lithium content. It has been shown that small grain sizes can be achieved in the lanthanum-zirconia-alumina system. The specific composition (composition B) with Li, Al=6.3, 0.67 is exemplary because The composition is found to be small grained after sintering at 1075°C, but This is due to the large grain size resulting from the selected processing conditions and This shows how specific the process is. In this case, compositions A, B, C, and D in the current study exhibited low grain size and high conductivity (>10 -4 S / cm) Note that this results in a fairly unique combination.

[0461] FIG. 12 shows a graphite alloy having fine grains as described herein and formed at a lower temperature, e.g., 1075°C. 1 shows an example of a scanning electron microscope image of a sintered lithium-filled garnet.

[0462] Figure 13 shows the bulk conductivity of * 10 -4 Li exceeding S / cm x La3Zr2O 12 ·yAl2O3 with Li:Al x:y The ratio is shown.

[0463] FIG. 14 illustrates various compositions that can be made using the methods described herein and the The densities associated with these compositions are shown.

[0464] FIG. 49 shows the XRD of composition C.

[0465] e. Impedance Measurement of Pellets of Example 5 - Composition C The pellet was polished to a thickness of approximately 1 mm, after which platinum (Pt) electrodes were attached to either side. The electrical transport properties were determined by sputter deposition. Spectra were measured at several temperatures.

[0466] Figure 50 shows the impedance of a polished pellet of composition C. R1 is the R2 is due to the interfacial impedance. The electrode effect is due to the Li This is due to the blocking of ions. The total resistance is equal to R1 + R2. The conductivity is given by the following equation:

number

[0467] The reported conductivities include all resistances observed in the impedance spectrum. do.

[0468] (f. Example 6 - Full Cell Charging and Discharging) A pellet of garnet containing composition C and a 2 μm Li deposited layer on one side of the pellet. a conductive additive comprising a carbon and sulfur-containing catholyte on the other side of the pellet; An electrochemical cell was assembled containing a cathode containing NCA along with the reagent.

[0469] The charge / discharge curves are shown in FIG.

[0470] (g. Example 7 - Plating and Stripping) Garnet bilayer thin films: Lithium plating and delamination for plating and delaminating Li on Ni|G|eLi The initial open circuit voltage is ~2.5 V. Initially, the current is set to 1 mA / cm. 2 Percentage of The cell voltage is gradually decreased toward 0. When the voltage drops below 0 (t=500 seconds), Li begins to plate at the nickel interface. At t=800 s, the current is turned off. The voltage is At t = 900 seconds, the four-step cycle begins. Repeat several times. 2 The current is then turned on again and plating is continued for 2 minutes. Then, 1mA / cm 2 The Li was stripped off for 2 minutes by passing the wire in the opposite direction. After repeating this sequence 10 times, Li is finally removed from the Ni side by the final peeling current. When the lithium is completely removed from the battery and, as a result, the lithium is depleted, the voltage rises sharply (t=2800 seconds).

[0471] The results are shown in Figure 48.

[0472] h. Example 8 - Powder, Slurry, Tape, and Bilayer Example 4: Preparation of fine-crystalline granular Li-ion conducting garnet ceramics We have produced um-filled garnets.

[0473] The powder was formulated as a slurry by milling the powder. 20 g of dry milled powder was , YSZ grinding media, and toluene, ethanol, and a phosphate ester dispersant. 8 g of this powder was then mixed with a 33% w / w solution of polyvinyl butyral in toluene and 4 g of soluble Mixed with plasticizer (dibutyl phthalate).

[0474] This slurry was then coated with silicon dioxide using a doctor blade (blade height set to 250 μm). The coating was tape cast onto the coated substrate and had a dry tape thickness of approximately 70 μm.

[0475] Electrode ink with 12.74 g of Ni powder and 3.64 g of a 7% w / w ethyl cellulose solution in solvent The electrodes were screen printed using a 400 mesh screen. The film was air dried and then oven dried at 120°C.

[0476] The bilayer film was fired in a tube furnace with a setter plate in which argon, H2, and H2O were flowing. The oxygen partial pressure within the tube is controlled by adjusting the relative flow rates of these three species. The binder is removed at 500°C. The film is sintered at approximately 1000-1200°C.

[0477] The bilayer membranes produced are shown in Figures 54, 55, and 56.

[0478] i. Example 9 - Powder, Slurry, Tape, and Bilayer 1 molar equivalent of Al2O3 and the required molar ratios of lithium hydroxide, zirconium oxide, and lanthanum oxide , and aluminum nitrate to form Li7Li3Zr2O 12 (LLZ) and alumina-containing powder The end was manufactured.

[0479] Dry the powder in an oven for 45 minutes to an hour, then ball the powder with 25% medium by volume. The mixture was dry-milled for 8 hours using a grinding technique. The media was separated using a sieve and then heated at 900°C in air. The mixture was calcined at rt for 6 hours to produce garnet powder.

[0480] Then, 300 g of this calcined garnet powder was used to prepare a slurry, which was then mixed for 30 g of dispersant, particle size (d 50 Add 300g of isopropanol or toluene until the viscosity reaches 300-400nm. The mixture was milled at a temperature of 4:1 in toluene and ethanol.

[0481] 35 g of this slurry was added to 2.65 g of a dispersing agent (e.g., Rhodoline 4160) and the zirconia catalyst was added. The mixture was crushed for 8 hours in a bottle (1 / 4 of the bottle volume). Indole was added to the slurry and milled for an additional 12 hours. 1.5 g of toluene was added and Mix for 2 hours.

[0482] Using a doctor blade setting and a blade height setting of 20 mils, apply the tape to the Mylar. The green tape was produced by casting the film onto a tape. The film was dried and then The film was separated from the Mylar. Ni was screen printed as Ni ink onto the dried film. Film disc was cut for sintering.

[0483] By placing the cut membrane with Ni on it between ceramic setter plates, The samples were sintered inside a tube furnace, which was heated to 200 °C at 5 °C / min in moist Ar. The mixture was heated to 200°C, held at 200°C for 4 hours, then heated at 5°C / min to 600°C, held for 4 hours, then heated at 10°C / min to 600°C. The furnace was heated at °C / min to 1100 °C and held for 1 hour at 315 sccm Ar and 10 sccm Ar / H. Cooled.

[0484] (j. Example 10 - Bilayer Membrane) As shown in Figure 59, by evaporating ~2um of Li on one side of the garnet side, A two-layer half-cell was fabricated.

[0485] Impedance (EIS) and plating were examined. Plating was examined using EIS with a linear voltage sweep. The plating started with the voltage at 0V (vs. OCV). After a pause, the initial plating was done at 200uA. The application and removal were performed at 100 μA with a rest period in between. Then, the final removal was performed at 200 μA. The results are shown in Figures 53 and 61.

[0486] k. Example 11 - Freestanding Membrane The required molar ratios of lithium hydroxide, zirconium oxide, lanthanum oxide, and aluminum nitrate The powder was produced by batch processing of aluminum to form an LLZ containing 1 molar amount of Al2O3. The powder was dried in an oven for 45 minutes to an hour, and then the volume was Dry milling was carried out for 8 hours using a ball milling technique with 25% media at 100°C, and the media was separated. The powder was then calcined in air at 900°C for 6 hours to produce garnet powder.

[0487] A slurry was prepared using 300 g of this calcined garnet powder, and the particle size (d 50 ) is 300~400nm 60 g of the slurry was attrition milled in 200 g of isopropanol and 30 g of dispersant until 5.35 g of dispersant (e.g., Rhodoline 4160) was added and milled with zirconia media for 8 hours. 3. 57g of the plasticizer dibutyl phthalate was added to 3.57g of the binder and milled at low rpm for an additional 12 hours. Then, 6.5 g of toluene was added and mixed for 2 hours.

[0488] Using a doctor blade setting and a blade height setting of 20 mils, the green tape was The film was manually cast onto Mylar tape. The film was allowed to dry and then separated from the Mylar. The membrane was cut to form discs for sintering.

[0489] The disks were sintered between ceramic setters in a tube furnace.

[0490] The samples were sintered by placing the cut membranes between ceramic setter plates. Sintering was carried out inside a tube furnace, which was heated to 200°C at 5°C / min in humid Ar and held at 200°C for 4 hours. The temperature was then heated to 600°C at 5°C / min, held for 4 hours, and then heated to 1100°C at 10°C / min. The furnace was heated and held at 315 sccm Ar and 10 sccm Ar / H for 1 hour, after which the furnace was cooled.

[0491] (l. Example 12 - Reaction Sintering) The required molar ratios of lithium hydroxide, zirconium oxide, lanthanum oxide, and aluminum nitrate A powder containing LLZ containing 1 molar equivalent of Al2O3 was produced by batch processing of the powder. The powder is dried in an oven for 45 minutes to 1 hour, and then ball milled using a medium that is 25% by volume. The mixture was then dried and ground for 8 hours using a sieve, separated from the medium, and then reacted. The powder was calcined in air at 900°C for 6 hours to produce garnet powder.

[0492] 300 g of calcined garnet powder was used with the reaction sintering precursor to prepare a slurry, and the particle size (d 50 ) until the particle size reached 300-400 nm, and 300 g of dispersant was added to 300 g of toluene / ethanol (4:1). or attrition-milled in diacetone.

[0493] 10 g of this slurry was mixed in a flactek mixer for 15 minutes, after which 0.2 g of binder was added to the slurry. The mixture was added to the slurry and mixed for an additional 15 minutes.

[0494] Using a doctor blade setting and blade height setting of 5 or 10 mils, slurries were sprayed with N. The green tape was produced by casting the film onto a foil. The film was dried and formed into a disk. was cut off.

[0495] Sintering was carried out by placing the membrane between ceramic setters in a tube furnace.

[0496] The samples were sintered by placing the cut membranes between ceramic setter plates. Sintering was carried out inside a tube furnace, which was heated to 200°C at 5°C / min in humid Ar and held at 200°C for 4 hours. The temperature was then heated to 600°C at 5°C / min, held for 4 hours, and then heated to 1100°C at 10°C / min. The furnace was heated and held at 315 sccm Ar and 10 sccm Ar / H for 1 hour, after which the furnace was cooled.

[0497] m. Example 13 - Low Area Specific Resistivity (ASR) In this example, a ceramic setter was compared to a metal setter. The films were prepared in accordance with Example 12 in some cases, resulting in garnet films with lower ASR. In some cases, a Pt setter plate is used, and in other cases, a ceramic setter plate is used. The powder was then sintered.

[0498] As shown in Figure 61, the films sintered using ceramic setter plates exhibited lower AS It had R.

[0499] The results are also shown in the table below.

[0500] Table 1 [Table 1]

[0501] These examples show the formation of a high-resistivity layer at the interface between the garnet and solid electrolyte with a Li anode. This shows that this is compatible with a low tendency to

[0502] (n. Example 14 - Low Area Specific Resistance (ASR) at the Pellet Surface) Pellets of lithium-loaded garnet were prepared as detailed above. The pellets were heated in Ar The samples were sintered either in a mixture of Ar / H2 or in air. The impedance results are shown in Figure 6. 2. The ASR is lower for Ar and Ar / H2 than for air.

[0503] Although the foregoing embodiments have been described in some detail for clarity of understanding, certain It will be evident that changes and modifications may be practiced within the scope of the appended claims. It should be noted that there are many alternative ways of implementing such processes, systems, and apparatus. Therefore, the present embodiments should be considered as illustrative and not restrictive. and the embodiments should not be limited to the details set forth herein. The present application provides the following inventions. (Configuration 1) A composition comprising a lithium-filled garnet and Al2O3, wherein the lithium-filled garnet However, the empirical formula is Li A La B M' c M'' D Zr E O F is characterized by During the ceremony, 4 <A<8.5、1.5<B<4、0≦C≦2、0≦D≦2、0≦E≦2、10<F≦13であり、 M' and M'' are, independently in each occurrence, absent or selected from Al, Mo, W, Nb, Sb, Ca, Ba, are each independently selected from Sr, Ce, Hf, Rb, or Ta; and The composition wherein the molar ratio of garnet:Al2O3 is 0.05 to 0.7. (Configuration 2) Empirical formula (Chemical formula 1) The composition according to Configuration 1, characterized by TIFF2025060723000007.tif7170; wherein 5.0 < x < 9 and 0.1 < y < 1.5. (Configuration 3) Empirical formula Li 7.0 La3(Zr t1 + Nb t2 + Ta t3 )O 12 Characterized by +0.35Al2O3; Wherein, so that the molar ratio of the combined amount of La and (Zr + Nb + Ta) is 3:2, t1 + t2 + t3 = 2 The composition according to Configuration 1. (Configuration 4) Empirical formula Li7La3Zr2O 12 ·0.35Al2O3, the composition according to Configuration 1. (Configuration 5) The composition according to Configuration 1, wherein A is 5, 6, 7, or �. (Configuration 6) The composition according to Configuration 5, wherein A is 7. (Configuration 7) The composition according to Configuration 1, wherein M' is Nb and M'' is Ta. (Configuration 8) The composition according to Configuration 1, wherein E is 1, 1.5, or 2. (Configuration 9) The composition according to Configuration 8, wherein E is 2. (Configuration 10) The composition according to Configuration 1, wherein C and D are 0. (Configuration 11) The composition according to Configuration 1, wherein the molar ratio of garnet:Al2O3 is 0.1 to 0.65. (Configuration 12) The composition according to Configuration 1, wherein the molar ratio of garnet:Al2O3 is 0.15 to 0.55. (Configuration 13) 2. The composition of claim 1, wherein the molar ratio of garnet:Al2O3 is 0.25 to 0.45. (Configuration 14) 2. The composition of claim 1 wherein the molar ratio of garnet:Al2O3 is 0.35. (Configuration 15) 2. The composition of claim 1 wherein the molar ratio of Al to garnet is 0.35. (Configuration 16) The lithium-filled garnet has an empirical formula of Li7La3Zr2O 12 It is characterized by a 10. The composition of claim 1, wherein the composition is doped with an amount of alumina. (Configuration 17) 17. An electrochemical device having an electrolyte made of the composition according to any one of aspects 1 to 16. (Configuration 18) 17. An electrochemical device comprising a catholyte made of the composition according to any one of aspects 1 to 16. (Configuration 19) The subscript values ​​represent the precursor chemicals used to make the claimed compositions. 17. The composition of any one of claims 1 to 16, wherein the molar ratio of elements is expressed. (Configuration 20) 17. The composition according to any one of claims 1 to 16, which is a thin film having a thickness of about 10 nm to about 100 μm. thing. (Configuration 21) 21. The membrane of claim 20, wherein the thickness is less than 50 μm and greater than 10 nm. (Configuration 22) 21. The membrane of claim 20, wherein the thickness is less than 40 μm and greater than 10 nm. (Configuration 23) 21. The membrane of claim 20, wherein the thickness is less than 30 μm and greater than 10 nm. (Configuration 24) 21. The membrane of claim 20, wherein the thickness is less than 20 μm and greater than 10 nm. (Configuration 25) 21. The membrane of claim 20, wherein the thickness is less than 10 μm and greater than 10 nm. (Configuration 26) 21. The membrane of claim 20, wherein the thickness is less than 5 μm and greater than 10 nm. (Configuration 27) 21. The membrane of claim 20, wherein the thickness is less than 1 μm and greater than 10 nm. (Configuration 28) 21. The membrane of claim 20, wherein the thickness is less than 0.5 μm and greater than 10 nm. (Configuration 29) d less than 10 μm 50 21. The membrane of claim 20, having grains with a diameter. (Configuration 30) d less than 9 μm 50 21. The membrane of claim 20, having grains with a diameter. (Configuration 31) d less than 8 μm 50 21. The membrane of claim 20, having grains with a diameter. (Configuration 32) d less than 7 μm 50 21. The membrane of claim 20, having grains with a diameter. (Configuration 33) d less than 6 μm 50 21. The membrane of claim 20, having grains with a diameter. (Configuration 34) d less than 5 μm 50 21. The membrane of claim 20, having grains with a diameter. (Configuration 35) The membrane has a d 50 21. The composition of claim 20, having grains with a diameter. (Configuration 36) The membrane has a d 50 21. The composition of claim 20, having grains with a diameter. (Configuration 37) The membrane has a d 50 21. The composition of claim 20, having grains with a diameter. (Configuration 38) The membrane has a d 50 21. The composition of claim 20, having grains with a diameter. (Configuration 39) 1. A method for making an aluminum-doped lithium-filled garnet, comprising: providing garnet precursors in a predetermined combination; optionally, drying the precursor at about 80°C to about 200°C for about 10 minutes to about 10 hours; milling the combination for 5 to 10 hours; The combination is calcined in a vessel at about 500°C to about 1200°C for about 4 to about 10 hours to form a garnet phase. To form; The formed garnet is called d 50 Grinding to a particle size of 100-1000 nm; The crushed formed garnet is mixed with a binder to add plasticizers, dispersants, and garnet chemicals. and optionally at least one member selected from the group consisting of precursors, forming a slurry comprising: optionally filtering the slurry; optionally providing a green film of said slurry; sintering the slurry or sintering the green film; wherein sintering comprises: applying pressure to the slurry with a setting plate; heating the slurry under a flowing gas at 140°C to 1200°C for about 15 minutes to about 6 hours; and The method includes thermally sintering or electric field assisted sintering for about 10 minutes to about 10 hours. (Configuration 40) The garnet precursor is selected from the group consisting of LiOH, Li2O, Li2CO3, La2O3, ZrO2, and Al(NO3)3.9H2O. 40. The method of claim 39, wherein the selected (Configuration 41) Calcining the combination is carried out in a vessel at 900°C for 6 hours or less. 41. The method according to claim 39 or 40. (Configuration 42) 42. Any one of claims 39 to 41, wherein the calcining step includes using an alumina container. The method described. (Configuration 43) grinding the formed garnet, 50 The particle size is increased to 400 nm. The method described in Seki 39. (Configuration 44) The crushed formed garnet is mixed with a binder to form a slurry. 44. The method of any one of claims 39 to 43, comprising about 4% w / w of a binder. (Configuration 45) 45. The method of any one of claims 39 to 44, wherein the binder is polyvinyl butyral. . (Configuration 46) 39. The method of claim 38, wherein filtering the slurry comprises filtering through an 80 mesh sieve. How to post. (Configuration 48) Applying pressure to the slurry with a setting plate provides a pressure of 3 metric tons. 40. The method of claim 39, comprising adding: (Configuration 49) 40. The method of claim 39, wherein the setter plate is a Pt setter plate. (Configuration 50) 40. The method of claim 39, wherein the flowing gas is argon gas flowing at a flow rate of 315 sccm. (Configuration 51) The slurry is heated under flowing inert gas, and the temperature is increased to 160°C to 200°C under a flow of humidified argon. Any of configurations 39-50, including separate dwells of 2-4 hours (hr) at 300°C and 330°C-600°C. The method described in section. (Configuration 52) grinding the formed garnet, 50 is continued until the wavelength is 200 to 450 nm. 40. The method of claim 39. (Configuration 53) grinding the formed garnet, 50 is continued until it reaches 200 to 400 nm. 40. The method of claim 39. (Configuration 54) grinding the formed garnet, 50 until the thickness is about 350 nm. 39. The method described in 39. (Configuration 55) 39. An energy storage device comprising the electrolyte according to any one of aspects 1 to 38. (Configuration 56) 1. A method for making an aluminum-doped lithium-filled garnet, comprising: providing garnet precursors in a predetermined combination; grinding said combination; The combination is calcined in a vessel at about 500°C to about 1200°C for about 0.5 to about 10 hours to form a garnet. To form; and The formed garnet is called d 50 Grind until the particle size is 10nm to 500μm The method comprising: (Configuration 57) Garnet precursors or calcined garnets; At least one selected from the group consisting of a binder, a solvent, a dispersant, and combinations thereof 1 member; A thin, free-standing, unsintered garnet film comprising: a garnet solids loading of at least 30% by volume (v / v); and The unsintered garnet film has a thickness of less than 100 μm. (Configuration 58) 58. The membrane of embodiment 57, further comprising a substrate adhered to the membrane. (Configuration 59) The substrate may be a polymer, a metal foil, a metal powder, a metal powder film, or a metal coating on a substrate. 59. The membrane of claim 58, (Configuration 60) 59. The method of claim 58, wherein the metal is selected from Ni, Cu, Al, steel, an alloy, or a comb...

Claims

1. A bilayer comprising a metal foil or metal powder placed in contact with a lithium-filled garnet thin film. There was, the lithium-filled garnet thin film is a thin sintered garnet film, The lithium-filled garnet thin film has a thickness of less than 50 μm and more than 10 nm; and The lithium-filled garnet thin film is coated with the metal foil or powder on at least one side of the film. It is connected to the end, The lithium-filled garnet is characterized by one of the following formulas: Layering: Li A La B M’ C M’’ D Zr E O F 、Li A La B M’ C M’’ D Ta E O F 、Li A La B M’ C M’’ D Nb E O F (wherein, 4 < A<8.5, 1.5<B<4, 0≦C≦2, 0≦D≦2, 0≦E<2, 10<F≦13, and M' and M' ' each independently in each occurrence is Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta ) selected from; The a The b Zr c Al d I'' e O f (5-a-7.7, 2-b-4, 0-c≦2.5, 0≦d-2,0≦e-2、 10<f≦13, and Me″ is a metal selected from Nb, Ta, V, W, Mo, or Sb. ); Al 2 O 3 Doped Li A La B M' c M'' D Zr E O F (In the formula, Al 2 O 3 Lithium-filled garnet The molar ratio to is 0.05 to 0.7; Li g La 3 Zr 2 O 12 -Al 2 O 3 (Wherein, 5.5<g<8.5 and Al 2 O 3 Lithium-filled garnet The molar ratio of ethylene to ethylene is 0.05 to 1.0; 【Chemistry 1】 where 5.0<x<9 and 0.1<y<1.5; or Li x La 3 Zr 2 O 12 +yAl 2 O 3 (wherein 5.5≦x≦9 and 0≦y≦1).

2. The metal is Ni; Al; Fe; stainless steel; an alloy of Ni, Cu, Al, or Fe; or Ni, Cu, 2. The bilayer of claim 1, wherein the bilayer is a combination of Al, Fe, or Al.

3. 13. An electrochemical stack comprising at least two or more bilayers according to claim 1.

4. The lithium-filled garnet thin film of claim 1, wherein the lithium-filled garnet thin film has a thickness of 1 μm to 150 μm. layer.

5. 10. The bilayer of claim 1, wherein the bilayer comprises a metal foil, and the metal foil is a current collector.

6. A triple layer comprising the bilayer of claim 1, wherein the bilayer is in contact with the metal foil or metal powder. the trilayer further comprising a second lithium-filled garnet thin film in contact therewith.

7. 10. The bilayer of claim 1, wherein the lithium-filled garnet thin film has a thickness of less than 20 μm.

8. 2. The method of claim 1, wherein the lithium-filled garnet thin film has a surface roughness of less than 5 μm. Layered.

9. The lithium-filled garnet thin film has a median grain size of 0.1 μm to 10 μm. Item 1. The bilayer according to item 1.

10. The lithium-filled garnet thin film has a median grain size of 1.0 μm to 5.0 μm. Item 1. The bilayer according to item 1.

11. The lithium-filled garnet has the empirical formula 【Chemistry 2】 2. The method according to claim 1, characterized by: wherein 5.0<x<9 and 0.1<y<1.

5. Layered.

12. The lithium-filled garnet is Li a La b Zr c Al d Me'' e O f (where 5<a<7.7, 2<b<4 , 0 < c ≦ 2.5, 0 ≦ d < 2, 0 ≦ e < 2, 10 < f ≦ 13, and Me ″ is Nb, Ta, W, Mo, or Sb.

13. 13. The bilayer of claim 12, wherein e=0.

14. 13. The bilayer of claim 12, wherein 10<f<13.

15. 13. The bilayer of claim 12, wherein a<7.

16. 13. The bilayer of claim 12, wherein 0.3<d<1.

17. The lithium-filled garnet is Li x La 3 Zr 2 O 12 .Al 2 O 3 At least one selected from the group consisting of 2. The bilayer of claim 1, comprising one member each of:

18. The bilayer of claim 5, wherein the metal is Cu.

19. 6. The bilayer of claim 5, wherein the metal is Ni.

Citation Information

Patent Citations

  • Ceramic material and preparation method therefor

    JP2011073962A

  • All-solid secondary battery

    JP2012209256A

  • All-solid lithium ion battery

    JP2012243743A

  • Solid electrolyte and method for producing the same

    JP2013037992A